Polypropylene resin foamed particles and method for producing same
By preparing polypropylene-based resin foamed particles with specific composition and structure, the problem of insufficient in-mold forming properties of foamed particles containing ethylene propylene-based rubber is solved, and good in-mold forming properties and molding properties are achieved.
Patent Information
- Application Number
- CN202380065130.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-22
AI Technical Summary
When foamed particles made of polypropylene resin composition containing ethylene propylene rubber are used, there is room for improvement in mold forming properties.
By preparing polypropylene-based resin foamed particles having a specific melting point, acetone insoluble component in the n-decane extract and an average diameter of rubber-like body, the core layer consists of an impact-resistant polypropylene-based resin composition and a low-melting point polypropylene-based resin melting mixture, and foaming is performed by a specific manufacturing method.
Even when ethylene propylene rubber is included, polypropylene resin foamed particles have good in-mold molding properties, thereby improving the impact absorption performance and compressive properties of the molded body.
Smart Images

Figure CN119866358A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polypropylene resin foamed particles and a method for producing the same. Background Art
[0002] Polypropylene resin foamed particle molded bodies are used for various purposes such as packaging materials, containers, and impact absorbing materials because they are lightweight and have excellent rigidity and compression properties. Polypropylene resin foamed particle molded bodies are manufactured, for example, by a method called in-mold molding method in which polypropylene resin foamed particles are filled into a forming mold and heated with steam. In the in-mold molding method, when steam is supplied to the forming mold to heat the foamed particles, the foamed particles soften and the foamed particles are foamed twice. As a result, the foamed particles in the forming mold are welded to each other, and a molded body having a desired shape corresponding to the shape of the cavity of the forming mold can be obtained.
[0003] Incidentally, in recent years, from the perspective of reducing environmental load, recycled materials such as post-consumer materials have attracted attention. Examples of recycled materials including polypropylene resins include polypropylene resin components recovered from used home appliances and automobiles, and automobile shredder residue (hereinafter referred to as "ASR") generated during the scrapping of automobiles as described in Patent Document 1.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-122299 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The polypropylene resin composition derived from the above-mentioned recycled materials generally contains ethylene propylene rubber. The expanded beads produced using the polypropylene resin composition containing ethylene propylene rubber have room for improvement in terms of in-mold moldability during in-mold molding.
[0009] The present invention has been made in view of the above background, and an object of the present invention is to provide polypropylene resin foamed particles having good in-mold moldability even when containing ethylene propylene rubber, and a method for producing the same.
[0010] Means used to solve problems
[0011] One aspect of the present invention is the polypropylene resin foamed particles according to the following [1] to [6].
[0012] [1] A polypropylene resin foamed particle having a foamed layer composed of a polypropylene resin composition, wherein:
[0013] The polypropylene resin composition comprises a polypropylene resin and a rubber-like body comprising an ethylene-propylene rubber.
[0014] The rubber-like body is dispersed in the polypropylene resin,
[0015] The melting point Tm of the foamed particles is 130° C. or higher and 162° C. or lower.
[0016] [2] The polypropylene resin foamed particles according to [1], wherein
[0017] The amount of the acetone-insoluble component contained in the n-decane extract of the foamed beads is 0.02 g or more and 0.10 g or less per 1 g of the foamed beads,
[0018] The melting point Tm of the foamed particles is 140° C. or higher and 162° C. or lower.
[0019] A difference Tm-Tc between a melting point Tm of the foamed particles and a crystallization temperature Tc of the foamed particles is 38° C. or less.
[0020] [3] The polypropylene resin foamed particles according to [1] or [2], wherein the average diameter of the rubber-like body is 0.1 μm or more and 2 μm or less.
[0021] [4] The polypropylene resin foamed particles according to any one of [1] to [3], wherein the polypropylene resin composition constituting the foamed layer comprises a polypropylene resin derived from recycled polypropylene and an ethylene propylene rubber.
[0022] [5] The polypropylene resin foamed beads according to any one of [1] to [4], wherein the flexural modulus of the polypropylene resin composition constituting the foamed layer is 800 MPa to 1300 MPa.
[0023] [6] The polypropylene resin foamed particles according to any one of [1] to [5], wherein
[0024] The foamed beads have a crystal structure in which, in a DSC curve obtained when the foamed beads are heated from 23° C. to 200° C. at a heating rate of 10° C. / min, a first endothermic peak Pa having the largest peak area and a second endothermic peak Pb adjacent to the first endothermic peak Pa on the high temperature side of the first endothermic peak Pa appear;
[0025] The independent bubble rate of the foamed particles is more than 85%,
[0026] The temperature Tb of the top of the second endothermic peak Pb is 158° C. or higher,
[0027] The difference Tb-Ta between the temperature Tb of the top of the second endothermic peak Pb and the temperature Ta of the top of the first endothermic peak Pa is 15° C. or more and 30° C. or less,
[0028] A ratio hb / ha of a peak height hb of the second endothermic peak Pb to a peak height ha of the first endothermic peak Pa is 1.2 or more and 2.8 or less.
[0029] Another aspect of the present invention is a method for producing foamed polypropylene resin particles according to the following [7] to
[15] .
[0030] [7] A method for producing polypropylene resin foamed particles, the method comprising foaming polypropylene resin particles having a core layer to obtain polypropylene resin foamed particles having a foamed layer, wherein:
[0031] The core layer is composed of a molten mixture of a polypropylene resin composition containing ethylene-propylene rubber and having a melting point of 160° C. or higher, and a polypropylene resin having a melting point of 125° C. or higher and less than 160° C.
[0032] The mass ratio of the polypropylene resin composition to the polypropylene resin in the core layer is polypropylene resin composition:polypropylene resin=2:98 to 70:30.
[0033] [8] The method for producing polypropylene resin foamed particles according to [7], wherein the melting point of the polypropylene resin is 130°C or higher and lower than 160°C.
[0034] [9] The method for producing polypropylene resin foamed particles according to [7] or [8], wherein the polypropylene resin composition is impact-resistant polypropylene.
[0035]
[10] The method for producing foamed polypropylene resin particles according to any one of [7] to [9], wherein the melting point Tm of the polypropylene resin composition is I The melting point Tm of the polypropylene resin B Difference Tm I -Tm B It is 5°C or higher and 35°C or lower.
[0036]
[11] The method for producing polypropylene resin foamed particles according to any one of [7] to
[10] , wherein the melt mass flow rate (MFR) of the polypropylene resin composition measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is IIt is 3 g / 10 minutes or more and 40 g / 10 minutes or less.
[0037]
[12] The method for producing foamed polypropylene resin particles according to any one of [7] to
[11] , wherein the flexural modulus of the polypropylene resin composition is 800 MPa to 1200 MPa.
[0038]
[13] The method for producing expanded polypropylene resin particles according to any one of [7] to
[12] , wherein the polypropylene resin composition comprises a polypropylene resin derived from recycled polypropylene and an ethylene propylene rubber.
[0039]
[14] A method for producing polypropylene resin foamed particles according to any one of [7] to
[13] , wherein the resin particles impregnated with a foaming agent and dispersed in an aqueous medium in a container are released from the container together with the aqueous medium in an atmosphere having a pressure lower than the pressure in the container, thereby causing the resin particles to foam to obtain foamed particles.
[0040]
[15] The method for producing foamed polypropylene resin particles according to any one of [7] to
[14] , wherein:
[0041] The melting point Tm of the polypropylene resin composition I The melting point Tm of the polypropylene resin B Difference Tm I -Tm B 5℃ or above and 35℃ or below,
[0042] The melt mass flow rate MFR of the polypropylene resin composition measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is I More than 3g / 10 minutes,
[0043] The melt mass flow rate MFR of the polypropylene resin measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is B 3g / 10min or more and 10g / 10min,
[0044] The melt mass flow rate MFR of the polypropylene resin composition I Relative to the melt mass flow rate MFR of the polypropylene resin B MFR I / MFR B It is 0.3 or more and 8 or less.
[0045] Effects of the Invention
[0046] According to the above aspect, it is possible to provide polypropylene resin foamed particles (hereinafter referred to as "foamed particles") having good in-mold moldability even when containing ethylene propylene rubber, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is an explanatory diagram showing a method for calculating the heat of fusion of a high temperature peak.
[0048] Figure 2 It is an explanatory diagram showing a method for calculating the peak height and the half maximum width of each endothermic peak in a DSC curve.
[0049] Figure 3 This is an electron microscope photograph showing the state of the polypropylene resin composition A1-1 in the example.
[0050] Figure 4 This is an electron microscope photograph showing the morphology of the expanded beads of Example 1-4.
[0051] Figure 5 This is an electron microscope photograph showing the morphology of the resin particles of Example 1-4. DETAILED DESCRIPTION
[0052] (Polypropylene resin foam particles)
[0053] The polypropylene resin composition constituting the foamed layer of the foamed beads includes a polypropylene resin and a rubber-like body including an ethylene-propylene rubber. The details of the polypropylene resin composition constituting the foamed layer will be described later.
[0054] 〔Melting point〕
[0055] The melting point Tm of the foamed beads is 130° C. to 162° C. When the melting point Tm of the foamed beads is within the specific range, the in-mold moldability of the foamed beads can be improved.
[0056] When the melting point Tm of the foamed particles is too low, there is a risk of reducing the compressive properties of the polypropylene resin foamed particle molded body (hereinafter referred to as the "foamed particle molded body" or "molded body") formed by in-mold molding of the foamed particles. In addition, in this case, there is a risk that the change in stress becomes larger when the compressive strain applied to the molded body increases. From the viewpoint of more easily improving the compressive properties of the molded body, the melting point Tm of the foamed particles is preferably above 135°C, more preferably above 140°C, further preferably above 143°C, particularly preferably above 146°C, and most preferably above 150°C.
[0057] When the melting point Tm of the expanded beads is too high, there is a possibility that the moldability may be reduced. From the viewpoint of more easily obtaining expanded beads with good moldability, the melting point Tm of the expanded beads is preferably 160°C or less, more preferably 158°C or less.
[0058] When constituting the preferred range of the melting point Tm of the foamed particles, the upper limit and lower limit of the melting point Tm of the foamed particles described above may be arbitrarily combined. For example, the preferred range of the melting point Tm of the foamed particles may be 135°C or more and 160°C or less, 140°C or more and 158°C or less, 143°C or more and 158°C or less, 146°C or more and 158°C or less, or 150°C or more and 162°C or less.
[0059] The melting point Tm of the foamed particles is determined based on JIS K7121-1987. Specifically, first, a test piece composed of foamed particles is prepared, and the state of the test piece is conditioned based on "(2) After a certain heat treatment, the melting temperature is measured" in "3. Conditioning of the test piece" in JIS K7121-1987. The heating rate and the cooling rate in the state conditioning are both set to 10°C / min. The state-conditioned test piece is heated from 30°C to 230°C at a heating rate of 10°C / min, thereby obtaining a DSC curve, and the vertex temperature of the melting peak that appears in the DSC curve is taken as the melting point Tm of the foamed particles. In addition, the flow rate of nitrogen in the measurement environment is set to 30 mL per minute. In addition, in the case where multiple melting peaks appear in the DSC curve, the vertex temperature of the melting peak with the highest height based on the baseline is taken as the melting point Tm of the foamed particles.
[0060] 〔Acetone-insoluble components in n-decane extract〕
[0061] The acetone-insoluble components contained in the n-decane extract of the foamed particles (hereinafter, the acetone-insoluble components are referred to as “D in the foamed particles”) sol -A insol The amount of D in the foamed particles is preferably 0.02 g or more and 0.10 g or less per 1 g of the foamed particles. sol -A insol It is mainly composed of ethylene propylene rubber. sol -A insol When the amount of D in the foamed particles is set within the specific range, the in-mold formability of the foamed particles can be further improved. In addition, by in-mold forming the foamed particles, the impact absorption performance of the molded body can be further improved. As a reason for this, it is believed that D in the foamed particles sol -A insolThe amount of the foamed particles within the specific range can suppress the excessive increase in stress of the molded body when a high compressive strain is applied, or can reduce the change in stress associated with the increase in compressive strain. In addition, as described later, the n-decane extract is prepared by heating the foamed particles in n-decane at 145° C. and then cooling to 23° C.
[0062] From the viewpoint of further improving the impact absorption performance of the molded article, D in the foamed particles sol -A insol The amount is more preferably 0.03 g or more, and further preferably 0.04 g or more per 1 g of the foamed beads.
[0063] On the other hand, D in the foamed particles sol -A insol If the amount of D in the foamed particles is too large, there is a risk of reducing the moldability of the foamed particles. sol -A insol The amount of D in the foamed beads is preferably 0.09 g or less, further preferably 0.08 g or less, and particularly preferably 0.07 g or less per 1 g of the foamed beads. sol -A insol The method of adjusting the amount to within the specific range can be, for example, a method of adjusting the amount of ethylene propylene rubber contained in the resin raw material and the mixing ratio of the resin raw material containing the ethylene propylene rubber during the production process of the foamed particles.
[0064] D in the foamed particles sol -A insol When the preferred range of the amount is sol -A insol For example, D in the foamed particles sol -A insol A preferred range of the amount may be 0.03 g to 0.09 g, 0.04 g to 0.08 g, or 0.04 g to 0.07 g per 1 g of the foamed beads.
[0065] D in foamed particles sol -A insolThe method for determining the amount of is as follows. First, the foamed particles are heated in n-decane at 145°C and then cooled to 23°C to prepare a n-decane extract. More specifically, the n-decane soluble components in the foamed particles are dissolved in the n-decane by adding the foamed particles to the n-decane and heating to a temperature of 145°C. After the n-decane solution is cooled to 23°C, the components precipitated in the n-decane solution that are insoluble in n-decane at 23°C are removed, thereby obtaining a n-decane extract containing n-decane soluble components. The acetone insoluble components in the n-decane extract (i.e., D in the foamed particles) are removed by adding the n-decane extract to acetone. sol -A insol Based on the mass of the precipitate obtained above and the mass of the foamed particles used in the measurement, the D contained in each 1g of the foamed particles can be calculated. sol -A insol About D in foamed particles sol -A insol A more detailed method for determining the amount is described in detail in the examples.
[0066] [Difference between melting point Tm and crystallization temperature Tc: Tm-Tc]
[0067] The difference Tm-Tc between the melting point Tm of the foamed particles and the crystallization temperature Tc of the foamed particles is preferably 38°C or less. In the past, when foamed particles containing ethylene propylene rubber were subjected to in-mold molding, the molded body immediately after the in-mold molding was completed was prone to local shrinkage, and there was a tendency that it was difficult to stably obtain a molded body with a desired shape. In contrast, by setting the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc of the foamed particles within the specific range, the local shrinkage of the molded body after in-mold molding can be more effectively suppressed even if the foamed particles contain ethylene propylene rubber, and a molded body with a desired shape can be more easily obtained. In addition, the lower limit of the difference Tm-Tc in the foamed particles is generally 30°C. The lower limit of the difference Tm-Tc is preferably 32°C.
[0068] The crystallization temperature Tc of the foamed particles is measured based on JIS K7121-1987 using a heat flux differential scanning calorimeter. More specifically, first, the foamed particles are heated from 23°C to 230°C at a heating rate of 10°C / min. Then, after maintaining the temperature of 230°C for 10 minutes, the temperature is cooled from 230°C to 30°C at a cooling rate of 10°C / min, thereby obtaining a DSC curve. The vertex temperature of the crystallization peak in the DSC curve is taken as the crystallization temperature Tc of the foamed particles. In addition, the flow rate of nitrogen in the measurement environment is set to 30 mL per minute. In addition, when multiple crystallization peaks appear in the DSC curve, the vertex temperature of the crystallization peak with the highest peak height is taken as the crystallization temperature Tc of the foamed particles.
[0069] [Polypropylene resin composition]
[0070] The foaming layer of the foamed particles is composed of a polypropylene resin composition (hereinafter also referred to as "resin composition") containing a polypropylene resin and the rubber-like body. In this specification, the polypropylene resin composition refers to a resin composition with a polypropylene resin as a main component. More specifically, the mass ratio of the polypropylene resin in the resin composition is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 80% by mass or more.
[0071] In this specification, polypropylene resin refers to a homopolymer of propylene monomer (i.e., propylene homopolymer), a propylene copolymer containing more than 70% by mass of a structural unit from propylene, and a mixture of a propylene homopolymer and the propylene copolymer. As the propylene copolymer, copolymers of propylene and ethylene and / or α-olefins with more than 4 carbon atoms can be cited. The propylene copolymer can be a random copolymer or a block copolymer. In addition, the total content of the structural unit from ethylene in the propylene copolymer and the content of the structural unit from α-olefins with more than 4 carbon atoms is preferably more than 1% by mass and less than 15% by mass, more preferably more than 2% by mass and less than 12% by mass. In addition, polypropylene resin and elastomers such as ethylene propylene rubber are different substances from each other. In this regard, polypropylene resin is distinguished from a polypropylene resin composition containing ethylene propylene rubbers such as impact polypropylene.
[0072] In addition, the rubber-like body includes ethylene propylene rubber. In this specification, ethylene propylene rubber refers to a rubber-like substance composed of an ethylene propylene copolymer containing an ethylene component and a propylene component. That is, the ethylene propylene rubber can be a copolymer of ethylene and propylene (i.e., EPM). In addition, the ethylene propylene rubber can also be an ethylene propylene copolymer (e.g., EPDM) containing components derived from monomers other than ethylene and propylene, such as diene, within the range that does not impair the above-mentioned effects. The mass ratio of the component derived from ethylene to the component derived from propylene in the ethylene propylene rubber (component derived from ethylene: component derived from propylene) is generally 30:70 to 80:20.
[0073] The rubber-like body is dispersed in the polypropylene resin. Specifically, the rubber-like body exists as a micro-domain (i.e., dispersed phase) dispersed in a matrix (i.e., continuous phase) composed of the polypropylene resin. That is, the foaming layer of the foamed particles has a morphology with the polypropylene resin as the matrix and the rubber-like body as the micro-domain. In addition, in the rubber-like body, in addition to the ethylene-propylene rubber, a polyethylene resin may also be included. The existence form of the rubber-like body in the foaming layer can be confirmed by observing the morphology of the foamed particle cross section shown below.
[0074] The observation method of the morphology of the foamed particles is as follows. First, a sample for observation is cut out near the center of the foamed particles. Then, the sample for observation is embedded in an epoxy resin, and after electron staining with ruthenium tetroxide, a supermicrotome is used to make a slice from the sample. The slice is placed on a microgrid of a transmission electron microscope (e.g., "JEM-1040Flash" manufactured by JEOL), observed at a predetermined magnification (e.g., 5000 times), and a cross-sectional photograph (i.e., TEM photograph) of the foamed particles is taken. The morphology of the phase of the polypropylene resin in the foaming layer and the phase of the rubber-like body containing ethylene propylene rubber is observed visually from the cross-sectional photograph.
[0075] From the viewpoint of being able to stably improve the in-mold formability of the foamed particles, the average diameter of the rubber-like body containing ethylene-propylene rubber dispersed in the polypropylene resin is preferably 0.1 μm or more and 2 μm or less, more preferably 0.3 μm or more and 1.5 μm or less, and further preferably 0.5 μm or more and 1 μm or less. The average diameter of the rubber-like body is calculated based on the TEM photo. Specifically, the longest diameter and the shortest diameter of more than 50 micro-regions randomly selected from the micro-regions (i.e., the phase of the rubber-like body) appearing in the TEM photo are measured respectively, and their arithmetic average is calculated. The arithmetic mean of the longest diameter and the shortest diameter obtained in this way is used as the average diameter of the rubber-like body containing ethylene-propylene rubber.
[0076] The polypropylene resin composition constituting the foaming layer is preferably a molten mixture of impact-resistant polypropylene and a polypropylene resin, more preferably a molten mixture of impact-resistant polypropylene having a melting point of 160°C or more and a polypropylene resin having a melting point of 125°C or more and less than 160°C, and further preferably a molten mixture of impact-resistant polypropylene having a melting point of 160°C or more and a polypropylene resin having a melting point of 130°C or more and less than 160°C. By constituting the foaming layer with such a molten mixture, foamed particles having good in-mold formability can be stably obtained. In addition, by in-mold molding of the foamed particles, a molded body with a small change in stress accompanying an increase in compressive strain can be more stably obtained.
[0077] In addition, impact-resistant polypropylene is a polypropylene resin composition in which a rubber-like body including ethylene-propylene rubber is dispersed in a polypropylene resin. As impact-resistant polypropylene, for example, commercially available impact-resistant polypropylene used as a polypropylene resin composition for forming a vehicle component can be cited. In addition, impact-resistant polypropylene includes a multistage polymer produced by copolymerizing ethylene and propylene in the presence of a propylene polymer through multistage polymerization, and a mixture produced by melt-mixing a polypropylene resin and an ethylene-propylene rubber.
[0078] In addition, from the viewpoint of more easily obtaining the above-mentioned effects, the viewpoint of effective utilization of resources, and the viewpoint of material recycling, the polypropylene resin composition constituting the foamed layer preferably contains a polypropylene resin derived from recycled polypropylene, and more preferably contains a polypropylene resin derived from recycled polypropylene and an ethylene-propylene-based rubber. Hereinafter, the polypropylene resin composition containing a polypropylene resin derived from recycled polypropylene and an ethylene-propylene-based rubber is also referred to as "resin composition A".
[0079] Examples of the recycled polypropylene include polypropylene resin compositions derived from pre-consumer materials, polypropylene resin compositions derived from post-consumer materials, etc. In addition, the recycled polypropylene preferably contains ethylene propylene rubber derived from post-consumer materials.
[0080] In this specification, post-consumer materials refer to "materials discharged from households, or materials generated as products that can no longer be used for their original purpose from commercial facilities, industrial facilities, and various facilities that are end users of products" as described in JIS Q14021: 2000. In addition, post-consumer materials also include materials returned from the distribution path.
[0081] More specifically, the post-consumer materials include, for example, post-consumer materials from automotive components, post-consumer materials from home appliances, and the like. As post-consumer materials from automotive components, for example, exterior materials such as bumpers removed from used cars, interior materials such as dashboards, ASR (i.e., automobile crushing residue) generated during the scrapping of cars, and the like can be cited. A resin composition A containing ethylene propylene rubber is recovered from such post-consumer materials. The main component of the resin composition A is preferably an impact-resistant polypropylene in which a rubber-like body containing ethylene propylene rubber is dispersed in a polypropylene resin. In addition, the melting point of the polypropylene resin contained in the impact-resistant polypropylene is preferably above 160°C.
[0082] In addition, from the viewpoint of effective utilization of resources and material recycling, the main component of resin composition A is preferably a polypropylene resin composition a (hereinafter referred to as "resin composition a") derived from automotive components. More specifically, the mass ratio of resin composition a derived from automotive components in resin composition A is preferably 50% by mass or more, more preferably 60% by mass or more. In addition, the main component of resin composition A is more preferably a polypropylene resin composition a1 (hereinafter referred to as "resin composition a1") recovered from ASR. More specifically, the mass ratio of resin composition a1 recovered from ASR in resin composition A is preferably 50% by mass or more, more preferably 60% by mass or more.
[0083] The resin composition a1 recovered from ASR contains a polypropylene resin as a main component that has undergone a thermal process for forming automotive components. In addition, the resin composition a1 recovered from ASR generally contains polypropylene resins recovered from a plurality of automotive components and a plurality of used cars. For these reasons, it was previously considered difficult to use the resin composition a1 recovered from ASR for the production of foamed particles. In contrast, the foamed particles are obtained by increasing the D sol -A insol The amount of, the melting point Tm, and the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc are within the specific ranges, respectively, and the in-mold formability of the foamed particles can be improved even when the resin composition a1 recovered from ASR is used as a raw material. In addition, by using the foamed particles for in-mold forming, a molded body with a low rate of increase in compressive stress accompanying an increase in compressive strain can be easily obtained.
[0084] The main component of the polypropylene resin composition a is a polypropylene resin. The mass ratio of the polypropylene resin in the polypropylene resin composition a is preferably 50 mass % or more, more preferably 60 mass % or more, and even more preferably 70 mass % or more.
[0085] In addition, in this specification, ASR refers to "automobile shredding residue" defined in Article 2, Clause 5 of Law No. 87 of 2001, "Law concerning the recycling of used automobiles, etc." More specifically, the dismantled automobile after removing the engine, battery and other recyclable parts from the used automobile is shredded, and metals and other useful substances are separated from the shredded materials. The material remaining after these substances are recovered is called ASR. In ASR, in addition to polypropylene resins from automobile components, other plastics other than polypropylene resins such as polystyrene (PS) and acrylonitrile-butadiene-styrene resin (ABS), rubber, various metals, etc. are also included. The method for recovering the resin composition a1 from ASR is not particularly limited, and the resin composition a1 can be recovered from ASR by appropriately combining known sorting methods.
[0086] As an example of a method for obtaining ASR, there can be cited a method having a disassembly step, an accessory separation step, and a crushing and sorting step, wherein the disassembly step is to remove reusable parts and non-reusable parts from a used automobile, the accessory separation step is to remove automobile accessories from a disassembled automobile after the disassembly step, and the crushing and sorting step is to crush the disassembled automobile and / or automobile accessories after the separation step, and metals are separated from the obtained crushed material to recover ASR. More specifically, ASR can be obtained by the methods described in Japanese Patent No. 6609877, Japanese Patent No. 6627142, Japanese Patent No. 6762071, etc.
[0087] The resin composition a1 can be recovered by, for example, a method of performing the following separation steps (α) to (δ) alone or in combination of two or more.
[0088] (α) Magnetic separation process, which uses magnetic force to separate metals and non-metals
[0089] (β) Wind sorting process, using wind to sort light and heavy objects
[0090] (γ) Wet gravity separation process, using solvent to separate light and heavy objects
[0091] (δ) Electrostatic separation process, which separates resins by the ease with which they are charged
[0092] For example, in the wet specific gravity sorting process (γ), the resin composition a1 contained in the ASR can be sorted out by a method using water flow classification and sedimentation velocity as described in Japanese Patent No. 3711472, a method using a pulsating bubbling tank and a sedimentation tank that discharge bubbles intermittently, and a suspended solids separation tank for separating substances lighter than water and substances heavier than water as described in Japanese Patent Publication No. 2004-58032, etc. In addition, as described in Japanese Patent Publication No. 2008-178846 and Japanese Patent No. 6762071, these sorting processes can be combined. For example, the wind sorting process and the wet specific gravity sorting process are combined, and after the light and heavy objects contained in the ASR are separated by wind power, they are immersed in the sorting liquid separately for specific gravity sorting, thereby sorting out the resin composition a1 contained in the ASR.
[0093] 〔Welding layer〕
[0094] The foamed particles may have a single-layer structure formed only by a foaming layer composed of the resin composition, or may have a multi-layer structure having the foaming layer and a welding layer covering the foaming layer in order to improve the welding property of the foamed particles during in-mold molding. The welding layer may exist on the entire surface of the foamed particles or on a part of the surface. In addition, the welding layer may be in a foamed state or a non-foamed state, but is preferably substantially in a non-foamed state. In addition, the above-mentioned "non-foamed state" includes a state in which the welding layer is not foamed and does not contain bubbles and a state in which the bubbles disappear after foaming, which means that there is almost no bubble structure in the welding layer. In addition, in the case where the foamed particles have a foaming layer and a welding layer, the foaming layer covered by the welding layer is sometimes referred to as a "foamed core layer."
[0095] The method for producing foamed particles having a fusion layer is not particularly limited, and examples thereof include a method of foaming resin particles having a core layer in a non-foamed state and a fusion layer covering the core layer, a method of obtaining a foamed core layer by foaming a core layer in a non-foamed state, and then attaching a fusion layer to the surface of the foamed core layer, etc. In the case of foaming resin particles having a fusion layer on the surface to obtain foamed particles, the following method is preferably adopted: when producing resin particles, a molten mixture for forming a core layer and a resin melt for forming a fusion layer are co-extruded using an extrusion device capable of co-extrusion, thereby laminating a fusion layer on the core layer.
[0096] The ratio of the fusion bonded layer in the foamed beads is preferably approximately 0.5% by mass or more and 20% by mass or less, and more preferably 1% by mass or more and 10% by mass or less.
[0097] Examples of the base resin constituting the welding layer include a crystalline polyolefin resin having a lower melting point than the resin composition constituting the foamed core layer, an amorphous polyolefin resin having a lower softening point than the resin composition constituting the foamed core layer, etc. The base resin constituting the welding layer is preferably a polypropylene resin and / or a polyethylene resin, and more preferably a polypropylene resin.
[0098] When the base resin constituting the welding layer is a crystalline polyolefin resin having a melting point, the melting point of the crystalline polyolefin resin is preferably 100°C or higher and lower than 160°C, more preferably 110°C or higher and 158°C or lower, and further preferably 120°C or higher and 155°C or lower.
[0099] In addition, the difference between the melting point of the resin composition constituting the foam core layer and the melting point of the base resin constituting the welding layer is preferably approximately 1°C or more and 40°C or less, more preferably 2°C or more and 35°C or less, and further preferably 5°C or more and 30°C or less. In this case, even when the molding pressure is relatively low, the in-mold formability of the foamed particles can be improved. In addition, by in-mold molding of the foamed particles, a molded body with good compression properties can be more easily obtained.
[0100] In addition, the foamed particles may also have a cylindrical shape with a through hole that penetrates axially therein. For example, the foamed particles may also have a bottom surface, a top surface that is arranged above the bottom surface and has a shape substantially the same as the bottom surface, and a lateral surface that connects the end edge of the bottom surface with the end edge of the top surface, and have a through hole that penetrates axially inside the foamed particles and opens on the bottom surface and the top surface. In addition, the cylindrical shape includes a round cylinder, a square cylinder, etc. In addition, the number of through holes may also be two or more.
[0101] The average pore size of the through hole is preferably less than 1mm, more preferably less than 0.95mm, further preferably less than 0.90mm, and particularly preferably less than 0.85mm. In this case, the compression properties of the molded body can be ensured, and the cooling time during in-mold molding can be easily shortened. In addition, by using the foamed particles, even if the curing process of the foamed particles is shortened or omitted, a molded body with good surface properties can be easily obtained. In addition, from the viewpoint of ease of manufacture, the average pore size of the foamed particles is preferably approximately more than 0.2mm, more preferably more than 0.3mm.
[0102] In addition, the ratio of the average pore size of the through holes to the average outer diameter of the foamed particles is preferably 0.4 or less, more preferably 0.3 or less, and further preferably 0.25 or less. In this case, the compression properties of the molded body can be ensured, and the cooling time during in-mold molding can be easily shortened. In addition, by using the foamed particles, even if the curing process of the foamed particles is shortened or omitted, a molded body with good surface properties can be easily obtained. In addition, from the viewpoint of ease of manufacture, the ratio of the average pore size of the through holes to the average outer diameter of the foamed particles is preferably 0.1 or more.
[0103] 〔Flexural modulus〕
[0104] The bending elastic modulus of the resin composition constituting the foaming layer of the foamed beads is preferably more than 800MPa and below 1600MPa, more preferably more than 800MPa and below 1400MPa, further preferably more than 800MPa and below 1300MPa, particularly preferably more than 800MPa and below 1200MPa, most preferably more than 900MPa and below 1200MPa. In this case, the mold formability of the foamed beads can be improved more easily. In addition, by using this foamed beads to make a formed body, it is possible to easily obtain a formed body that the compressive stress is not easy to rise when applying compression strain.
[0105] The flexural modulus of the resin composition constituting the foamed layer can be obtained by measurement in accordance with JIS K7171: 2008. The test piece used for measuring the flexural modulus may be obtained from a non-foamed sheet produced by hot-pressing foamed beads, for example.
[0106] 〔Melt mass flow rate〕
[0107] The melt mass flow rate of the resin composition constituting the foaming layer when measured at a temperature of 230°C and a load of 2.16kg is preferably 5g / 10 minutes or more and 20g / 10 minutes or less, more preferably 8g / 10 minutes or more and 18g / 10 minutes or less, and further preferably 10g / 10 minutes or more and 16g / 10 minutes or less. In this case, the in-mold formability of the foamed particles can be more easily improved. In addition, by using the foamed particles for in-mold forming, it is easier to obtain foamed particles that can produce a molded body with good compression strength. The melt mass flow rate of the resin composition constituting the foaming layer is a value measured using foamed particles or resin particles as a sample, based on JIS K7210-1:2014, under the conditions of a test temperature of 230°C and a load of 2.16kg. In addition, the foamed particles used as a sample can be defoamed in advance.
[0108] [Bulk density of foamed particles]
[0109] The bulk density of the foamed particles is preferably 10 kg / m 3 Above and 200kg / m 3 Below, more preferably 12kg / m 3 Above and 100kg / m 3 Below, more preferably 15kg / m 3 Above and 80kg / m 3 Below, particularly preferably 20kg / m 3 Above and 70kg / m 3 In this case, a compact having a light weight and good compressive strength can be obtained more easily.
[0110] The calculation method of the bulk density of the foamed particles is as follows. First, the foamed particles are allowed to stand for more than 24 hours in an environment with a relative humidity of 50%, a temperature of 23°C, and an air pressure of 1 atm to adjust the state of the foamed particles. The foamed particles obtained in this way are filled into a measuring cylinder, and the bottom of the measuring cylinder is gently tapped on the ground several times to stabilize the filling height of the foamed particle group in the measuring cylinder. The bulk volume (unit: L) of the foamed particle group is read from the scale of the measuring cylinder. Then, the bulk density (unit: kg / m 3 ).
[0111] [Apparent density of foamed particles]
[0112] The apparent density of the foamed particles is preferably 10 kg / m 3 Above and 150kg / m 3 By making the apparent density of the foamed particles preferably 10 kg / m 3 More preferably 20kg / m 3 More preferably, 30 kg / m 3 In addition, the apparent density of the foamed beads is preferably 100 kg / m 3 Below, more preferably 80kg / m 3 Next, a lighter molded body can be obtained.
[0113] When constituting the preferred range of the apparent density of the foamed particles, the upper and lower limits of the apparent density mentioned above can be arbitrarily combined. For example, the apparent density can be 20 kg / m 3 Above and 100kg / m 3 Below, can also be 30kg / m 3 Above and 80kg / m 3 the following.
[0114] The method for calculating the apparent density of the foamed particles is as follows. First, the foamed particle group is allowed to stand for 1 day in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1 atm to adjust the state of the foamed particles. After measuring the mass of the foamed particle group (unit: g), use a metal mesh to sink it into a measuring cylinder filled with water at 23°C, and calculate the volume of the foamed particle group (unit: L) based on the amount of water surface rise. Afterwards, the apparent density of the foamed particles (unit: kg / m 3 ).
[0115] [Average bubble diameter of foamed particles]
[0116] The average bubble diameter of the foamed particles is preferably 40 μm to 100 μm, more preferably 45 μm to 90 μm, and even more preferably 50 μm to 80 μm. In this case, the in-mold formability of the foamed particles can be further improved, and a good molded body can be obtained more easily within a wider range of molding pressures.
[0117] The average bubble diameter of the foamed particles is a value calculated by the following method. First, the foamed particles are cut in approximately two equal parts. Next, an enlarged photograph is obtained in a manner that all the exposed cut surfaces are included in the field of view. On the obtained enlarged photograph, four line segments are drawn from the outermost surface of the foamed particles through the central part to the outermost surface of the opposite side in a manner that the angles formed by adjacent line segments are equal (that is, in a manner that the angles formed by adjacent line segments are 45°). The value obtained by dividing the total length of the four line segments obtained in this way by the total number of bubbles intersecting the line segments is used as the bubble diameter of each foamed particle.
[0118] The above operation is performed on ten or more foamed beads randomly selected, and the value obtained by arithmetic averaging the cell diameters of the foamed beads obtained for the respective foamed beads is defined as the average cell diameter of the foamed beads.
[0119] [Independent cell ratio of foamed particles]
[0120] The closed cell ratio of the foamed beads is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. In this case, the moldability of the foamed beads can be further improved, and a good molded body can be obtained more easily within a wider range of molding pressures.
[0121] The closed cell ratio of the foamed particles is a value measured using an air comparison type densitometer based on ASTM-D2856-70 step C. The method for measuring the closed cell ratio of the foamed particles is as follows. The stacked volume after state adjustment is about 20 cm 3The foamed particles are used as the measuring sample, and the apparent volume Va of the measuring sample is measured according to the amount of liquid level rise when the measuring sample is sunk into a measuring cylinder filled with ethanol. After the measuring sample after the apparent volume Va is measured is fully dried, the true volume value Vx of the measuring sample measured by an air comparison pycnometer ("Beckman Model 1000 Air Comparison Pycnometer" manufactured by Tokyo Science Co., Ltd.) is measured according to step C described in ASTM-D2856-70. Then, using these volume values Va and Vx, the independent bubble rate (unit: %) of the measuring sample is calculated based on the following formula (1). The above operation is performed five times by changing the measuring sample, and the arithmetic mean (N=5) of the independent bubble rates in the five measuring samples is taken as the independent bubble rate (unit: %) of the foamed particles.
[0122] Closed cell ratio = (Vx-W / ρ) × 100 / (Va-W / ρ)…(1)
[0123] The symbols in the above formula (1) have the following meanings.
[0124] Vx: The true volume of the sample for measurement measured by the above method, that is, the sum of the volume of the resin constituting the foamed beads and the total volume of the cells of the closed cell portion in the foamed beads (unit: cm 3 )
[0125] Va: The apparent volume of the sample for measurement measured by the amount of liquid level rise when the sample for measurement is sunk into a graduated cylinder filled with ethanol (unit: cm 3 )
[0126] W: Mass of the sample to be measured (unit: g)
[0127] ρ: Density of the resin constituting the foamed particles (unit: g / cm 3 )
[0128] 〔Ash content of foamed particles〕
[0129] The ash content of the foamed beads is preferably 0.1% by mass or more and 4% by mass or less. In this case, the amount of components derived from post-consumer materials can be increased while ensuring good in-mold formability of the foamed beads, making it easier to utilize post-consumer materials.
[0130] From the viewpoint of more effectively utilizing the polypropylene resin composition derived from post-consumer materials, the ash content of the foamed beads is more preferably 0.2% by mass or more, and further preferably 0.5% by mass or more. On the other hand, from the viewpoint of more stably achieving good in-mold formability of the foamed beads, the ash content of the foamed beads is more preferably 3% by mass or less, and further preferably 2% by mass or less.
[0131] In addition, when forming the preferred range of the ash content of the foamed particles, the upper limit and lower limit of the ash content of the foamed particles mentioned above can be arbitrarily combined. For example, the preferred range of the ash content of the foamed particles can be 0.1 mass% to 3 mass%, 0.2 mass% to 3 mass%, or 0.5 mass% to 2 mass%.
[0132] The ash content of the expanded beads can be measured by the direct ash method (A method) of JIS K7250-1: 2006. More specifically, the ash content of the expanded beads can be calculated from the mass of the residue remaining after the expanded beads are burned.
[0133] 〔High temperature peak〕
[0134] The foamed particles preferably have a crystal structure as follows: in the DSC curve obtained when heated from 23°C to 230°C at a heating rate of 10°C / min, a melting peak caused by the inherent melting of the resin component contained in the foamed particles and one or more melting peaks located at a position closer to the high temperature side than the melting peak appear. Foamed particles with such a crystal structure have excellent in-mold formability. In addition, by in-mold molding of the foamed particles, a molded body with excellent compression properties can be obtained more easily. In addition, hereinafter, the melting peak caused by the inherent melting of the resin component appearing in the DSC curve is referred to as a "resin inherent peak", and the melting peak appearing at a higher temperature side than the resin inherent peak is referred to as a "high temperature peak". The resin inherent peak appears due to the melting of the crystals usually possessed by the resin component contained in the foamed particles. On the other hand, it is presumed that the high temperature peak appears due to the melting of secondary crystals formed in the resin component during the manufacturing process of the foamed particles. That is, when a high temperature peak appears in the DSC curve, it is presumed that secondary crystals are formed in the resin component.
[0135] Whether the foamed particles have the above-mentioned crystal structure can be determined based on the DSC curve obtained by differential scanning calorimetry (DSC) according to JIS K7122-1987 and the above-mentioned conditions. In addition, the flow rate of nitrogen in the measurement environment can be set to 30 mL per minute. In addition, when performing DSC, 1 to 3 mg of foamed particles can be used as a sample.
[0136] Specifically, in the DSC curve obtained when heating is performed from 23°C to 230°C at a heating rate of 10°C / min as described above (i.e., the first heating), both the resin-specific peak and the high-temperature peak of the resin component contained in the foamed particles appear. In contrast, in the DSC curve obtained when the first heating is performed, the particles are cooled from 230°C to 23°C at a cooling rate of 10°C / min, and then heated from 23°C to 230°C again at a heating rate of 10°C / min (i.e., the second heating), only the resin-specific peak of the resin component contained in the foamed particles is observed. Therefore, by comparing the DSC curve obtained in the first heating and the DSC curve obtained in the second heating, the resin-specific peak and the high-temperature peak can be distinguished.
[0137] From the viewpoint of further improving the in-mold formability and compression properties of the foamed beads, the peak temperature of the high temperature peak of the foamed beads is preferably 155° C. to 170° C., more preferably 160° C. to 170° C. From the same viewpoint, the heat of fusion of the high temperature peak is preferably 10 J / g to 45 J / g, more preferably 12 J / g to 35 J / g, and further preferably 15 J / g to 32 J / g.
[0138] In addition, the total melting heat of the foamed beads is preferably 60 J / g or more and 100 J / g or less, more preferably 65 J / g or more and 90 J / g or less, and further preferably 70 J / g or more and 85 J / g or less. In this case, the in-mold formability of the foamed beads can be more easily improved. In addition, by in-mold forming of the foamed beads, a molded body with excellent compression properties can be more easily obtained.
[0139] The peak temperature of the high temperature peak, the melting heat of the high temperature peak and the total melting heat are the values obtained as follows. First, 1 to 3 mg of foamed beads are used as a sample and a differential scanning calorimetry is performed under the condition of heating from 23°C to 230°C at a heating rate of 10°C / min to obtain a DSC curve. Figure 1 An example of a DSC curve is shown in FIG. 1 . In the case where the foamed particles have a high temperature peak, in the DSC curve, as shown in FIG. Figure 1 As shown, a resin-specific peak ΔH1 and a high-temperature peak ΔH2 having a peak on the high-temperature side of the peak of the resin-specific peak ΔH1 appear. The temperature corresponding to the peak of the high-temperature peak ΔH2 is defined as the peak temperature of the high-temperature peak.
[0140] Next, a straight line L1 is drawn, which connects point α corresponding to 80° C. on the DSC curve and point β corresponding to the melting end temperature T of the foamed beads. The melting end temperature T is the end point on the high temperature side of the high temperature peak ΔH2, that is, the intersection of the high temperature peak ΔH2 in the DSC curve and the baseline on the high temperature side of the high temperature peak ΔH2.
[0141] After drawing the straight line L1, draw a straight line L2, which passes through the maximum point γ between the resin-specific peak ΔH1 and the high-temperature peak ΔH2 and is parallel to the vertical axis of the graph. The resin-specific peak ΔH1 and the high-temperature peak ΔH2 are divided by the straight line L2. The melting heat of the high-temperature peak ΔH2 can be calculated based on the area of the portion of the DSC curve that constitutes the high-temperature peak ΔH2, the straight line L1, and the portion surrounded by the straight line L2. In addition, the total melting heat of the foamed particles can be calculated based on the area of the portion of the DSC curve that constitutes the resin-specific peak ΔH1, the portion that constitutes the high-temperature peak ΔH2, and the portion surrounded by the straight line L1. That is, the total melting heat of the foamed particles is the sum of the melting heat of the resin-specific peak ΔH1 and the melting heat of the high-temperature peak ΔH2.
[0142] Peak height ratio
[0143] Preferably, the foamed particles have the following crystal structure: in a DSC curve obtained when the foamed particles are heated from 23° C. to 200° C. at a heating rate of 10° C. / min, a first endothermic peak Pa having the largest peak area and a second endothermic peak Pb adjacent to the first endothermic peak Pa on the high temperature side of the first endothermic peak Pa appear;
[0144] The temperature Tb of the top of the second endothermic peak Pb is 158° C. or higher,
[0145] The difference Tb-Ta between the temperature Tb of the top of the second endothermic peak Pb and the temperature Ta of the top of the first endothermic peak Pa is 15° C. or more and 30° C. or less,
[0146] A ratio hb / ha of a peak height hb of the second endothermic peak Pb to a peak height ha of the first endothermic peak Pa is 1.2 or more and 2.8 or less.
[0147] The expanded beads having such DSC characteristics have good in-mold moldability and are excellent in the balance of rigidity with respect to molding pressure. The reasons for this are as follows, for example.
[0148] Since the temperature Tb of the top of the second endothermic peak Pb is within the specific range, the foamed beads have excellent heat resistance, so it is possible to suppress the damage of the bubbles of the foamed beads during the molding heating. In addition, by in-mold molding of the foamed beads, the heat resistance of the molded body can be further improved. From the viewpoint of further improving these effects, the temperature Tb of the top of the second endothermic peak Pb is preferably 160°C or more, and more preferably 162°C or more. From the viewpoint of further improving the in-mold moldability of the foamed beads, the temperature Tb of the top of the second endothermic peak Pb is preferably 175°C or less.
[0149] As a method for controlling the temperature Tb of the top of the second endothermic peak Pb within the specific range, for example, there can be cited a method of using a polypropylene-based resin having a relatively high melting point as a raw material, etc. In particular, by adding a polypropylene-based resin composition containing the ethylene-propylene-based rubber and having a relatively high melting point to the resin composition constituting the foamed layer, the temperature Tb of the top of the second endothermic peak Pb can be more easily controlled within the specific range.
[0150] In addition, conventionally, the temperature Tb of the top of the second endothermic peak Pb of the foamed beads made of the polypropylene resin composition containing the ethylene-propylene rubber is high, and the difference Tb-Ta between the top temperatures is easily small, so there is a tendency for the in-mold moldability to be poor. In contrast, the in-mold moldability of the foamed beads can be improved by making the difference Tb-Ta between the top temperature Tb of the second endothermic peak Pb and the top temperature Ta of the first endothermic peak Pa within the specific range.
[0151] As a reason for this, for example, the following reason can be considered: by setting the vertex temperature difference Tb-Ta to the specific range, even when in-mold molding is performed at a relatively low molding pressure, it is possible to fully melt the crystals that are relatively easy to melt (i.e., crystals that produce the second endothermic peak Pb when melted) while maintaining the crystals that are relatively difficult to melt in the foamed particles (i.e., crystals that produce the second endothermic peak Pa when melted), thereby appropriately softening the foamed particles.
[0152] From the viewpoint of more reliably improving the in-mold formability of the foamed beads, the difference in vertex temperature Tb-Ta is preferably 18°C or more, more preferably 20°C or more. On the other hand, when the difference in vertex temperature Tb-Ta is too large, there is a risk that the foamed beads are easily contracted. From the viewpoint of further suppressing the contraction of the foamed beads, the difference in vertex temperature Tb-Ta is preferably 28°C or less, more preferably 26°C or less.
[0153] When forming the preferred range of the vertex temperature difference Tb-Ta, the upper and lower limits of the vertex temperature difference Tb-Ta described above can be arbitrarily combined. For example, the vertex temperature difference Tb-Ta can be 18°C to 28°C, or 20°C to 26°C.
[0154] As a method for controlling the difference in vertex temperature Tb-Ta within the specific range, for example, as the resin composition constituting the foaming layer, there can be cited a method of using a molten mixture of a polypropylene resin composition with a relatively high melting point containing the ethylene-propylene rubber and a propylene random copolymer with a relatively low melting point.
[0155] Furthermore, by setting the peak height ratio hb / ha of the foamed beads within the specific range, the in-mold moldability is improved, and the balance of rigidity with respect to the molding pressure is improved, so that a molded body having rigidity commensurate with the molding pressure can be easily obtained.
[0156] The foamed particles have a DSC characteristic with a peak height ratio hb / ha in the specific range, so that the balance of rigidity with respect to molding pressure is good even when the foamed particles contain ethylene propylene rubber. The reason why the balance of rigidity with respect to molding pressure is improved by making the peak height ratio hb / ha of the foamed particles in the specific range is not clear at present, but the following reasons may be considered, for example.
[0157] The peak height ratio hb / ha is considered to be related to the existence state and amount of high-rigidity crystals (i.e., crystals that generate the second endothermic peak Pb when melted) having the same crystal structure, and it is considered that when the peak height ratio hb / ha is high, it is considered that the high-rigidity crystals described above exist in a state with few structural defects. In addition, it is considered that such high-rigidity crystals affect the thermal processability of the foamed beads.
[0158] Therefore, it is believed that by setting the peak height ratio hb / ha to the specific range, the balance between the amount of crystals with high rigidity and relatively difficult to melt and the amount of crystals that are relatively easy to melt in the foamed beads can be formed into an appropriate range, and the distribution of the melting temperature of crystals that are relatively easy to melt can be appropriately widened. As a result, it is believed that the bubbles of the foamed beads are less likely to be damaged during in-mold molding.
[0159] From the viewpoint of more reliably improving the recovery of the molded body, the peak height ratio hb / ha is preferably 1.3 or more, more preferably 1.4 or more, and further preferably 1.5 or more. In addition, from the viewpoint of further improving the balance of rigidity relative to the molding pressure, the peak height ratio hb / ha is preferably 2.6 or less, and more preferably 2.4 or less.
[0160] When forming the preferred range of the peak height ratio hb / ha, the upper and lower limits of the peak height ratio hb / ha described above may be arbitrarily combined. For example, the peak height ratio hb / ha may be 1.3 or more and 2.6 or less, 1.4 or more and 2.6 or less, or 1.5 or more and 2.4 or less.
[0161] Examples of methods for controlling the peak height ratio hb / ha within the specific range include a method in which the molten mixture is used as the resin composition constituting the foamed layer, and the ratio of the amount of the polypropylene resin composition having a relatively high melting point and containing the ethylene-propylene rubber to the amount of the propylene random copolymer having a relatively low melting point in the molten mixture is adjusted within the range described below; a method in which the bending modulus of the random copolymer is adjusted within the range described below; a method in which the retention time in the step of forming the second endothermic peak Pb in the production process of the foamed beads is adjusted; a method in which the foaming temperature is adjusted in the production process of the foamed beads; and the like.
[0162] The peak height of each endothermic peak is the distance between the interpolated base line and the peak apex perpendicular to the horizontal axis. Specifically, the peak height of the endothermic peak is a value obtained as follows.
[0163] First, a DSC curve is obtained by the following method to determine the first endothermic peak Pa and the second endothermic peak Pb. Specifically, 1 to 3 mg of the state-conditioned foamed beads are used as a sample and subjected to differential scanning calorimetry under the conditions of heating from 23°C to 230°C at a heating rate of 10°C / min, thereby obtaining a DSC curve. At least two endothermic peaks appear in the DSC curve of the foamed beads.
[0164] Then, if Figure 2 As shown, a straight line L1 is drawn, and the straight line L1 connects point α corresponding to 80° C. on the DSC curve and point β corresponding to the melting end temperature T of the foamed beads. The melting end temperature T is the end point on the high temperature side of the endothermic peak with the highest temperature at the top, that is, the intersection of the endothermic peak with the highest temperature at the top in the DSC curve and the baseline on the high temperature side of the endothermic peak.
[0165] After the straight line L1 is drawn, a straight line L2 is drawn, which passes through the maximum point γ existing between adjacent endothermic peaks and is parallel to the vertical axis of the graph. The adjacent endothermic peaks are divided into individual endothermic peaks by the straight line L2. And the area of the portion surrounded by the portion constituting each endothermic peak in the DSC curve, the straight line L1, and the straight line L2 is set as the peak area of the endothermic peak, the endothermic peak with the largest peak area among the multiple endothermic peaks is set as the first endothermic peak Pa, and the endothermic peak adjacent to the first endothermic peak Pa on the high temperature side of the first endothermic peak Pa is set as the second endothermic peak Pb.
[0166] Next, a line segment parallel to the vertical axis of the graph is drawn from the vertex of each endothermic peak on the DSC curve to the straight line L1, and the length of the line segment is taken as the peak height of each endothermic peak. That is, the peak height ha of the first endothermic peak Pa is the length of the line segment L3 drawn from the vertex of the first endothermic peak Pa to the straight line L1 and parallel to the vertical axis of the graph. In addition, the peak height hb of the second endothermic peak Pb is the length of the line segment L4 drawn from the vertex of the second endothermic peak Pb to the straight line L1 and parallel to the vertical axis of the graph.
[0167] In addition, in the DSC curve, as endothermic peaks, only two endothermic peaks, namely the first endothermic peak Pa and the second endothermic peak Pb, may appear, or other endothermic peaks may appear in addition to the first endothermic peak Pa and the second endothermic peak Pb. In addition, the first endothermic peak Pa may be, for example, the above-mentioned resin-specific peak, and the second endothermic peak Pb may be, for example, the above-mentioned high temperature peak.
[0168] The full width at half maximum of the first endothermic peak Pa is preferably 15°C or more and less than 25°C. In this case, the balance of rigidity with respect to the molding pressure can be further improved, and a molded body having rigidity commensurate with the molding pressure can be more easily obtained. In particular, a molded body having rigidity expected according to the minimum molding pressure can be more easily obtained. In addition, the in-mold moldability of the foamed particles in the case of in-mold molding at a lower molding pressure can be further improved. From the viewpoint of more reliably obtaining these effects, it is more preferable that the full width at half maximum of the first endothermic peak Pa is 18°C or more and less than 25°C.
[0169] The full width at half maximum wa of the first endothermic peak Pa is obtained as follows. First, a line segment L3 parallel to the vertical axis of the graph is drawn from the vertex of the first endothermic peak Pa to the straight line L1 by the above method. Figure 2 As shown in FIG. 1 , a straight line L5 is drawn which passes through the midpoint of the line segment L3 and is parallel to the straight line L1. Then, two intersection points of the straight line L5 and the first endothermic peak Pa are determined. The difference between the temperature corresponding to the intersection point on the high temperature side and the temperature corresponding to the intersection point on the low temperature side at the two intersection points thus obtained is set as the half maximum full width wa of the first endothermic peak Pa.
[0170] In addition, depending on the shape of the DSC curve, the straight line L5 may not intersect with the portion on the high temperature side of the top of the first endothermic peak Pa. In this case, the intersection of the straight line L5 and the straight line parallel to the vertical axis passing through the melting end temperature of the first endothermic peak Pa is determined, and the difference between the temperature corresponding to the intersection and the temperature corresponding to the intersection on the low temperature side is defined as the half maximum width wa of the first endothermic peak Pa. In addition, the melting end temperature of the first endothermic peak Pa when determining the half maximum width wa of the first endothermic peak Pa refers to the temperature corresponding to the intersection of the tangent drawn from the point where the gradient becomes the maximum in the curve on the high temperature side of the first endothermic peak Pa and the straight line L1.
[0171] From the viewpoint of more reliably obtaining the above-mentioned effect, it is more preferred that the foamed beads have a crystal structure in which, in a DSC curve obtained when the foamed beads are heated from 23° C. to 200° C. at a heating rate of 10° C. / min, a first endothermic peak Pa having the largest peak area and a second endothermic peak Pb adjacent to the first endothermic peak Pa on the high temperature side of the first endothermic peak Pa appear,
[0172] The independent bubble rate of the foamed particles is more than 85%,
[0173] The temperature Tb of the top of the second endothermic peak Pb is 158° C. or higher,
[0174] The difference Tb-Ta between the temperature Tb of the top of the second endothermic peak Pb and the temperature Ta of the top of the first endothermic peak Pa is 15° C. or more and 30° C. or less,
[0175] A ratio hb / ha of a peak height hb of the second endothermic peak Pb to a peak height ha of the first endothermic peak Pa is 1.2 or more and 2.8 or less.
[0176] By using such expanded beads for in-mold molding, even when the resin composition constituting the expanded layer of the expanded beads contains ethylene propylene rubber, the in-mold moldability is good, and a molded body having a good balance of rigidity with respect to the in-mold molding pressure can be easily obtained.
[0177] 〔Melting end temperature of foamed particles〕
[0178] Preferably, the foamed particles are heated from 23°C to 200°C at a heating rate of 10°C / min, then cooled to 23°C at a cooling rate of 10°C / min, and heated again from 23°C to 200°C at a heating rate of 10°C / min, and the melting end temperature in the second DSC curve obtained is 160°C or above. The melting end temperature in the second DSC curve is related to the melting point of the resin component contained in the foamed particles. In the case of containing a resin component with a high melting point, there is a tendency for the melting end temperature in the second DSC curve to become higher. Therefore, the foamed particles whose melting end temperature in the second DSC curve is 160°C or above can more reliably improve the heat resistance. In addition, the upper limit of the melting end temperature in the second DSC curve of the foamed particles is not particularly limited, and is approximately 175°C.
[0179] The method for determining the melting end temperature of the foamed particles is as follows. First, a heat flux differential scanning calorimeter is used to heat the foamed particles from 23°C to 200°C at a heating rate of 10°C / min. Thereafter, the foamed particles are cooled from 200°C to 23°C at a cooling rate of 10°C / min. After the cooling is completed, the foamed particles are heated again from 23°C to 200°C at a heating rate of 10°C / min (i.e., the second heating), and a DSC curve is obtained. Then, the end point on the high temperature side of the melting peak that appears in the DSC curve in the second heating, that is, the temperature of the intersection of the melting peak in the second DSC curve and the baseline on the high temperature side of the melting peak is taken as the melting end temperature.
[0180] (Method for producing polypropylene resin foamed particles)
[0181] The foamed particles can be obtained by foaming polypropylene resin particles having a core layer. The foamed particles are preferably produced by the following production method.
[0182] That is, when producing the polypropylene resin foamed particles, the polypropylene resin foamed particles having a core layer are foamed to obtain the polypropylene resin foamed particles having a foamed layer.
[0183] The core layer of the resin pellets used in the production method is composed of a molten mixture of a polypropylene resin composition I containing an ethylene-propylene rubber and having a melting point of 160° C. or higher and a polypropylene resin B having a melting point of 125° C. or higher and less than 160° C.,
[0184] The mass ratio of the polypropylene resin composition I to the polypropylene resin B in the core layer is polypropylene resin composition I:polypropylene resin B=2:98 to 70:30. By foaming the resin particles having the core layer, the foamed particles can be obtained more easily.
[0185] 〔Production of resin pellets〕
[0186] In the manufacturing method, first, resin particles having the core layer are prepared. When forming the core layer, it is preferred to use an impact-resistant polypropylene containing ethylene-propylene rubber and having a melting point of 160° C. or more as the polypropylene resin composition I. In addition, as described later, the core layer can be formed by melt-mixing the polypropylene resin composition I and the polypropylene resin B. The core layer becomes a foaming layer of the foamed particles after foaming. Therefore, the composition of the molten mixture constituting the core layer can appropriately refer to the composition of the resin composition constituting the foaming layer of the foamed particles described above.
[0187] Polypropylene resin composition I
[0188] As the polypropylene resin composition I (hereinafter also referred to as resin composition I) used in the preparation of the resin particles, for example, the resin composition A and impact polypropylene constituting the foaming layer of the above-mentioned foamed particles can be used. Therefore, regarding the constitution of the resin composition A and impact polypropylene used as the resin composition I, the constitution related to the resin composition A and impact polypropylene used in the above-mentioned foaming layer can be appropriately referred to.
[0189] When the polypropylene resin foamed particles are prepared using the resin composition A as the resin composition I, the melting point Tm I , melt mass flow rate MFR I , flexural modulus M I Heat of fusion H I The preferred ranges of the physical property values in the resin composition I shown below are respectively related to the melting point Tm A , melt mass flow rate MFR A , flexural modulus M A Heat of fusion H A Therefore, when the polypropylene resin foamed beads are prepared using the resin composition A as the resin composition I, the preferred ranges of the corresponding physical property values in the resin composition A contained in the foamed beads can be the same as the preferred ranges of the corresponding physical property values in the resin composition I.
[0190] Similarly, when using impact-resistant polypropylene as the resin composition I to produce polypropylene resin foamed particles, the melting point Tm I , melt mass flow rate MFR I , flexural modulus M I Heat of fusion H I The preferred ranges of the physical property values in the resin composition I shown below are respectively the same as the preferred ranges of the corresponding physical property values in the impact-resistant polypropylene. Therefore, when the impact-resistant polypropylene is used as the resin composition I to produce the polypropylene resin foamed beads, the preferred ranges of the corresponding physical property values in the resin composition I can be adopted as the preferred ranges of the physical property values in the impact-resistant polypropylene contained in the foamed beads.
[0191] Melting point Tm of resin composition I I It is preferably 150°C or more, more preferably 160°C or more, further preferably 161°C or more, and particularly preferably 162°C or more. In this case, when compressive strain is applied to the molded body, the compressive stress at a relatively small amount of compressive strain tends to be high. In addition, the change in stress associated with the increase in compressive strain can be more easily reduced. From the viewpoint of further improving the in-mold moldability of the foamed particles and further expanding the range of molding pressures that can obtain good molded bodies, the melting point Tm of the resin composition I ... and further preferably 161°C or more. In this case, the melting point Tm of the resin composition I is preferably 150°C or more, more preferably 160°C or more, and particularly preferably 162°C or more. In this case, the melting point Tm of the resin composition I is preferably 150°C or more, more preferably 160°C or more,I It is preferably 170°C or lower, more preferably 168°C or lower, and further preferably 165°C or lower.
[0192] In the melting point Tm I The above melting point Tm can be arbitrarily combined when the preferred range is I For example, the melting point Tm I The preferred range of Tm is 150°C or more and 170°C or less. In this case, in addition to the above-mentioned effects, the foaming property of the foamed particles can be further improved. I The preferred range of may be 160°C to 170°C, 161°C to 168°C, or 162°C to 165°C.
[0193] Melting point Tm of resin composition I I The method for measuring the melting point Tm of the foamed beads is the same as the method for measuring the melting point Tm of the foamed beads described above, except that a test piece composed of the resin composition I is used instead of the foamed beads.
[0194] Flexural modulus M of resin composition I I It is preferably 800 MPa to 1600 MPa, more preferably 800 MPa to 1400 MPa, further preferably 800 MPa to 1300 MPa, particularly preferably 800 MPa to 1200 MPa, and most preferably 900 MPa to 1200 MPa. In this case, the moldability of the foamed particles can be more easily improved. Flexural modulus M I It can be determined based on JIS K7171:2008.
[0195] MFR of the resin composition I measured under the conditions of a temperature of 230°C and a load of 2.16 kg I It is preferably 3 g / 10 minutes or more, more preferably 10 g / 10 minutes or more, further preferably 14 g / 10 minutes or more, and particularly preferably 20 g / 10 minutes or more. In addition, the melt mass flow rate MFR measured under the conditions of temperature 230°C and load 2.16 kg is I It is preferably 40 g / 10 minutes or less, more preferably 35 g / 10 minutes or less, and still more preferably 30 g / 10 minutes or less. In this case, the moldability of the foamed beads can be further improved, and the range of molding pressures for obtaining a good molded body can be further expanded.
[0196] In the composition of melt mass flow rate MFR I The above melt mass flow rate MFR can be arbitrarily combined when the preferred range isI For example, MFR I The preferred range may be 3 g / 10 minutes to 40 g / 10 minutes, 10 g / 10 minutes to 40 g / 10 minutes, 14 g / 10 minutes to 35 g / 10 minutes, or 20 g / 10 minutes to 30 g / 10 minutes.
[0197] The MFR of the above resin composition I is I This is a value measured under the conditions of a test temperature of 230°C and a load of 2.16 kg based on JIS K7210-1:2014.
[0198] The ash content of the resin composition I is preferably 1% by mass or more and 25% by mass or less. In this case, even when the melt mass flow rate of the resin composition I is relatively high, the in-mold formability of the foamed particles can be further improved, and the range of the molding pressure at which a good molded body can be obtained can be further expanded.
[0199] By using the resin combination I of ash content in the described specific range, the bubble diameter of expanded particles can be made smaller, and the bubble film is thinned. In addition, it is believed that such expanded particles are easily softened due to heating, and on the other hand, resin is not easy for excessive elongation. Therefore, it is believed that by using the resin combination I of ash content in the described specific range, even in the case of carrying out in-mold forming with high forming pressure, the shrinkage of formed body is also easily suppressed.
[0200] The ash content of the resin composition I is more preferably 2% by mass or more, and further preferably 3% by mass or more. In this case, for example, a polypropylene resin composition having a relatively high ash content such as the resin composition a1 derived from ASR can be more easily blended, and the resin component derived from post-consumer materials can be more effectively utilized.
[0201] In addition, from the viewpoint of further improving the in-mold formability of the foamed beads, the ash content of the resin composition I is more preferably 20 mass % or less, further preferably 15 mass % or less, further preferably 10 mass % or less, particularly preferably 8 mass % or less, and most preferably 6 mass % or less.
[0202] The upper limit and lower limit of the ash content described above may be arbitrarily combined when constituting the preferred range of the ash content of the resin composition I. For example, the preferred range of the ash content of the resin composition I may be 1% by mass or more and 20% by mass or less, 2% by mass or more and 15% by mass or less, 2% by mass or more and 10% by mass or less, 3% by mass or more and 8% by mass or less, or 3% by mass or more and 6% by mass or less.
[0203] The ash content of the resin composition I can be measured according to the direct ash method (A method) of JIS K7250-1: 2006. More specifically, the ash content can be calculated based on the mass of the residue remaining after burning the resin composition I. In addition, the ash contained in the combustion residue of the resin composition I is mainly derived from the inorganic components contained in the resin composition I such as the inorganic filler.
[0204] The resin composition I preferably shows a morphology in which a polypropylene resin is a matrix (i.e., a continuous phase) and a rubber-like body containing ethylene-propylene rubber is a microdomain (i.e., a dispersed phase). In addition, the resin composition I more preferably shows a morphology in which a homopolypropylene as a polypropylene resin is a matrix and a rubber-like body containing ethylene-propylene rubber is a microdomain.
[0205] By including the resin composition I in the foaming layer, foamed particles with good in-mold formability can be obtained more stably. In addition, by using the foamed particles for in-mold forming, a molded body with good mechanical properties such as compressive strength can be more easily obtained. From the same point of view, the melting point of the polypropylene resin constituting the matrix in the resin composition I is more preferably above 160°C. In addition, in the micro-domain of the rubber-like body in the resin composition I, in addition to the ethylene-propylene rubber, a polyethylene resin may also be included.
[0206] The observation method of the morphology of the resin composition I is as follows. First, an observation sample is cut out from the resin composition I. The cutting method of the observation sample is not particularly limited. For example, in the case of a cylindrical pellet in the shape of the resin composition I, the pellet can be cut vertically relative to the height direction of the pellet in a manner passing through the center of the pellet. In this way, an observation sample with a cross section exposed in the center of the pellet composed of the resin composition I can be obtained. Next, the observation sample is embedded in an epoxy resin, and after electron staining with ruthenium tetroxide, a supermicrotome is used to make a slice from the sample. The slice is mounted on a microgrid of a transmission electron microscope (for example, "JEM-1040Flash" manufactured by Japan Electronics Co., Ltd.), observed at a predetermined magnification (for example, 5000 times), and a cross-sectional photo (that is, TEM photo) of the resin composition A is taken. From the cross-sectional photo, the morphology of the phase of the polypropylene resin in the resin composition A and the phase of the rubber-like body containing ethylene propylene rubber is visually observed.
[0207] From the viewpoint of being able to stably improve the in-mold formability of the foamed particles, the average diameter of the rubber-like body containing ethylene-propylene rubber in the resin composition I is preferably 0.5 μm or more and 5 μm or less, more preferably 0.8 μm or more and 3 μm or less, and further preferably 1 μm or more and 2 μm or less. The average diameter of the rubber-like body in the resin composition I is calculated based on the TEM photo. Specifically, the longest diameter and the shortest diameter of more than 50 micro-regions randomly selected from the micro-regions (i.e., the phase of the rubber-like body) appearing in the TEM photo are measured respectively, and their arithmetic average is calculated. The arithmetic mean of the longest diameter and the shortest diameter obtained in this way is used as the average diameter of the rubber-like body containing ethylene-propylene rubber.
[0208] The acetone insoluble components contained in the n-decane extract of the resin composition I (i.e., D sol -A insol ) is preferably 0.05 g or more and 0.30 g or less, more preferably 0.06 g or more and 0.25 g or less, and further preferably 0.08 g or more and 0.20 g or less per 1 g of the resin composition I. In this case, the foamed particles can be obtained more easily. sol -A insol The main component is derived from ethylene propylene rubber. sol -A insol The method for determining the amount of D is to use resin composition I instead of foamed particles and calculate D per 1g of resin composition I. sol -A insol In addition, the amount of D in the above-mentioned foamed particles sol -A insol The method for determining the amount is the same.
[0209] The resin composition I may contain resins other than polypropylene resins and elastomers other than ethylene propylene rubbers, etc., within the range that the above-mentioned effects are not impaired. Examples of the resin that may be contained in the resin composition I include polystyrene resins, polyethylene resins, and acrylonitrile-butadiene-styrene resins, and examples of the elastomer include ethylene butene rubbers and ethylene octene rubbers. In addition, these resins and elastomers may be resins and elastomers derived from post-consumer materials.
[0210] In the range of not damaging the above-mentioned effect, the resin combination I can include inorganic substances such as talcum, silicon dioxide, glass fiber. The main component of the inorganic substance included in the resin combination I is preferably talcum. In this case, even when using the resin combination I with a relatively high melting point, the weldability of the foamed particles can be further improved. As a result, the mold-forming property of the foamed particles can be further improved. As its reason, it can be considered that the average bubble diameter of the foamed particles is easily reduced.
[0211] In the range of not damaging the above-mentioned effect, the resin combination I can include additives such as bubble adjuster, crystal nucleating agent, flame retardant, flame retardant aid, plasticizer, antistatic agent, antioxidant, ultraviolet absorber, light stabilizer, antibacterial agent, colorant. In addition, resin combination I preferably includes carbon black as colorant. In this case, for example, the content of the carbon black in resin combination A can be more than 0.1 mass % and less than 2 mass %, or more than 0.2 mass % and less than 1 mass %. By making the content of the carbon black in resin combination I be in the specific range, it is possible to obtain a molded body having excellent design properties of a speckled pattern formed by relatively shallow black (gray) and white.
[0212] Polypropylene resin B
[0213] The polypropylene resin B (hereinafter also referred to as resin B) used in the preparation of the resin particles may be a polypropylene resin that has not been subjected to a thermal process such as molding for forming a molded article (i.e., a non-recycled polypropylene resin), or a polypropylene resin that has been subjected to an overheating process (more specifically, a recycled polypropylene resin after material recycling). From the viewpoint of being able to more stably improve the in-mold moldability of the foamed particles, the resin B is preferably a non-recycled polypropylene resin.
[0214] Melting point Tm of resin B B It is preferably 125° C. or higher and lower than 160° C., more preferably 130° C. or higher and lower than 160° C., further preferably 135° C. or higher and lower than 158° C., particularly preferably 140° C. or higher and lower than 156° C., and most particularly preferably 142° C. or higher and lower than 155° C. In this case, the foamability in the production process of the foamed beads can be further improved, and the in-mold formability of the foamed beads can be further improved.
[0215] Melting point Tm of resin B BThe method for measuring the melting point Tm of the foamed beads is the same as the method for measuring the melting point Tm of the foamed beads described above, except that a test piece composed of resin B is used instead of the foamed beads. In addition, when two or more polypropylene resins are used as resin B in the manufacture of the foamed beads, the plurality of polypropylene resins are melt-mixed in a manner to obtain the same mixing ratio as in the manufacture of the foamed beads, and a test piece composed of the molten mixture of these polypropylene resins can be used.
[0216] Flexural modulus of resin B M B Preferably, it is 800 MPa or more, more preferably 850 MPa or more, and further preferably 900 MPa or more. In this case, the moldability of the foamed particles can be more easily improved, and the balance of rigidity with respect to the molding pressure can be more easily improved. In addition, from the viewpoint of more easily improving the moldability of the foamed particles and further expanding the moldable range, the bending elastic modulus M of the resin B is B It is preferably 1500 MPa or less, more preferably 1400 MPa or less, further preferably 1350 MPa or less, and particularly preferably 1300 MPa or less.
[0217] The bending elastic modulus M of the constituent resin B B When the preferred range is set to B For example, the bending elastic modulus M of resin B is B The preferred range may be 800 MPa to 1500 MPa, 800 MPa to 1400 MPa, 850 MPa to 1350 MPa, 900 MPa to 1500 MPa, 900 MPa to 1400 MPa, or 900 MPa to 1300 MPa.
[0218] In addition, the bending modulus M of resin B B It can be obtained based on JIS K7171: 2008. When two or more polypropylene resins are used as resin B in the production of foamed beads, the plurality of polypropylene resins are melt-mixed in a manner to have the same mixing ratio as in the production process of the foamed beads, and the bending elastic modulus of a test piece composed of the melt mixture of these polypropylene resins is set as the bending elastic modulus M of resin B. B .
[0219] The ash content of resin B is preferably less than 1% by mass, more preferably less than 0.5% by mass. In this case, during the production process of the foamed beads, the moldability of the foamed beads can be further improved while maintaining good foamability, further expanding the range of molding pressures for obtaining good molded bodies.
[0220] The ash content of B can be measured according to the direct ash method (A method) of JIS K7250-1: 2006. More specifically, the ash content of resin B can be calculated from the mass of the residue remaining after burning resin B.
[0221] The melt mass flow rate MFR of resin B measured under the conditions of temperature 230°C and load 2.16 kg is B Preferably, it is 3 g / 10 minutes or more and 10 g / 10 minutes or less, and more preferably 6 g / 10 minutes or more and 9 g / 10 minutes or less. In this case, the moldability of the foamed particles can be more stably improved. In addition, when two or more polypropylene resins are used as the resin B, the melt mass flow rate of the sample obtained by melt-mixing these polypropylene resins at the same ratio as the mixing ratio in the manufacturing process of the foamed particles is set as the melt mass flow rate MFR of the resin B. B .
[0222] Heat of fusion of resin B B Preferably, the heat of fusion H of the polypropylene resin B is 50 J / g or more and 100 J / g or less. In this case, the moldability of the foamed particles can be improved more stably. B It is more preferably 60 J / g or more and 98 J / g or less, and further preferably 65 J / g or more and 96 J / g or less. In addition, when two or more polypropylene resins are used as the resin B, the melting heat of a sample obtained by melt-mixing these polypropylene resins at the same mass ratio as that in the production of the resin pellets is set as the melting heat H of the resin B. B .
[0223] Heat of fusion of resin B BIt can be obtained based on the DSC curve obtained by performing differential scanning calorimetry (DSC) in accordance with JIS K 7122-1987. Specifically, first, resin B is used as a test piece, and the state of the test piece is conditioned based on "(2) After a certain heat treatment, the melting temperature is measured" in "3. Conditioning of the test piece" in JIS K 7122-1987. The heating rate and cooling rate in the state conditioning are both 10°C / min, and the temperature range is 23°C to 230°C. Thereafter, the state-conditioned test piece is heated again from 23°C to 230°C at a rate of 10°C / min, thereby obtaining a DSC curve (DSC curve during the second heating). In addition, the flow rate of nitrogen in the measurement environment is set to 30 mL per minute. In the DSC curve, a straight line is drawn connecting the point equivalent to 80°C and the end point on the high temperature side of the melting peak with the highest vertex temperature. Heat of fusion H of resin B B It can be calculated based on the area of the region surrounded by the straight line determined in this way and the melting peak of the DSC curve.
[0224] Resin B is preferably a propylene-based copolymer comprising more than 70% by mass of a structural unit from propylene, more preferably a propylene-based copolymer comprising more than 80% by mass of a structural unit from propylene. By using this resin B, it is possible to more easily obtain foamed particles with excellent moldability in the mold. In addition, two or more propylene-based copolymers may be included in the resin B.
[0225] From the same viewpoint, the resin B is preferably a copolymer of propylene and ethylene and / or an α-olefin having at least 4 carbon atoms. In addition, the copolymer is more preferably a random copolymer (ie, a propylene-based random copolymer).
[0226] Examples of the α-olefin used in the propylene copolymer include 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-butene, etc. The total content of the structural unit derived from ethylene and the content of the structural unit derived from the α-olefin having 4 or more carbon atoms in the propylene copolymer (i.e., the content of the comonomer component) is preferably 1% by mass or more and 15% by mass or less, and more preferably 2% by mass or more and 12% by mass or less.
[0227] In addition, when two or more polypropylene resins are used as the resin B, the ratio of the mass of the comonomer component to the total mass of these polypropylene resins (that is, the total mass of the resin B) is used as the content of the comonomer component. That is, the content of the comonomer component when two or more polypropylene resins are used as the resin B is the total content of the structural unit derived from ethylene and the content of the structural unit derived from α-olefin having 4 or more carbon atoms in a sample obtained by melt-mixing a plurality of polypropylene resins at the same ratio as the mixing ratio in the production process of the foamed beads.
[0228] The main component of resin B is preferably a copolymer of propylene and ethylene and / or butene, more preferably a propylene copolymer b1 containing a structural unit derived from ethylene (i.e., an ethylene component) as a copolymer component and / or a propylene copolymer b2 containing a structural unit derived from ethylene and 1-butene (i.e., an ethylene component and a butene component) as a copolymer component. In this case, the moldability of the foamed particles can be more reliably improved.
[0229] Examples of the propylene-based copolymer b1 (hereinafter referred to as "copolymer b1") include propylene-ethylene random copolymers, etc. In addition, examples of the propylene-based copolymer b2 (hereinafter referred to as "copolymer b2") include propylene-ethylene-butene random copolymers, etc. The total ratio of the copolymer b1 to the total mass of the resin B contained in the foamed particles and the ratio of the copolymer b2 are preferably 60% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.
[0230] When resin B contains copolymer b1 as a main component, the content of ethylene component in copolymer b1 is preferably 1 mass % or more, more preferably 2 mass % or more. In this case, the in-mold moldability of the foamed beads can be further improved when in-mold molding is performed at a lower molding pressure.
[0231] The content of ethylene components in the copolymer b1 is preferably 6% by mass or less, more preferably 5% by mass or less, further preferably 4% by mass or less, and particularly preferably 3% by mass or less. In this case, a molded body having good compressive strength and the like can be obtained more easily.
[0232] When resin B comprises copolymer b2 as main component, the total of the content of the ethylene component in copolymer b2 and the content of the butene component is preferably more than 2 mass %, more preferably more than 4 mass %, further preferably more than 6 mass %. In this case, the mold-in-mold formability of the foamed beads under the situation of mold-in-mold forming can be further improved with lower forming pressure.
[0233] The total content of the ethylene component and the butene component in the copolymer b2 is preferably 15% by mass or less, more preferably 12% by mass or less. In this case, a molded body having good compressive strength and the like can be obtained more easily.
[0234] In addition, from the viewpoint of being able to mold at a relatively low molding pressure and being able to more easily obtain a molded body with good compressive strength, etc., the ratio of the content of the butene component in copolymer b2 to the content of the ethylene component is preferably greater than 7 and less than 25, more preferably greater than 8 and less than 20, and further preferably greater than 10 and less than 18.
[0235] The contents of the component derived from ethylene and the component derived from butene in the resin B can be determined based on, for example, IR spectrum. The method for measuring the contents of the component derived from ethylene and the component derived from butene in the resin B is described in detail in Examples.
[0236] In the preferred range of the content of the comonomer component constituting the resin B, etc., the above-mentioned upper limit value and lower limit value may be arbitrarily combined.
[0237] Without impairing the above-mentioned effects, the resin B may contain additives such as bubble regulators, crystal nucleating agents, flame retardants, flame retardant aids, plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, light stabilizers, antibacterial agents, colorants, etc.
[0238] Mix ratio
[0239] The mixing ratio of the resin composition I and the resin B in the core layer (wherein the total mass of the resin composition I and the mass of the resin B is set to 100 mass%) is preferably resin composition I: resin B = 2: 98 to 70: 30. That is, the mass ratio of the resin composition I to the total mass of the resin composition I and the resin B mixed in the core layer is preferably 2 mass% or more and 70 mass% or less.
[0240] When resin composition A is used as resin composition I contained in the core layer, by setting the mass ratio of resin composition A to 2 mass % or more, the amount of resin composition A derived from recycled materials such as post-consumer materials that can be incorporated into the resin particles can be increased, thereby more effectively and flexibly utilizing the resin components derived from recycled materials.
[0241] From the viewpoint of further improving the impact absorption performance of the molded body, the mass ratio of the resin composition I to the total of the resin composition I and the resin B is preferably 3% by mass or more, more preferably 5% by mass or more, further preferably 8% by mass or more, and particularly preferably 10% by mass or more. In this case, it is easy to increase the compressive stress under a relatively small amount of compressive strain when compressive strain is applied to the molded body. In addition, in this case, the rate of increase of the compressive stress associated with the increase in strain can be further reduced, and the impact absorption performance of the molded body can be further improved.
[0242] In addition, by setting the mass ratio of the resin composition I to 70% by mass or less, the in-mold formability of the foamed beads can be more easily improved. From the viewpoint of being able to more stably improve the in-mold formability of the foamed beads, the mass ratio of the resin composition I to the total of the resin composition I and the resin B is preferably 65% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, particularly preferably 45% by mass or less, and most preferably 40% by mass or less.
[0243] When forming the preferred range of the mass ratio of the resin composition I, the upper limit and lower limit of the mass ratio of the resin composition I described above can be arbitrarily combined. For example, the preferred range of the mass ratio of the resin composition I to the resin B may be resin composition I:resin B=3:97 to 65:35, 3:97 to 60:40, 8:92 to 60:40, 10:90 to 70:30, 10:90 to 50:50, 3:97 to 40:60, or 2:98 to 45:55.
[0244] Melting point difference
[0245] Melting point Tm of resin composition I I Melting point Tm of resin B B Difference Tm I -Tm B Preferably, the melting point difference Tm is 5°C or more. In this case, the moldability of the foamed beads can be further improved, and the range of molding pressures in which a good molded body can be obtained can be further expanded. From the viewpoint of more reliably obtaining the effect, the melting point difference Tm I -Tm B It is more preferably 8°C or higher, and even more preferably 10°C or higher. From the same viewpoint, the melting point difference Tm I -Tm B It is preferably 35°C or lower, more preferably 30°C or lower, further preferably 28°C or lower, particularly preferably 25°C or lower, and most preferably 20°C or lower.
[0246] In constituting the melting point difference Tm I -TmB When the preferred range of the melting point difference Tm is I -Tm B For example, the melting point difference Tm I -Tm B The preferred range may be 5°C to 35°C, 8°C to 28°C, 10°C to 30°C, 10°C to 25°C, or 5°C to 20°C.
[0247] Difference in melt mass flow rate
[0248] Melt mass flow rate MFR of resin composition I I The melt mass flow rate MFR of resin B B Difference MFR I -MFR B It is preferably 5 g / 10 minutes or more, more preferably 8 g / 10 minutes or more, and even more preferably 12 g / 10 minutes or more. I -MFR B It is preferably 40 g / 10 minutes or less, more preferably 35 g / 10 minutes or less, further preferably 30 g / 10 minutes or more, and particularly preferably 25 g / 10 minutes or less. In this case, the variation in the in-mold moldability of the foamed beads can be further reduced.
[0249] The difference in the melt mass flow rate MFR I -MFR B When the preferred range of the melt mass flow rate difference MFR is I -MFR B For example, the difference in melt mass flow rate MFR I -MFR B It can be more than 5g / 10 minutes and less than 40g / 10 minutes, more than 5g / 10 minutes and less than 35g / 10 minutes, more than 8g / 10 minutes and less than 30g / 10 minutes, more than 12g / 10 minutes and less than 25g / 10 minutes, or more than 10g / 10 minutes and less than 40g / 10 minutes.
[0250] Melt mass flow rate ratio
[0251] Melt mass flow rate MFR of resin composition I I Relative to the melt mass flow rate MFR of resin B B MFR I / MFR BIt is preferably 0.3 to 8, more preferably 0.5 to 7.5, and still more preferably 1 to 7. In this case, the balance between foamability and in-mold formability is good, and in-mold formability can be more easily improved even when the apparent density is low.
[0252] ·Bending elastic modulus ratio
[0253] Flexural modulus of resin B M B Relative to the bending elastic modulus M of the resin composition I I Ratio M B / M I It is preferably 0.8 or more, more preferably 0.9 or more, further preferably 1 or more, and particularly preferably greater than 1. In addition, the bending elastic modulus M of the resin B is B Relative to the bending elastic modulus M of the resin composition I I Ratio M B / M I The bending elastic modulus M of the resin B combined with the resin composition I is preferably 2 or less, more preferably 1.6 or less, and further preferably 1.5 or less. B When the content is within the specific range, the in-mold moldability of the foamed beads can be further improved. Furthermore, by using the foamed beads for in-mold molding, the compressive strength of the molded body can be more easily improved.
[0254] The ratio of the bending elastic modulus M B / M I When the preferred range is within the range of B / M I For example, B / M I The preferred range of may be 0.8 or more and 2 or less, 0.9 or more and 1.6 or less, greater than 1 and 2 or less, or 1 or more and 1.5 or less.
[0255] In addition, by using a resin composition I having a melting point above a specific temperature, it is easy to increase the compressive stress of the obtained molded body under a relatively small compressive strain. On the other hand, when a resin composition A is used as the resin composition I, the resin composition A has a bending elastic modulus M A Relative to melting point Tm A The ratio of the polypropylene resin composition to the foamed layer is relatively low, and there is a tendency for the in-mold moldability of the foamed particles to decrease. The polypropylene resin composition constituting the foamed layer comprises such a resin composition A and a polypropylene resin having a melting point Tm higher than that of the resin composition A. A Low melting point Tm BOn the other hand, the resin B having a relatively high flexural modulus has a good balance between the melting point and the flexural modulus in the foaming layer, so it is easy to stably obtain foamed particles that have excellent in-mold formability and can be formed into a molded body with excellent compressive strength.
[0256] From the viewpoint of more reliably obtaining the above-mentioned effects, the core layer of the resin particles in the method for producing the foamed particles is composed of a molten mixture of a polypropylene resin composition A and a polypropylene resin B, and the melting point Tm of the polypropylene resin composition A is A Above 160°C, the bending modulus M A is 800 MPa or more and 1200 MPa or less, and the melting point Tm of the polypropylene resin B is B Less than 160℃, bending modulus M B 900 MPa or more and 1400 MPa or less,
[0257] The polypropylene-based resin composition A comprises a polypropylene-based resin derived from a post-consumer material as recycled polypropylene and an ethylene-propylene-based rubber,
[0258] The bending elastic modulus M B With respect to the bending elastic modulus M A Ratio M B / M A is 1 or more,
[0259] The mass ratio of the polypropylene resin composition A to the polypropylene resin B in the core layer is polypropylene resin composition A: polypropylene resin B = 10: 90 to 70: 30. In this case, the resin component from post-consumer materials can be effectively utilized, and the moldability is good, and a foamed bead molded body with excellent compression strength can be stably obtained.
[0260] Preferably, the melting heat H of the resin composition I is I is 60 J / g or more and 100 J / g or less, and the melting heat H of the resin B is B is 60 J / g or more and 100 J / g or less, and the melting heat H I With the melting heat H B The sum H I +H B 140 J / g or more and 175 J / g or less. When resin composition A is used as resin composition I, when the physical properties of resin composition A derived from recycled materials such as post-consumer materials are compared between different batches, the deviation of the physical properties is likely to become large. In contrast, by reducing the melting heat H of resin composition I to I and the melting heat H of resin B BOn the basis of being respectively within the specific range, further, the sum of the heat of fusion H I +H B Within the specific range, even when using a resin composition A having large deviations in physical properties, the in-mold moldability of the foamed beads can be improved more stably. B Relative to the melting heat H of the resin composition I I Ratio H B / H I It is preferably 0.7 or more and 1.2 or less, and more preferably 0.8 or more and 1.1 or less.
[0261] In addition, the melting heat H of the resin composition I I The method for determining the heat of fusion H of the resin B is as follows: the resin composition I is used as the test piece instead of the resin B. B The determination method is the same.
[0262] The method for preparing resin particles is not particularly limited. For example, in the case of making resin particles of a single-layer structure by a wire cutting method, the resin composition I, the resin B, and additives used as needed are supplied to an extruder, and the resin composition I and the resin B are heated and kneaded in the extruder to obtain a molten mixture. The molten mixture is extruded into a wire shape from a small hole of a die head attached to the downstream side of the extruder. By cutting off the extrudate of the wire shape to a desired length while pulling, it is possible to obtain resin particles consisting of a molten mixture (more specifically, a melt-kneaded product) of the resin composition I and the resin B.
[0263] The operation of manufacturing the molten mixture of the resin composition I and the resin B and the operation of manufacturing the resin pellets from the molten mixture can be performed using the same extruder as described above. In addition, for example, the above two operations can also be performed using different extruders, etc.
[0264] The acetone insoluble components (i.e., D sol -A insol The amount of D in the resin particles is preferably 0.02 g or more and 0.10 g or less per 1 g of the resin particles. sol -A insol It is mainly composed of ethylene propylene rubber. sol -A insol When the amount of D in the resin particles is within the specific range, the foamed particles can be obtained more easily. sol -A insolThe amount of D in the resin particles is preferably 0.03 g or more, and further preferably 0.04 g or more per 1 g of the resin particles. sol -A insol The amount is more preferably 0.09 g or less, further preferably 0.08 g or less, and particularly preferably 0.07 g or less per 1 g of the resin particles.
[0265] D in the resin particles sol -A insol When the amount of D in the above resin particles is within the preferred range, the above resin particles can be arbitrarily combined. sol -A insol For example, D in the resin particles sol -A insol The preferred range of the amount of D in the resin particles is 0.03 g to 0.09 g, 0.04 g to 0.08 g, or 0.04 g to 0.07 g. sol -A insol The method for determining the amount of D in the foamed particles is to use resin particles instead of foamed particles to calculate the amount per 1g of resin particles. sol -A insol The method for determining the amount is the same.
[0266] The melting point Tmr of the resin particles is preferably 130°C or more and 162°C or less. By setting the melting point Tmr of the resin particles within the specific range, the foamed particles can be obtained more easily. From the viewpoint of more easily improving the compressive properties of the molded body, the melting point Tmr of the resin particles is preferably 135°C or more, more preferably 140°C or more, further preferably 143°C or more, particularly preferably 146°C or more, and most preferably 150°C or more. In addition, from the viewpoint of more easily obtaining foamed particles with good in-mold formability, the melting point Tmr of the resin particles is preferably 160°C or less, more preferably 158°C or less.
[0267] When constituting the preferred range of the melting point Tmr of the resin particles, the upper limit and lower limit of the melting point Tmr of the resin particles described above can be arbitrarily combined. For example, the preferred range of the melting point Tmr of the resin particles can be 135°C or more and 160°C or less, 140°C or more and 158°C or less, 143°C or more and 158°C or less, 146°C or more and 158°C or less, or 150°C or more and 162°C or less. The method for determining the melting point Tmr of the resin particles is the same as the method for determining the melting point Tm of the foamed particles described above, except that a test piece composed of resin particles is used instead of a test piece composed of foamed particles.
[0268] The bending elastic modulus of the polypropylene resin composition (more specifically, the molten mixture of resin composition I and resin B) constituting the core layer of the resin particles is preferably 800 MPa or more and 1600 MPa or less, more preferably 800 MPa or more and 1400 MPa or less, further preferably 800 MPa or more and 1300 MPa or less, particularly preferably 900 MPa or more and 1300 MPa or less, and most preferably 900 MPa or more and 1200 MPa or less. In this case, the moldability of the foamed particles can be further improved.
[0269] The difference Tmr-Tcr between the melting point Tmr of the resin particles and the crystallization temperature Tcr of the resin particles is preferably 38°C or less. In this case, the foamed particles can be obtained more easily. In addition, the lower limit of the difference Tmr-Tcr in the resin particles is usually 30°C. The lower limit of the difference Tmr-Tcr is preferably 32°C. The method for determining the crystallization temperature Tcr of the resin particles is the same as the method for determining the crystallization temperature Tcr of the foamed particles described above, except that a test piece composed of resin particles is used instead of a test piece composed of foamed particles.
[0270] In the polypropylene resin composition constituting the core layer, the rubber-like body is preferably present as a microdomain dispersed in a matrix composed of a polypropylene resin. In this case, from the viewpoint of being able to stably improve the in-mold formability of the foamed particles, the average diameter of the rubber-like body dispersed in the polypropylene resin in the resin particles is preferably 0.1 μm or more and 2 μm or less, more preferably 0.3 μm or more and 1.5 μm or less, and further preferably 0.5 μm or more and 1 μm or less. The method for observing the morphology of the resin particles and the method for determining the average diameter of the rubber-like body are the same as the above-mentioned method for observing the morphology of the foamed particles and the method for determining the average diameter of the rubber-like body except that the resin particles are used instead of the foamed particles.
[0271] In the direct foaming method described below, from the viewpoint of being able to improve the foamability when producing foamed beads from resin particles and from the viewpoint of stably obtaining foamed beads having excellent in-mold moldability, it is preferred that the core layer of the resin particles is composed of a molten mixture of the impact polypropylene as the polypropylene resin composition I and the propylene random copolymer as the polypropylene resin B.
[0272] The melting point Tm of the impact polypropylene of the resin composition I is I The melting point Tm of the propylene random copolymer as the resin B is B Difference Tm I -Tm B 5℃ or above and 35℃ or below,
[0273] The melt mass flow rate MFR of the resin composition I measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is I More than 3g / 10 minutes,
[0274] The melt mass flow rate MFR of the resin B measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is B 3g / 10min or more and 10g / 10min,
[0275] The melt mass flow rate MFR of the resin composition I I Relative to the melt mass flow rate MFR of the resin B B MFR I / MFR B It is 0.3 or more and 8 or less.
[0276] 〔Foaming〕
[0277] Next, the resin particles are foamed. The method for foaming the resin particles is not particularly limited, but the resin particles are preferably foamed by a method called a "direct foaming method" in which the resin particles impregnated with a foaming agent dispersed in an aqueous medium in a container are released from the container together with the aqueous medium in an atmosphere having a pressure lower than the pressure in the container. A preferred embodiment of the foaming method is described below.
[0278] When the resin particles are foamed by the direct foaming method, first, the resin particles are placed in a container such as a pressure vessel and dispersed in an aqueous medium. At this time, a dispersant, a dispersing aid, a surfactant, etc. for dispersing the resin particles may be added to the aqueous medium in the container as required.
[0279] As the dispersant, for example, inorganic particles such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, and mica can be used. These inorganic particles can be used alone or in combination of two or more inorganic particles. As the dispersing aid, for example, aluminum sulfate can be used. In addition, as the surfactant, for example, anionic surfactants such as sodium alkylbenzene sulfonate, sodium dodecylbenzene sulfonate, and sodium alkane sulfonate can be used. These surfactants can be used alone or in combination of two or more surfactants.
[0280] Next, a foaming agent is supplied into the container to increase the pressure in the container, thereby impregnating the resin particles with the foaming agent. Thus, resin particles containing the foaming agent can be obtained. At this time, the resin particles in the container are heated together with the aqueous medium, so that the impregnation of the foaming agent into the resin particles can be promoted.
[0281] As the foaming agent used in the foaming process, for example, inorganic physical foaming agents such as carbon dioxide, air, nitrogen, helium, argon, hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, hexane, ethyl chloride, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, trans-1-chloro-3,3,3-trifluoropropene and other halogenated hydrocarbons such as organic physical foaming agents can be used. From the perspective of environmental load and operability, carbon dioxide is preferably used as the foaming agent. The amount of the foaming agent added is preferably 0.1 parts by mass or more and 30 parts by mass or less, preferably 0.5 parts by mass or more and 15 parts by mass or less relative to 100 parts by mass of the resin particles.
[0282] The pressure in the container immediately before foaming is preferably 0.5 MPa (G) or more under gauge pressure. On the other hand, the pressure in the container is preferably 4.0 MPa (G) or less under gauge pressure. If it is within the above range, foaming particles can be safely manufactured without the risk of damage to the container, explosion, etc.
[0283] After the foaming agent is impregnated into the resin particles, the contents of the container are released in an atmosphere with a lower pressure than that of the container. The resin particles are foamed to form a cell structure, and are cooled by the external gas (ie, atmosphere) to stabilize the cell structure, thereby obtaining foamed particles.
[0284] In the manufacturing method, a step of adjusting the crystal structure of the resin component contained in the resin particles may be performed during the period from dispersing the resin particles in the aqueous medium to foaming the resin particles. By adjusting the crystal structure of the resin component and then foaming the resin particles, foamed particles having excellent in-mold formability and excellent compression strength can be easily obtained.
[0285] The method for adjusting the crystal structure of the resin component is as follows, for example. First, a holding process is performed in which the temperature of the resin particles is maintained within a temperature range of (melting point of the resin composition constituting the core layer of the resin particles - 15°C) or more and (melting point of the resin composition + 15°C) or less for a sufficient period of time, preferably for about 10 to 60 minutes. By foaming the resin particles subjected to this holding process, foamed particles having a crystal structure in which the above-mentioned high temperature peak appears in the DSC curve can be obtained. In addition, the temperature in the container during foaming is preferably above (melting point of the resin composition - 5°C) and below (melting point of the resin composition + 10°C).
[0286] In the manufacturing method, resin particles that have been subjected to the holding step may be prepared in advance, and the resin particles may be foamed to obtain foamed particles. From the viewpoint of improving the productivity of the foamed particles, it is preferred that the resin particles dispersed in the dispersion medium in the container are heated in the presence of a foaming agent to perform the holding step, and then the contents of the sealed container are released from the container in an atmosphere having a pressure lower than the pressure in the container to foam the resin particles, thereby obtaining foamed particles having a crystal structure showing the above-mentioned high temperature peak.
[0287] As a reason why the mechanical strength and in-mold formability of the foamed beads can be improved by heating and foaming under the above conditions, it can be considered that secondary crystals of the polypropylene resin are formed in the resin composition constituting the foamed beads, etc. Whether secondary crystals of the polypropylene resin are formed can be judged by the presence or absence of a high temperature peak in the DSC curve.
[0288] In the manufacturing method, when foaming the resin particles, the resin particles can be foamed in one stage as described above, or the resin particles can be foamed in multiple stages of more than two stages. When the resin particles are foamed in two stages, first, in the foaming process of the first stage, the resin particles are foamed by a direct foaming method or the like to obtain primary foamed particles. In the foaming process of the second stage, for example, after the primary foamed particles are pressurized by air or the like to increase the pressure (internal pressure) in the bubbles of the primary foamed particles, the primary foamed particles are heated by steam or the like to further foam them. By foaming the resin particles in multiple stages in this way, foamed particles with a higher foaming ratio (i.e., a low bulk density) can be easily obtained.
[0289] (Polypropylene resin foamed particle molded body)
[0290] After the foamed beads are filled into a forming mold, a heating medium such as steam is supplied into the forming mold for in-mold forming, thereby obtaining a molded body. The density of the molded body is preferably 10 kg / m 3 Above and 200kg / m 3 In this case, the balance between the lightness and the compressive strength of the molded body becomes more favorable.
[0291] From the viewpoint of further improving the compressive strength of the molded body, the density of the molded body is more preferably 12 kg / m 3 More preferably, 15 kg / m 3 More than, particularly preferably 20kg / m 3 From the viewpoint of further improving the lightness of the molded body, the density of the molded body is more preferably 100 kg / m 3 Below, more preferably 80kg / m 3 Below, particularly preferably 70kg / m3 Below, most preferably 60kg / m 3 The density of the molded body is calculated by dividing the mass of the molded body (unit: g) by the volume (unit: L) obtained from the outer dimensions of the molded body and converting the result into units.
[0292] In order to further improve the mechanical properties of the molded body, the closed cell ratio of the molded body is preferably 70% or more, more preferably 75% or more, and even more preferably 80% or more.
[0293] The closed cell ratio of the molded body was measured according to ASTM 2865-70 step C. Specifically, first, a test body of 25 mm in length × 25 mm in width × 30 mm in height was cut out from the center of the molded body, and the geometric volume Va (unit: cm 3 ), that is, the product of the longitudinal dimension (unit: cm), the lateral dimension (unit: cm) and the height dimension (unit: cm). Next, according to step C described in ASTM-D2856-70, an air comparison pycnometer (specifically, "Beckman Model 1000 Air Comparison Pycnometer" manufactured by Tokyo Science Co., Ltd.) is used to measure the true volume value Vx of the test body. In addition, the true volume value Vx obtained by the air comparison pycnometer is the sum of the volume of the resin constituting the measurement sample and the total volume of the bubbles in the independent bubble part of the measurement sample (unit: cm 3 ).
[0294] The closed cell ratio (unit: %) of the test body was calculated using the mass W (unit: g) of the test body, the density ρ (unit: g / cm 3 ), the geometric volume Va of the test body and the true volume Vx of the test body obtained by the above method are expressed by the following formula (2).
[0295] Closed cell ratio = (Vx-W / ρ) × 100 / (Va-W / ρ)…(2)
[0296] The above operation was performed on five test pieces, and the closed cell ratio of each test piece was calculated. Then, the arithmetic mean of the closed cell ratios of the five test pieces was taken as the closed cell ratio of the molded body.
[0297] [Compression properties of molded body]
[0298] The ratio of the 5% compressive strength to the 50% compressive strength in the molded body is 0.45 or more, more preferably 0.50 or more, further preferably 0.52 or more, and particularly preferably 0.55 or more. The energy absorption characteristics of the molded body can be evaluated based on the magnitude of the compressive stress under various strains. More specifically, in a stress-strain curve in which the horizontal axis is the strain applied to the molded body and the vertical axis is the compressive stress corresponding to the strain, the energy absorption characteristics of the molded body can be evaluated based on the magnitude of the compressive stress under various strains. a The closer the shape of the stress-strain curve is to a rectangular shape, the more the molded body has the desired energy absorption characteristics. a The compressive stress σ a and the dependent variable ε a Small strain ε b The compressive stress σ b The smaller the difference, the closer the shape of the stress-strain curve is to a rectangle, and the strain ε a The energy absorption characteristics of the molded body in the region up to 100% are better. In addition, the upper limit of the ratio of the 5% compressive strength to the 50% compressive strength in the molded body is not particularly limited as long as it is within the range that can achieve the desired purpose of the present invention, and is usually 1.0, 0.8, or 0.7.
[0299] The molded body having the compression strength ratio within the specific range has a stress-strain curve closer to a rectangular shape, thus having good compressive properties, and being able to make the energy absorption characteristics better under a wide range of strains. Such a molded body can be preferably used as a vehicle component. As a vehicle component, examples thereof include impact absorbing materials such as bumper cores, tibia pads, floor spacers, and seat core materials.
[0300] The 5% compressive strength and 50% compressive strength of the molded article are values obtained based on the method specified in JIS K7220: 2006. The method for measuring the 5% compressive strength and 50% compressive strength of the molded article will be described in more detail in Examples.
[0301] (Resin raw materials)
[0302] The resin raw material for foamed beads used in the method for producing foamed beads is preferably a polypropylene resin composition containing a polypropylene resin composition a derived from automobile parts and having a melting point of 160° C. or higher.
[0303] By using the foamed beads resin raw material as the polypropylene resin composition A in the production method, foamed beads having excellent in-mold moldability can be produced, and resin components derived from automobile parts can be effectively utilized as resources.
[0304] The resin raw material at least includes the polypropylene resin composition a from automobile parts, that is, automobile parts such as bumpers and instrument panels formed of polypropylene resin compositions, recycled polypropylene resin compositions from defective products and scraps generated in the manufacturing process of automobile parts, and recycled polypropylene resin compositions with polypropylene resin compositions recovered from ASR as the main component. In addition to the polypropylene resin composition a from automobile parts, the resin raw material may also include recycled polypropylene resin compositions from consumer products other than automobiles such as home appliances and non-recycled polypropylene resins.
[0305] From the viewpoint of material recycling of the resin component derived from automobile parts, the content of the polypropylene resin composition a derived from automobile parts contained in the resin raw material is preferably 50% by mass or more, more preferably 60% by mass or more.
[0306] Likewise, from the viewpoint of material recycling of the resin component derived from ASR, the content of the polypropylene resin composition a1 recovered from the ASR contained in the resin raw material is preferably 50% by mass or more, more preferably 60% by mass or more.
[0307] As described above, the resin raw material is configured so as to be usable as the polypropylene resin composition A in the production method. Therefore, for more detailed configuration of the resin raw material, the description related to the polypropylene resin composition A can be appropriately referred to.
[0308] The resin raw material preferably has a melt flow rate of 10 g / 10 min or more and 40 g / 10 min or less when measured at a temperature of 230° C. and a load of 2.16 kg. The resin raw material having a melt flow rate within the specific range can be suitably used for producing the foamed beads.
[0309] From the same viewpoint, the ash content of the resin raw material is preferably 1% by mass or more and 25% by mass or less. In addition, the resin raw material shows a morphology of a polypropylene resin as a matrix and a rubber-like body containing ethylene propylene rubber as a micro-domain, and the bending elastic modulus of the resin raw material is preferably 800MPa or more and 1200MPa or less.
[0310] The manufacturing method of the resin raw material is as follows. First, the polypropylene resin composition a from the automotive component is supplied to an extruder for melt mixing. At this time, the polypropylene resin composition a from the automotive component can be crushed as needed. In addition, as needed, in addition to the polypropylene resin composition a from the automotive component, recycled polypropylene resin compositions, non-recycled polypropylene resins, and additives from consumer products other than automobiles can also be added to the extruder.
[0311] After the polypropylene resin or the like is melt-kneaded in an extruder, the molten mixture is extruded from the extruder. The extrudate thus obtained is cooled, cut into pellets of appropriate length, and thereby a resin raw material can be obtained.
[0312] Example
[0313] Examples of the foamed particles are described below.
[0314] <Implementation Method 1>
[0315] (Polypropylene resin composition A)
[0316] Table 1 shows the properties of the polypropylene resin composition A used in the manufacture of the foamed particles in this embodiment. In addition, the resin composition A1-1 used in this example is "PLC-A02" manufactured by Planic Co., Ltd., and the resin composition A1-2 is "ELVBP-10" manufactured by the same company. Both the resin composition A1-1 and the resin composition A1-2 are impact-resistant polypropylenes containing ethylene propylene rubber from post-consumer materials. More specifically, the main component of the resin composition A1-1 is the polypropylene resin composition a1 recovered from ASR, and the resin composition A1-2 is the polypropylene resin composition a recovered from used automobile parts (more specifically, bumpers).
[0317] Resin composition A1-1 and resin composition A1-2 are cylindrical pellets, and the average length in the height direction of the pellets (the average length in the extrusion direction when manufacturing the pellets) is 3mm, the diameter of the pellets is 3mm, and the average mass of the pellets is 16mg. In addition, the resin composition A1-1 and the resin composition A1-2 contain an inorganic substance with talc as the main component. By the method described later, the form of the resin composition A1-1 and the resin composition A1-2 used in this example is observed, and the result shows that the resin composition A1-1 and the resin composition A1-2 are all based on polypropylene resin as the matrix and the rubber-like body containing ethylene propylene rubber as the form of the micro-region.
[0318] Table 1
[0319] (Table 1) Polypropylene resin composition A
[0320] unit A1-1 A1-2 density <![CDATA[kg / m 3 ]]> 930 990 <![CDATA[D sol -A insol ]]> g 0.12 0.11 Carbon black content quality% 0.4 0.7 Ash content quality% 4.8 12.7 <![CDATA[Melting point Tm A > ℃ 164 164 <![CDATA[Heat of fusion H A > J / g 81 65 <![CDATA[Melt mass flow rate MFR A > g / 10 minutes 26 29 <![CDATA[Flexural modulus M A > MPa 950 1090 <![CDATA[M A / Tm A ]]> MPa / ℃ 5.8 6.6
[0321] The methods for measuring the physical property values of the resin composition A shown in Table 1 are as follows.
[0322] 〔D in resin composition A sol -A insol 〕
[0323] D in resin composition A sol -A insol , that is, the amount of components soluble in n-decane and insoluble in acetone is determined by the following method. Specifically, first, accurately weigh about 5 g of resin composition A as a sample. Add the sample to 200 ml of n-decane and heat to dissolve at 145°C for 30 minutes. Next, cool the obtained n-decane solution to 23°C over 2 hours and leave it at 23°C for 30 minutes. In this way, the components insoluble in n-decane contained in the n-decane solution are precipitated. Thereafter, the n-decane solution is filtered to filter out the precipitate to obtain a n-decane extract containing n-decane-soluble components. Add the n-decane extract to about 3 times the amount of acetone relative to the n-decane extract, and leave it at 23°C for 18 hours to dissolve the acetone-insoluble components in the n-decane extract (that is, D in resin composition A). sol -A insol ) is precipitated. The precipitate is filtered and dried, and the mass of the precipitate is measured. The mass of the precipitate measured in this way (unit: g) is divided by the mass of the sample (unit: g) to obtain a value as D per 1 g of the resin composition A contained in the resin composition A. sol -A insol The amount (unit: g) is calculated.
[0324] [Form of resin composition A1-1]
[0325] The morphology of resin composition A1-1 is observed by the following method. First, the cylindrical pellets composed of resin composition A1-1 are cut vertically relative to the height direction of the pellets in a manner through the center thereof, and an observation sample in which the cross section of the center of the pellets is exposed is prepared. Next, the observation sample is embedded in an epoxy resin, and after electron staining with ruthenium tetroxide, a slice containing the center of the pellets is made from the sample using an ultramicrotome or the like. The slice is mounted on a microgrid of a transmission electron microscope (e.g., "JEM-1040Flash" manufactured by JEOL), observed at a magnification of 5000 times, and a cross-sectional photograph (i.e., TEM photograph) of resin composition A1-1 is taken.
[0326] The morphology of the phase of the polypropylene resin and the phase of the rubber-like body containing the ethylene-propylene rubber in the resin composition A1-1 were visually observed from the cross-sectional photograph. Figure 3 A cross-sectional photograph of resin composition A1-1 is shown in FIG. Figure 3 In FIG. 1 , the microdomain D of the rubber-like body composed of the ethylene-propylene rubber is shown in a relatively dark tone, and the matrix M of the polypropylene resin is shown in a bright tone relative to the microdomain D.
[0327] In addition, the average diameter of the rubber-like body containing ethylene propylene rubber is calculated based on the TEM photo. More specifically, the longest diameter and the shortest diameter of 50 micro-regions randomly selected from the micro-regions (specifically the rubber-like body) appearing in the TEM photo are measured respectively. The arithmetic mean of the longest diameter and the shortest diameter obtained in this way is used as the average diameter of the rubber-like body containing ethylene propylene rubber. As a result, the average diameter of the rubber-like body containing ethylene propylene rubber in resin composition A1-1 is 1.2μm.
[0328] 〔Ash content〕
[0329] The ash content of resin composition A is measured according to the direct ashing method (A method) of JIS K7250-1:2006. Specifically, first, after accurately weighing about 5 g of resin composition A, resin composition A is placed in a crucible. The resin composition A in the crucible is heated for 1 hour in an electric furnace with the atmosphere temperature set to 600°C, thereby causing the resin composition A to burn. After the heating is completed, the mass of the residue remaining in the crucible is measured. Then, the value of the ratio of the mass of the residue to the mass of the resin composition A before heating, which is expressed as a percentage, is taken as the ash content of resin composition A (unit: mass %).
[0330] Melting point Tm A and the heat of fusion H A 〕
[0331] Melting point Tm of resin composition A A Determined based on JIS K7121-1987. Specifically, first, based on "(2) After a certain heat treatment, the melting temperature is measured" of "3. Conditioning of the test piece" in JIS K7121-1987, the state of the test piece composed of the resin composition A is adjusted. The state-adjusted test piece is heated from 23°C to 230°C at a heating rate of 10°C / min, thereby obtaining a DSC curve. In addition, the flow rate of nitrogen in the measurement environment is set to 30 mL per minute. In addition, the top temperature of the melting peak appearing in the DSC curve is set to the melting point Tm A In addition, as a measuring device, a heat flux differential scanning calorimeter (manufactured by SII Nano Technology Co., Ltd., model: DSC7020) was used.
[0332] In addition, the melting heat H of the resin composition A was determined from the DSC curve obtained by differential scanning calorimetry according to JIS K 7122-1987. A Specifically, at the above melting point Tm A On the DSC curve obtained by the measurement, a straight line connecting the point corresponding to 80°C in the DSC curve and the end point on the high temperature side of the melting peak with the highest peak temperature is drawn. Then, based on the area of the region surrounded by the straight line determined in this way and the melting peak of the DSC curve, the melting heat H of the resin composition A is calculated. A .
[0333] Melt mass flow rate MFR A 〕
[0334] According to JIS K7210-1:2014, under the conditions of temperature 230°C and load 2.16 kg, the melt mass flow rate MFR of the resin composition A is A Carry out determination.
[0335] 〔Flexural modulus M A 〕
[0336] The resin composition A was hot-pressed at 180°C to prepare a sheet with a thickness of 4 mm, and a test piece with a length of 80 mm×width of 10 mm×thickness of 4 mm was cut out from the sheet. The bending elastic modulus M of the test piece was determined in accordance with JIS K7171:2008. A In addition, the radius R1 of the indenter and the radius R2 of the support platform were both 5 mm, the distance between the fulcrums was 64 mm, and the test speed was 2 mm / min.
[0337] (Polypropylene resin B)
[0338] Table 2 shows the properties of the polypropylene resin B used in the manufacture of the foamed beads in this embodiment. In addition, the resin B used in this example is composed of non-recycled polypropylene resin. In addition, the resin B used in this example is any one of propylene-ethylene random copolymers (B1-1 to B1-4) or homopolypropylene (B1-5). In addition, in Table 2, the propylene random copolymer is recorded as "rPP" and the homopolypropylene is recorded as "hPP".
[0339] The methods for measuring the physical property values shown in Table 2 are the same as the methods for measuring the physical property values in the above-mentioned resin composition A. In addition, the calculation method of the "ethylene component content" of the resin B in Table 2 is as follows.
[0340] The content of ethylene components in resin B is determined by a known method determined by IR spectroscopy. Specifically, it is determined by using the method described in the Handbook of Polymer Analysis (edited by the Polymer Analysis Research Council of the Japanese Society of Analytical Chemistry, published in January 1995, published by Kinokuniya Bookstore, pages and item names: 615-616 "II.2.32.3.4 Propylene / ethylene copolymer", 618-619 "II.2.32.3.5 Propylene / butene copolymer"), that is, a method of quantitatively determining the relationship between the value obtained by correcting the absorbance of ethylene and butene with a predetermined coefficient and the thickness of the film-like test piece.
[0341] More specifically, first, resin B was hot-pressed at 180°C to form a film, and a plurality of test pieces with different thicknesses of 0.1 to 0.3 mm were prepared. Next, the IR spectrum of each test piece was measured to read the 722 cm-1 IR spectrum derived from ethylene. -1 and 733cm -1 The absorbance at 722 , A 733 ) and 766cm from butene -1 The absorbance at 766 ). Next, for each test piece, the ethylene content (unit: mass %) in resin B was calculated using the following formulas (3) to (5). The value obtained by arithmetic averaging the ethylene content obtained for each test piece was taken as the ethylene content (unit: mass %) in resin B.
[0342] (K′ 733 ) c =I / 0.96{(K′ 733 ) a -0.268(K′ 722 ) a}…(3)
[0343] (K′ 722 ) c =1 / 0.96{(K′ 722 ) a -0.150(K′ 733 ) a}…(4)
[0344] Ethylene content = 0.575 {(K' 722 ) c +(K′ 733 ) c}…(5)
[0345] Among them, K′ in formulas (3) to (5) a is the apparent absorption coefficient (K′) at each wave number a=A / ρt), K′ c is the corrected absorption coefficient, A is the absorbance, and ρ is the density of the resin (unit: g / cm 3 ), t is the thickness of the film-like test piece (unit: cm).
[0346] For each test piece, the butene content (unit: mass %) in the resin B was calculated using the following formula (6). The value obtained by arithmetic averaging the butene content obtained for each test piece was taken as the butene content (unit: mass %) in the resin B.
[0347] Butene content = 12.3 (A 766 / L)…(6)
[0348] In the formula (6), A is absorbance, and L is the thickness of the film-like test piece (unit: mm).
[0349] Table 2
[0350] (Table 2) Polypropylene resin B
[0351] unit B1-1 B1-2 B1-3 B1-4 B1-5 Types of polypropylene resins - R R R R h density <![CDATA[kg / m 3 ]]> 900 900 900 900 900 Ethylene content quality% 2.8 1.1 3.4 0.6 0 Butene content quality% - - - 9.7 - Ash content quality% 0 0 0 0 0 <![CDATA[Melting point Tm B > ℃ 143 151 139 141 162 <![CDATA[Heat of fusion H B > J / g 79 91 63 66 101 <![CDATA[Melt mass flow rate MFR B > g / 10 minutes 8 7 7 7 10 <![CDATA[Flexural modulus M B > MPa 950 1200 850 910 1650
[0352] Next, the structure and production method of the foamed beads in this embodiment will be described.
[0353] (Example 1-1)
[0354] The foaming particles of Example 1-1 have a foaming layer composed of a polypropylene resin composition. The resin composition constituting the foaming layer includes a polypropylene resin and a rubber-like body G including ethylene propylene rubber, and the rubber-like body G is dispersed in the polypropylene resin. When making the foaming particles of Example 1-1, first, resin composition A1-1, resin B1-1 and a bubble regulator are put into an extruder to form a molten mixture of resin composition A and resin B in the extruder. In addition, the mass ratio of resin composition A1-1 to resin B1-1 is the value shown in Table 3. In addition, as a bubble regulator, zinc borate is used. Relative to the total of 100% by mass of resin composition A1-1 and resin B1-1, the addition amount of zinc borate is 0.05% by mass. Afterwards, the mixture in the molten state is extruded into a strand from a small hole of a die head arranged on the downstream side of the extruder. After the strand-like extrudate is pulled out and cooled, it is cut into an appropriate length using a granulator, thereby obtaining resin particles.
[0355] The resin particles thus obtained were foamed by a direct foaming method. Specifically, first, 1 kg of the resin particles were put into a container with an internal volume of 5 L together with 3 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.02 parts by mass of sodium alkylbenzene sulfonate as a dispersing aid, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the resin particles, and the resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0356] After that, carbon dioxide as a foaming agent was supplied into the sealed container while stirring the container, so that the temperature in the container rose to 155.5°C. The pressure in the container at this time was 2.1 MPa (G). After that, the temperature in the container was adjusted to 156°C and the temperature was maintained for 15 minutes, thereby impregnating the foaming agent into the resin particles. After that, the container was opened and the contents were released under atmospheric pressure, thereby foaming the resin particles. Through the above, the foamed particles of Example 1-1 were obtained.
[0357] (Examples 1-2 to 1-4)
[0358] The foamed beads of Examples 1-2 to 1-4 have substantially the same structure as the foamed beads of Example 1-1, except that the mass ratio of the resin composition A1-1 to the resin B1-1 is changed as shown in Table 3. In the manufacturing method of the foamed beads in these Examples, the mass ratio of the resin composition A1-1 to the resin B1-1 supplied to the extruder is changed, and the temperature in the container during foaming is changed to 152.5°C in Example 1-2, 161°C in Example 1-3, and 158.5°C in Example 1-4, respectively. The manufacturing method of the foamed beads in these Examples is substantially the same as the manufacturing method of the foamed beads in Example 1-1.
[0359] (Examples 1 to 5 to 1-7)
[0360] As shown in Table 4, the foamed beads of Examples 1-5 to 1-7 have substantially the same structure as the foamed beads of Example 1-4 except that any one of polypropylene resins B1-2 to B1-4 is used instead of polypropylene resin B1-1 as resin B. In the method for producing the foamed beads in these Examples, the resin B supplied to the extruder is changed from polypropylene resin B1-1 to polypropylene resin B shown in Table 4, and the method for producing the foamed beads is substantially the same as the method for producing the foamed beads of Example 4.
[0361] (Comparative Example 1-1)
[0362] The foamed layer of the foamed beads of Comparative Example 1-1 does not contain resin B, but is composed of resin composition A. The method for producing the foamed beads of Comparative Example 1-1 is shown in Table 5, and is substantially the same as the method for producing the foamed beads of Example 1-1, except that resin composition A1-1 is used instead of the resin composition containing resin composition A and resin B to produce the resin beads, and the temperature in the container during foaming is changed to 164°C.
[0363] (Comparative Example 1-2)
[0364] As shown in Table 5, the foamed beads of Comparative Example 1-2 have substantially the same structure as the foamed beads of Example 1-4 except that the polypropylene resin B1-5 is used instead of the polypropylene resin B1-1 as the resin B. In the method for producing the foamed beads in Comparative Example 1-2, the resin B supplied to the extruder is changed from the polypropylene resin B1-1 to the polypropylene resin B5, and the temperature in the container during foaming is changed to 164° C., and the method for producing the foamed beads is substantially the same as the method for producing the foamed beads of Example 1-4.
[0365] (Comparative Examples 1-3)
[0366] As shown in Table 5, the foaming layer of the foamed beads of Comparative Example 1-3 does not contain the resin composition A, but is composed of the resin B1-1 and the resin B1-5. The method for producing the foamed beads of Comparative Example 1-3 is as shown in Table 5, except that the resin composition composed of the resin B1-1 and the resin B1-5 is used to make the resin beads instead of the resin composition containing the resin composition A and the resin B, and is substantially the same as the method for producing the foamed beads of Example 1-1.
[0367] (Example 1-8)
[0368] As shown in Table 6, the bulk density of the foamed particles of Examples 1-8 is 27 kg / m 3 , except that the foamed beads of Example 1-1 have substantially the same structure. The method for producing the foamed beads of Example 1-8 is substantially the same as the method for producing the foamed beads of Example 1-1 except that the temperature in the container during foaming is changed to 155.5°C and the pressure in the container during foaming is changed to 2.8 MPa (G).
[0369] (Examples 1-9)
[0370] As shown in Table 7, the foamed beads of Example 1-9 have substantially the same structure as the foamed beads of Example 1-4 except that the resin composition A1-2 is used instead of the resin composition A1-1 as the resin composition A. In the method for producing the foamed beads in Example 1-9, the resin composition A supplied to the extruder is changed from the resin composition A1-1 to the resin composition A1-2, and the method for producing the foamed beads is substantially the same as the method for producing the foamed beads of Example 1-4.
[0371] (Reference Example 1-1)
[0372] The foaming layer of the foamed beads of Reference Example 1-1 does not contain the resin composition A, but is composed of the resin B. In the method for producing the foamed beads of Reference Example 1-1, the method is substantially the same as the method for producing the foamed beads of Example 1-1, except that the resin B1-1 is used instead of the resin composition containing the resin composition A and the resin B to produce the resin beads, and the temperature in the container during foaming is changed to 149.5°C.
[0373] (Reference Example 1-2)
[0374] The foamed layer of the foamed beads of Reference Example 1-2 does not contain the resin composition A, but is composed of the resin B. In the method for producing the foamed beads of Reference Example 1-2, the temperature in the container during foaming was changed to 147° C., and the pressure in the container was changed to 4.0 MPa (G), and the method is substantially the same as the method for producing the foamed beads of Reference Example 1-1.
[0375] (Examples 1-10)
[0376] The foamed particles of Examples 1-10 have a foamed core layer composed of a polypropylene resin composition and a fusion layer covering the foamed core layer. The polypropylene resin composition constituting the foamed core layer comprises a polypropylene resin and a rubber-like body G comprising an ethylene-propylene rubber, and the rubber-like body G is dispersed in the polypropylene resin. When the foamed particles of Examples 1-10 are prepared, first, a co-extrusion device having an extruder for forming a core layer, an extruder for forming a fusion layer, and a co-extrusion die connected to the two extruders is used, and the composite extruded from the co-extrusion device is cut by a wire cutting method to prepare multi-layer resin particles having a fusion layer.
[0377] Specifically, resin composition A1-1, resin B1-1, bubble regulator and carbon black are supplied to the extruder for core layer formation, and a molten mixture of resin composition A1-1 and resin B1-1 for core layer formation is formed in the extruder. In addition, the ratio of resin composition A1-1 and resin B1-1 in the molten mixture for core layer formation is set to resin composition A1-1: resin B1-1 = 15: 85. As a bubble regulator, zinc borate is used. Relative to the total of 100% by mass of resin composition A1-1 and resin B1-1, the addition amount of zinc borate is 0.05% by mass. Relative to the total of 100% by mass of resin composition A1-1 and resin B1-1, the addition amount of carbon black is 2.8% by mass.
[0378] In addition, a polypropylene resin (specifically, a propylene-ethylene-butene random copolymer, melting point 122° C., melt mass flow rate 6 g / 10 minutes) and carbon black were supplied to an extruder for forming a welding layer, and a molten mixture for forming a welding layer was formed in the extruder. In addition, the amount of carbon black added to the molten mixture for forming a welding layer was 2.8% by mass relative to 100% by mass of the polypropylene resin.
[0379] By converging these molten mixtures in a die head, a composite body consisting of a non-foamed cylindrical core layer and a non-foamed fusion layer covering the side surface of the core layer is formed, and then co-extruded from the die head into a strand. After the strand-like composite body is pulled out and cooled, it is cut into appropriate lengths using a granulator, thereby obtaining columnar resin particles (i.e., multilayer resin particles) having a core layer and a fusion layer covering the outer side surface of the core layer. The proportion of the fusion layer in the multilayer resin particles is 3% by mass.
[0380] Next, the multilayered resin particles were foamed by a direct foaming method. Specifically, first, 100 kg of the multilayered resin particles were put into a container with an internal volume of 400 L together with 220 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.004 parts by mass of sodium alkylbenzene sulfonate as a dispersing aid, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the multilayered resin particles, and the multilayered resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0381] Afterwards, carbon dioxide as a foaming agent is supplied into the sealed container while stirring the inside of the container, so that the temperature in the container rises to 158.2°C. The pressure in the container at this time is 1.6MPa(G). Afterwards, the temperature is maintained for 15 minutes, thereby impregnating the multilayer resin particles with the foaming agent. Afterwards, the container is opened and the contents are released under an atmospheric pressure atmosphere, thereby foaming the multilayer resin particles. The foamed particles thus obtained are dried for 24 hours in an atmosphere at a temperature of 23°C and a relative humidity of 50%. Thus, primary foamed particles having a foamed core layer formed by foaming a core layer and a non-foamed fusion layer covering the foamed core layer are obtained.
[0382] Next, the primary foamed particles are placed in a pressure tank as a pressure-resistant container, and the pressure tank is sealed. In this state, the pressure tank is pressurized with air as an inorganic gas, so that the air is impregnated into the bubbles in a manner such that the pressure inside the bubbles of the primary foamed particles becomes 0.35 MPa (G). After the internal pressure is applied to the primary foamed particles, the primary foamed particles are taken out of the pressure tank and placed in a metal drum. Thereafter, steam is supplied to the primary foamed particles and heated at atmospheric pressure. Thus, the primary foamed particles are further foamed to obtain foamed particles (i.e., secondary foamed particles). Through the above, the foamed particles of Examples 1-10 are obtained. In addition, the proportion of the fusion layer in the foamed particles is 3% by mass.
[0383] (Example 1-11)
[0384] The foamed particles of Example 1-11 have a foamed core layer composed of a polypropylene resin composition and a fusion layer covering the foamed core layer. The polypropylene resin composition constituting the foamed core layer comprises a polypropylene resin and a rubber-like body G comprising an ethylene-propylene rubber, and the rubber-like body G is dispersed in the polypropylene resin. In addition, the foamed particles of Example 1-11 are cylindrical foamed particles having through holes that penetrate the interior in the axial direction. When making the foamed particles of Example 1-11, first, a co-extrusion device having an extruder for forming a core layer, an extruder for forming a fusion layer, and a co-extrusion die connected to the two extruders is used, and the composite extruded from the co-extrusion device is cut by a wire cutting method to make multilayer resin particles with a fusion layer. In addition, the co-extrusion die used in Example 1-11 has a mechanism that can form through holes in the core layer of the multilayer resin particles.
[0385] Specifically, resin composition A1-1, resin B1-1, bubble regulator and carbon black are supplied to the extruder for core layer formation, and a molten mixture of resin composition A1-1 and resin B1-1 for core layer formation is formed in the extruder. In addition, the mass ratio of resin composition A1-1 and resin B1-1 in the molten mixture for core layer formation is set to resin composition A1-1: resin B1-1 = 17: 83. As a bubble regulator, zinc borate is used. Relative to the total of 100% by mass of resin composition A1-1 and resin B1-1, the addition amount of zinc borate is 0.05% by mass. Relative to the total of 100% by mass of resin composition A1-1 and resin B1-1, the addition amount of carbon black is 2.8% by mass.
[0386] In addition, a polypropylene resin (specifically, a propylene-ethylene random copolymer, melting point 133° C., melt mass flow rate 24 g / 10 min) and carbon black were supplied to an extruder for forming a welding layer, and a molten mixture for forming a welding layer was formed in the extruder. The amount of carbon black added to the molten mixture for forming a welding layer was 2.8% by mass relative to 100% by mass of the polypropylene resin.
[0387] By converging these molten mixtures in a die head, a composite body consisting of a non-foamed cylindrical core layer and a non-foamed fusion layer covering the side surface of the core layer is formed, and then co-extruded from the die head into a strand. The strand-shaped composite body is pulled out and cooled, and then cut into appropriate lengths using a pelletizer, thereby obtaining a cylindrical multilayer resin pellet having a core layer with a through hole penetrating the interior in the axial direction and a fusion layer covering the outer side surface of the core layer. The proportion of the fusion layer in the multilayer resin pellet is 5% by mass.
[0388] Next, the multilayered resin particles were foamed by a direct foaming method. Specifically, first, 100 kg of the multilayered resin particles were put into a container with an internal volume of 400 L together with 220 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.004 parts by mass of sodium alkylbenzene sulfonate as a dispersing aid, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the multilayered resin particles, and the multilayered resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0389] Afterwards, carbon dioxide as a foaming agent is supplied into the sealed container while stirring the inside of the container, so that the temperature in the container rises to 159.3°C. The pressure in the container at this time is 1.5MPa(G). By maintaining this temperature for 15 minutes, the foaming agent is impregnated into the multilayer resin particles. Afterwards, the container is opened and the contents are released under atmospheric pressure, thereby foaming the multilayer resin particles. The foamed particles obtained in this way are dried for 24 hours in an atmosphere with a temperature of 23°C and a relative humidity of 50%. By the above, a cylindrical primary foamed particle having a foamed core layer with through holes formed by foaming a core layer and a non-foamed fusion layer covering the foamed core layer is obtained.
[0390] Next, the primary foaming particles are placed in a pressure tank as a pressure-resistant container, and the pressure tank is sealed. In this state, the pressure tank is pressurized using air as an inorganic gas, so that the air is impregnated in the bubbles in the primary foaming particles in a manner such that the pressure in the bubbles is 0.35MPa (G). After the internal pressure is applied to the primary foaming particles, the primary foaming particles are taken out of the pressure tank and placed in a metal drum. After that, steam is supplied to the primary foaming particles and heated at atmospheric pressure. By the above, the primary foaming particles are further foamed to obtain foaming particles (i.e., secondary foaming particles). By the above, the foaming particles of Examples 1-11 are obtained. In addition, the proportion of the fusion layer in the foaming particles is 5% by mass. In addition, the foaming particles have through holes that penetrate the interior in the axial direction, and the average pore size of the through holes is 0.69mm, and the ratio of the average pore size of the through holes to the average outer diameter of the foaming particles is 0.20.
[0391] In addition, the average pore size of the through holes is calculated as follows. First, 100 foamed particles are randomly selected, and these foamed particles are cut at the position where their cross-sectional area is the largest with a plane perpendicular to the axial direction, so that the cut surface of the foamed particles is exposed. Next, a photo of the cut surface of the foamed particles is taken, and image analysis is performed to measure the cross-sectional area (i.e., opening area) of the through holes in the cut surface. Then, the diameter of an imaginary perfect circle having the same area as the cross-sectional area of the through holes is calculated, and this value is used as the pore size of the through holes in each foamed particle. The above operation is performed on 100 foamed particles, and the arithmetic mean of the pore size of the through holes obtained is used as the average pore size of the through holes of the foamed particles.
[0392] In addition, the average outer diameter of the foamed particles is calculated as follows. First, 100 foamed particles are randomly selected, and these foamed particles are cut at the position where their cross-sectional area is the largest with a plane perpendicular to the axial direction, so that the cut surface of the foamed particles is exposed. Next, a photo of the cut surface of the foamed particles is taken, and image analysis is performed to measure the cross-sectional area of the foamed particles containing the through holes (that is, the area of the area surrounded by the outer peripheral edge of the foamed particles in the cut surface). Then, the diameter of an imaginary perfect circle having the same area as the cross-sectional area of the foamed particles is calculated, and this value is used as the outer diameter of each foamed particle. The above operation is performed on 100 foamed particles, and the arithmetic mean of the outer diameters of the obtained foamed particles is used as the average outer diameter of the foamed particles.
[0393] Tables 3 to 7 show various properties of the resin particles, foamed particles, and molded articles obtained by in-mold molding of the foamed particles in Examples 1-1 to 1-9 and Comparative Examples 1-1 to 1-3 obtained above.
[0394] In addition, the bulk density of the foamed particles of Examples 1-10 is 27 kg / m 3 , D in foamed particles sol -A insol The amount of foamed particles is 0.03 g per 1 g, the melting point Tm is 148°C, the difference between the melting point Tm and the crystallization temperature Tc is 35°C, and the melting heat of the high temperature peak is 20 J / g. The moldable range of the foamed particles of Examples 1-10 is 0.27-0.31 MPa (G). The density of the molded body of Examples 1-10 is 30 kg / m 3 , 5% compression strength is 220kPa, 50% compression strength is 420kPa, and the compression strength ratio is 0.52.
[0395] The bulk density of the foamed particles of Examples 1-11 is 33 kg / m 3 , D in foamed particles sol -A insol The amount of foamed particles is 0.03 g per 1 g, the melting point Tm is 148°C, the difference between the melting point Tm and the crystallization temperature Tc is 35°C, and the melting heat of the high temperature peak is 22 J / g. The moldable range of the foamed particles of Examples 1-11 is 0.30-0.34 MPa (G). The density of the molded body of Examples 1-11 is 35 kg / m 3 , 5% compression strength is 140kPa, 50% compression strength is 270kPa, and the compression strength ratio is 0.52.
[0396] The foamed beads of Reference Example 1-1 did not contain a rubber-like body composed of ethylene-propylene rubber. The bulk density of the foamed beads of Reference Example 1-1 was 45 kg / m 3, the average bubble diameter is 110μm, the independent bubble rate is 96%, the melting point Tm is 143℃, the difference Tm-Tc is 40℃, the ash content is 0% by mass, the melt mass flow rate is 9g / 10min, the bending elastic modulus is 950MPa, the peak temperature Th of the high temperature peak is 156℃, and the melting heat of the high temperature peak is 16J / g. The formable range of the foamed particles of Reference Example 1-1 is 0.28-0.32MPa(G). The density of the molded body of Reference Example 1-1 is 50kg / m 3 , the independent bubble rate is 86%, the 5% compression strength is 210kPa, the 50% compression strength is 425kPa, and the compression strength ratio is 0.49.
[0397] The foamed beads of Reference Example 1-2 did not contain a rubber-like body containing ethylene-propylene rubber. The bulk density of the foamed beads of Reference Example 1-2 was 27 kg / m 3 , the average bubble diameter is 150μm, the independent bubble rate is 96%, the melting point Tm is 143℃, the difference Tm-Tc is 40℃, the ash content is 0% by mass, the melt mass flow rate is 9g / 10min, the bending elastic modulus is 950MPa, the peak temperature Th of the high temperature peak is 156℃, and the melting heat of the high temperature peak is 16J / g. The formable range of the foamed particles of Reference Example 1-2 is 0.28-0.32MPa(G). The density of the molded body of Reference Example 1-2 is 30kg / m 3 , the independent bubble rate is 85%, the 5% compression strength is 95kPa, the 50% compression strength is 240kPa, and the compression strength ratio is 0.40.
[0398] [Melting point Tm of foamed particles and melting point Tmr of resin particles]
[0399] The melting point Tm of the foamed beads and the melting point Tmr of the resin beads are determined by using the foamed beads or the resin beads instead of the resin composition A. A The determination method is the same.
[0400] [Crystallization temperature Tc of foamed particles and crystallization temperature Tcr of resin particles]
[0401] Based on JIS K7121-1987, a heat flux differential scanning calorimeter is used to measure the crystallization temperature Tc of the foamed particles. More specifically, first, the foamed particles are heated from 23°C to 230°C at a heating rate of 10°C / min, and the temperature of 230°C is maintained for 10 minutes. Thereafter, the particles are cooled from 230°C to 30°C at a cooling rate of 10°C / min, thereby obtaining a DSC curve. In addition, the flow rate of nitrogen in the measurement environment is set to 30 mL per minute. The vertex temperature of the crystallization peak in the DSC curve is taken as the crystallization temperature Tc of the foamed particles. In addition, when multiple crystallization peaks appear in the DSC curve, the vertex temperature of the crystallization peak with the highest peak height is taken as the crystallization temperature Tc of the foamed particles.
[0402] The method for measuring the crystallization temperature Tcr of the resin particles is the same as the method for measuring the crystallization temperature Tc of the foamed beads described above, except that the resin particles are used instead of the foamed beads.
[0403] [Bulk density of foamed particles]
[0404] The foamed beads were left to stand for more than 24 hours in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1 atm to adjust the state of the foamed beads. The bulk volume thus obtained was about 500 cm 3 Fill the measuring cylinder with the foamed particles and tap the ground with the bottom of the measuring cylinder several times to stabilize the filling height of the foamed particle group in the measuring cylinder. Then, read the exact bulk volume of the foamed particle group from the scale of the measuring cylinder (unit: L). Then, convert the value obtained by dividing the mass of the foamed particle group in the measuring cylinder (unit: g) by the above-mentioned bulk volume to calculate the bulk density of the foamed particles (unit: kg / m 3 ).
[0405] [Average bubble diameter of foamed particles]
[0406] The foamed particles are cut into approximately two equal parts. Then, an enlarged photograph is obtained in such a way that the exposed cut surface is completely within the field of view. On the obtained enlarged photograph, four line segments are drawn from the outermost surface of the foamed particles through the central part to the outermost surface of the opposite side in such a way that the angles formed by adjacent line segments are equal (that is, in such a way that the angles formed by adjacent line segments are 45°). The value obtained by dividing the total length of the four line segments obtained in this way by the total number of bubbles intersecting the line segments is taken as the bubble diameter of each foamed particle.
[0407] The above operation is performed on ten or more foamed beads randomly selected, and the value obtained by arithmetic averaging the cell diameters of the foamed beads obtained for the respective foamed beads is defined as the average cell diameter of the foamed beads.
[0408] [Independent cell ratio of foamed particles]
[0409] Based on ASTM-D2856-70 step C, the closed cell ratio of the foamed particles was measured using an air comparison pycnometer. Specifically, first, the state-adjusted bulk volume was about 20 cm 3 The foamed particles are used as the measurement sample, and the measurement sample is sunk into a measuring cylinder filled with ethanol. The apparent volume Va of the measurement sample is measured according to the amount of liquid level rise at this time. After the measurement sample after the apparent volume Va is measured is fully dried, the true volume value Vx of the measurement sample measured by an air comparison pycnometer ("Beckman Model 1000 Air Comparison Pycnometer" manufactured by Tokyo Science Co., Ltd.) is measured according to step C described in ASTM-D2856-70. Then, using these volume values Va and Vx, the independent bubble rate (unit: %) of the measurement sample is calculated based on the following formula (1). The measurement sample is changed and the operation is performed more than five times, and the arithmetic mean (N=5) of the independent bubble rates in the five measurement samples is taken as the independent bubble rate (unit: %) of the foamed particles.
[0410] Closed cell ratio = (Vx-W / ρ) × 100 / (Va-W / ρ)…(1)
[0411] The symbols in the above formula (1) have the following meanings.
[0412] Vx: The true volume of the sample for measurement measured by the above method, that is, the sum of the volume of the resin constituting the foamed beads and the total volume of the cells of the closed cell portion in the foamed beads (unit: cm 3 )
[0413] Va: The apparent volume of the sample for measurement measured by the amount of liquid level rise when the sample for measurement is sunk into a graduated cylinder filled with ethanol (unit: cm 3 )
[0414] W: Mass of the sample to be measured (unit: g)
[0415] ρ: Density of the resin constituting the foamed particles (unit: g / cm 3 )
[0416] 〔D in foamed particles sol -A insol And D in the resin particles sol -A insol 〕
[0417] D in foamed particles sol -A insol, that is, the amount of components that are soluble in n-decane and insoluble in acetone is determined by the following method. Specifically, first, accurately weigh about 5 g of foamed particles as a sample. Add the sample to 200 ml of n-decane and heat to dissolve at 145°C for 30 minutes. Next, cool the obtained n-decane solution to 23°C over 2 hours and leave it at 23°C for 30 minutes. In this way, the components insoluble in n-decane in the n-decane solution are precipitated. Thereafter, the n-decane solution is filtered to filter out the precipitate to obtain a n-decane extract containing n-decane-soluble components. Add the n-decane extract to about 3 times the amount of acetone relative to the n-decane extract, and leave it at 23°C for 18 hours to dissolve the acetone-insoluble components in the n-decane extract (that is, D in the foamed particles). sol -A insol ) is precipitated. The precipitate is filtered and dried, and the mass of the precipitate is measured. The D of each 1 g of foamed particles contained in the foamed particles is calculated by dividing the mass of the precipitate measured in this way (unit: g) by the mass of the sample (unit: g). sol -A insol Amount (unit: g).
[0418] In addition, the D sol -A insol The method for determining the amount of D in the foamed particles is to use resin particles instead of foamed particles to calculate the amount per 1g of resin particles. sol -A insol The method for determining the amount is the same.
[0419] [Form of foamed particles and form of resin particles]
[0420] The morphology of the foamed particles was observed by the following method. First, the foamed particles were cut through their center, and a sample for observation in which a cross section of the center of the foamed particles was exposed was prepared. Next, the sample for observation was embedded in an epoxy resin, and after electron staining with ruthenium tetroxide, a slice containing the center of the foamed particles was made from the sample using an ultramicrotome or the like. The slice was placed on a microgrid of a transmission electron microscope ("JEM-1040Flash" manufactured by JEOL Ltd.), observed at a magnification of 5000 times, and a cross-sectional photograph (i.e., TEM photograph) of the foamed particles was taken.
[0421] The morphology of the phase of the polypropylene resin and the phase of the rubber-like body containing the ethylene-propylene rubber in the bubble film of the foaming layer was visually observed from the cross-sectional photograph. Figure 4 The cross-sectional photographs of the foamed particles of Examples 1-4 are shown in FIG. Figure 4As shown, it was confirmed that the cell membrane 11 of the foamed beads 1 had a morphology in which microdomains D containing rubbery bodies G of ethylene-propylene rubber were dispersed in a polypropylene resin matrix M. In addition, based on the cross-sectional photograph obtained in this way, the average diameter of the rubbery bodies in the morphology of the foamed beads was calculated by the same method as the method for calculating the average diameter of the rubbery bodies in the morphology of the resin composition A.
[0422] The method for observing the morphology of the resin particles is the same as the method for observing the morphology of the foamed particles described above, except that the resin particles are used instead of the foamed particles. Figure 5 The cross-sectional photographs of the resin particles of Examples 1-4 are shown in FIG. Figure 5 As shown, it was confirmed that the resin particles 10 had a morphology in which microdomains D including rubbery bodies G of ethylene-propylene rubber were dispersed in a polypropylene resin matrix M. In addition, based on the cross-sectional photograph obtained in this way, the average diameter of the rubbery bodies in the morphology of the resin particles was calculated by the same method as the method for calculating the average diameter of the rubbery bodies in the morphology of the resin composition A.
[0423] 〔Ash content of resin particles and foamed particles〕
[0424] The method for measuring the ash content of the resin particles and the ash content of the foamed particles is the same as the method for measuring the ash content of the resin composition A described above, except that the resin particles or the foamed particles are used instead of the resin composition A.
[0425] [Melt mass flow rate of the resin composition constituting the foamed beads]
[0426] The foamed beads were defoamed by hot pressing at 180° C. for 3 minutes to prepare a sheet made of a resin composition constituting the foamed beads. The melt mass flow rate was measured at a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K7210-1:2014 using a pelletized sample obtained by cutting the sheet.
[0427] [Flexural modulus of the resin composition constituting the foamed beads]
[0428] The foamed beads were hot pressed at 180°C to prepare a sheet with a thickness of 4 mm, from which a test piece with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm was cut. The bending elastic modulus of the test piece was determined in accordance with JIS K7171: 2008. In addition, the radius R1 of the indenter and the radius R2 of the support were both 5 mm, the distance between the fulcrums was 64 mm, and the test speed was 2 mm / min.
[0429] 〔Resin-specific peak and high temperature peak〕
[0430] The vertex temperature and melting heat of the high temperature peak are obtained from the DSC curve obtained by differential scanning calorimetry (DSC) according to JIS K7122-1987. Specifically, first, about 3 mg of foamed particles are used as a sample, and the sample is heated from 23°C to 230°C at a heating rate of 10°C / min, and differential scanning calorimetry is performed to obtain a DSC curve. In addition, the flow rate of nitrogen in the measurement environment is set to 30 mL per minute. Based on the DSC curve, the vertex temperature T of the resin intrinsic peak ΔH1 is obtained. l And the peak temperature T of the high temperature peak ΔH2 h In addition, in Tables 3 to 7, the "difference in vertex temperature T h -T l The column records the peak temperature T of the high temperature peak ΔH2. h Subtract the peak temperature T of the resin intrinsic peak ΔH1 l The value obtained.
[0431] Next, a straight line L1 is drawn, which connects point α corresponding to 80°C and point β corresponding to the melting end temperature T of the foamed beads on the DSC curve. Furthermore, a straight line L2 is drawn, which passes through the maximum point γ existing between the resin-specific peak ΔH1 and the high-temperature peak ΔH2 and is parallel to the vertical axis of the graph, and the resin-specific peak ΔH1 and the high-temperature peak ΔH2 are divided by the straight line L2.
[0432] Then, the melting heat of the resin intrinsic peak ΔH1 is calculated based on the area of the portion surrounded by the straight line L1 and the straight line L2 constituting the resin intrinsic peak ΔH1 in the DSC curve. In addition, the melting heat of the high temperature peak ΔH2 is calculated based on the area of the portion surrounded by the straight line L1 and the straight line L2 constituting the high temperature peak ΔH2 in the DSC curve.
[0433] The operation is performed more than three times using different samples, and the arithmetic mean of the heat of fusion of the resin inherent peak ΔH1 obtained in each measurement is taken as the heat of fusion of the resin inherent peak ΔH1 of the foamed particles, and the arithmetic mean of the heat of fusion of the high temperature peak ΔH2 is taken as the heat of fusion of the high temperature peak ΔH2 of the foamed particles.
[0434] 〔Density of molded body〕
[0435] The foamed bead molded body is obtained by in-mold molding at the lowest molding pressure in the above-mentioned moldable range. The density of the molded body (unit: kg / m2) is calculated by converting the mass (unit: g) of the foamed bead molded body into a volume (unit: L) obtained from the outer dimensions of the molded body. 3 ).
[0436] 〔Formable range〕
[0437] In the evaluation of the formable range, the forming pressure during formal heating is changed by 0.01 MPa at a time from 0.26 MPa (G) to 0.42 MPa (G) to perform in-mold forming, thereby producing a molded body, and the formable range is determined based on the surface properties, weldability and recovery properties of the obtained molded body.
[0438] The manufacturing method of the molded body is as follows. First, the foamed particles are placed in a pressure-resistant container, and the pressure-resistant container is pressurized with air so that the air is impregnated into the foamed particles, and an internal pressure of 0.10 MPa (G) is given to the foamed particles. Next, the foamed particles given the internal pressure are filled into a forming mold by a crack filling method. In this example, a forming mold having a cavity capable of forming a flat-plate-shaped molded body of 250 mm in length, 200 mm in width, and 50 mm in thickness is used. In the crack filling, after the foamed particles are filled into the forming mold with a crack gap of 5 mm (i.e., a crack amount of 10%) opened in the thickness direction of the molded body, the forming mold is completely closed, thereby mechanically compressing the foamed particles in the forming mold.
[0439] Next, steam is supplied to the forming mold for in-mold forming. In in-mold forming, first, steam is supplied to the forming mold for 5 seconds with the discharge valve of the forming mold open for preheating. Next, the discharge valve is closed, and steam is supplied from one surface side of the forming mold until a pressure is reached that is 0.08MPa(G) lower than the forming pressure during formal heating, and the first one-side heating is performed. Next, steam is supplied from the other surface side of the forming mold until a pressure is reached that is 0.04MPa(G) lower than the forming pressure during formal heating, and the second one-side heating is performed. Thereafter, steam is supplied from both sides of the forming mold until the forming pressure during formal heating is reached, and formal heating is performed. After the formal heating is completed, the pressure in the forming mold is released, and the formed body is cooled in the forming mold until the surface pressure caused by the foaming force of the formed body becomes 0.04MPa(G).
[0440] After that, the formed body taken out from the forming mold is placed in an oven at 80°C for 12 hours to perform a curing process. After the curing process, the formed body is placed under the conditions of a relative humidity of 50%, 23°C, and 1atm for 24 hours to adjust the state of the formed body. The surface properties, weldability, and recovery properties of the formed body after state adjustment are evaluated, and the range of the forming pressure that is qualified in any item of the evaluation criteria described later (that is, the forming pressure that can obtain a qualified product) is taken as the formable range. The larger the formable range, the better the in-mold formability can be judged. In addition, the lower the formable forming pressure, the less steam can be used for in-mold forming, so it can be judged as excellent productivity.
[0441] The evaluation method of surface properties, weldability, and recovery properties in the evaluation of the formable range is as follows.
[0442] Surface
[0443] A 100 mm × 100 mm square is drawn in the center of one surface of the molded body in the thickness direction, and then a diagonal line is drawn from any corner of the square. Then, the number of voids existing on the diagonal line, that is, the number of voids with a size of 1 mm × 1 mm or more formed in the gaps between the foamed particles is counted. Then, if the number of voids is two or less, it is judged to be qualified, and if it is three or more, it is judged to be unqualified.
[0444] Weldability
[0445] The molded body is broken in a manner that is roughly equally divided in the long side direction. By visually observing more than 100 foamed particles randomly selected from the foamed particles exposed on the fracture surface, it is determined whether the foamed particles are broken inside the particles (i.e., foamed particles with material damage) or foamed particles are broken at the interface between the foamed particles. Then, the value expressing the ratio of the number of foamed particles observed to be broken inside the particles to the total number of foamed particles (i.e., the material damage rate) is calculated as a percentage, and this value is used as the welding rate. Then, the case where the welding rate is 80% or more is judged as qualified, and the case where it is less than 80% is judged as unqualified.
[0446] Restoration
[0447] When the molded body is viewed from the top in the thickness direction, the thickness of the molded body at four locations 10 mm inside from each vertex of the surface surrounded by the 250 mm vertical side and the 200 mm horizontal side to the center of the surface and the thickness of the molded body at the center of the surface are measured. Next, the ratio of the thickness of the thinnest portion to the thickness of the thickest portion among the measured portions is calculated (unit: %). If the thickness ratio thus obtained is 95% or more, it is judged to be acceptable, and if it is less than 95%, it is judged to be unacceptable.
[0448] [Closed cell ratio of molded body]
[0449] The mold was formed at the lowest molding pressure in the above-mentioned moldable range to obtain a molded body. A test body with a length of 25 mm × a width of 25 mm × a height of 30 mm was cut out from the center of the molded body, and the geometric volume Va (unit: cm 3), that is, the product of the longitudinal dimension (unit: cm), the lateral dimension (unit: cm) and the height dimension (unit: cm). Next, according to step C described in ASTM-D2856-70, an air comparison pycnometer (specifically, "Beckman Model 1000 Air Comparison Pycnometer" manufactured by Tokyo Science Co., Ltd.) is used to measure the true volume value Vx of the test body. In addition, the true volume value Vx obtained by the air comparison pycnometer is the sum of the volume of the resin constituting the measurement sample and the total volume of the bubbles in the independent bubble part of the measurement sample (unit: cm 3 ).
[0450] The mass W (unit: g) of the test piece obtained above and the density ρ (unit: g / cm 3 ), the geometric volume Va of the test body obtained by the above method and the true volume Vx of the test body are used to calculate the closed bubble ratio (unit: %) of the test body by the following formula (2).
[0451] Closed cell ratio = (Vx-W / ρ) × 100 / (Va-W / ρ)…(2)
[0452] The above operation was performed on five test pieces, and the closed cell ratio of each test piece was calculated. Then, the arithmetic mean of the closed cell ratios of the five test pieces was taken as the closed cell ratio of the molded body.
[0453] [5% compression strength and 50% compression strength of molded body]
[0454] In-mold forming is performed at the lowest forming pressure in the above-mentioned formable range to obtain a formed body. A rectangular test piece with a length of 50 mm, a width of 50 mm, and a thickness of 25 mm is collected from the center of the formed body. Based on the method specified in JIS K7220:2006, a compression test of the test piece is performed at a compression speed of 10 mm / min to obtain a stress-strain curve. In addition, the compression test is carried out in a laboratory at 23°C. Based on the stress-strain curve, the 5% deformation compressive stress and 50% deformation compressive stress of the test piece are calculated, and the values are used as the 5% compressive strength and 50% compressive strength of the formed body. In addition, the value obtained by dividing the value of the 50% compressive strength by the density of the formed body is recorded in the "50% compressive strength / density" column of Tables 3 to 7 (unit: kPa / (kg / m 3 )), in the column of "Compression Strength Ratio", the ratio of 5% compression strength to 50% compression strength, that is, the value obtained by dividing the 5% compression strength by the 50% compression strength is recorded.
[0455] Table 3
[0456] (Table 3)
[0457]
[0458] Table 4
[0459] (Table 4)
[0460]
[0461] Table 5
[0462] (Table 5)
[0463]
[0464] Table 6
[0465] (Table 6)
[0466]
[0467] Table 7
[0468] (Table 7)
[0469]
[0470] As shown in Tables 3 and 4, the polypropylene resin composition constituting the foamed layer in the foamed beads of Examples 1-1 to 1-7 includes a polypropylene resin and a rubber-like body including an ethylene-propylene rubber, and the rubber-like body is dispersed in the polypropylene resin. In addition, the melting point Tm of the foamed beads is within the specific range. Therefore, the foamed beads of Examples 1-1 to 1-7 have good in-mold formability. In addition, D sol -A insol The amount and the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc are both within the specific range, so the molded body composed of these foamed particles has a low increase rate of compressive stress associated with an increase in compressive strain and has excellent impact absorption.
[0471] On the other hand, the melting point Tm of the expanded beads of Comparative Example 1-1 deviates from the specific range as shown in Table 5. Therefore, the expanded beads of Comparative Example 1-1 cannot form a good molded article.
[0472] The melting point Tm of the expanded beads of Comparative Example 1-2 deviates from the specific range. Therefore, the expanded beads of Comparative Example 1-2 cannot form a good molded article.
[0473] The foamed particles of Comparative Examples 1-3 do not contain a rubber-like body containing ethylene-propylene rubber. The foamed particles of Comparative Examples 1-3 have a narrower range of molding pressures that can produce good molded bodies than the foamed particles of the Examples. In addition, the compression strength ratio of the molded body composed of the foamed particles of Comparative Examples 1-3 is smaller than the compression strength ratio of the molded body composed of the foamed particles of the Examples, and the rate of increase of the compressive stress accompanying the increase of the compressive strain is high.
[0474] In addition, from the comparison of Examples 1-1 to 1-7 with Reference Example 1-1, and from the comparison of Example 1-8 with Reference Example 1-2, it can be understood that the foamed particles containing a rubber-like body including ethylene propylene rubber can reduce the rate of increase of compressive stress associated with the increase in compressive strain of the molded body compared to foamed particles not containing a rubber-like body.
[0475] As shown in Table 7, it is understood that the same effect can be obtained also in the foamed beads of Examples 1 to 9 in which the foamed layer contains the polypropylene resin composition A derived from an automobile member and containing an ethylene-propylene rubber.
[0476] In addition, as shown in Examples 1-10 and 1-11, it can be understood that this effect can also be obtained in foamed beads having a fusion layer and foamed beads having through holes.
[0477] <Implementation Method 2>
[0478] (Polypropylene resin composition A)
[0479] Table 8 shows the properties of the polypropylene resin composition A used in the manufacture of the foamed particles of this embodiment. The resin composition A2-1 shown in Table 8 is a recycled polypropylene with the polypropylene resin composition a1 recovered from ASR as the main component (more specifically, the resin composition A2-1 is "PLC-A02" manufactured by Planic Co., Ltd.). The shape of the resin composition A2-1 is a cylindrical pellet, the average length in the height direction of the pellet (the average length in the extrusion direction during pellet manufacturing) is 3 mm, the diameter of the pellet is 3 mm, and the average mass of the pellet is 16 mg. In addition, the resin composition A2-1 contains an inorganic substance with talc as the main component. The morphology of the resin composition A2-1 used in this example was observed by the method described later, and the results showed that the resin composition A2-1 has a morphology with polypropylene as the matrix and a rubber-like body containing the ethylene propylene rubber as the micro-region.
[0480] Table 8
[0481] (Table 8) Polypropylene resin composition A
[0482] unit A2-1 density <![CDATA[kg / m 3 ]]> 930 Ethylene content quality% 26 Ash content quality% 5 <![CDATA[Melting point Tm A > ℃ 164 <![CDATA[Melt mass flow rate MFR A > g / 10 minutes 26 <![CDATA[Flexural modulus M A > MPa 950 23℃ n-decane soluble components quality% 12 <![CDATA[D sol -A insol ]]> g 0.12
[0483] The methods for measuring the physical property values of the polypropylene resin composition A shown in Table 8 are the same as the methods for measuring the physical property values of the polypropylene resin composition A in the first embodiment.
[0484] (Polypropylene resin B)
[0485] Table 9 shows the properties and the like of the polypropylene resin B used for producing the foamed beads of the present embodiment.
[0486]
[0487] The methods for measuring the physical property values of the polypropylene resin B shown in Table 9 are the same as the methods for measuring the physical property values of the polypropylene resin B in the first embodiment.
[0488] Next, the structure and production method of the foamed beads of this embodiment will be described.
[0489] (Example 2-1)
[0490] The resin composition A2-1, the polypropylene resin B2-1 and the bubble regulator were put into an extruder at a mass ratio shown in Table 10 to form a mixture containing the resin composition A2-1 and the molten state of the resin B2-1 in the extruder. In addition, zinc borate was used as a bubble regulator. The addition amount of zinc borate was 500 mass ppm relative to the total of the resin composition A2-1 and the resin B2-1.
[0491] Then, the molten mixture is extruded into a strand from a small hole of a die head provided on the downstream side of the extruder. The strand-shaped extrudate is pulled out and cooled, and then cut into appropriate lengths using a pelletizer to obtain resin pellets.
[0492] The resin particles thus obtained were foamed by a direct foaming method. Specifically, first, 1 kg of the resin particles were put into a container with an internal volume of 5 L together with 3 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.02 parts by mass of sodium alkylbenzene sulfonate as a dispersing aid, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the resin particles, and the resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0493] After that, carbon dioxide as a foaming agent is supplied into the sealed container while stirring the container, so that the temperature in the container rises to 156.2°C. The pressure in the container at this time is 2.1MPa(G). After that, the temperature in the container is maintained for 15 minutes, thereby impregnating the foaming agent into the resin particles. After that, the container is opened and the contents are released under atmospheric pressure, thereby foaming the resin particles. The foamed particles are dried in an atmosphere of a temperature of 23°C and a relative humidity of 50% for 24 hours. Through the above, the foamed particles of Example 2-1 are obtained.
[0494] (Examples 2-2 to 2-3)
[0495] The methods for producing the foamed beads of Examples 2-2 to 2-3 were substantially the same as the method for producing the foamed beads of Example 2-1, except that the mass ratio of the resin composition A to the resin B and the foaming conditions were changed as shown in Table 10.
[0496] (Examples 2-4 to 2-5)
[0497] The methods for producing foamed beads of Examples 2-4 to 2-5 were substantially the same as the method for producing foamed beads of Example 2-1, except that the type of resin B, the mass ratio of resin composition A to resin B, and foaming conditions were changed as shown in Tables 10 and 11.
[0498] (Example 2-6)
[0499] The method for producing the foamed beads of Example 2-6 was substantially the same as the method for producing the foamed beads of Example 2-1, except that the mass ratio of the resin composition A to the resin B and the foaming conditions were changed as shown in Table 11.
[0500] (Example 2-7)
[0501] The method for producing the foamed beads of Example 2-7 was substantially the same as the method for producing the foamed beads of Example 2-3, except that the type of resin B and the foaming conditions were changed as shown in Table 11.
[0502] (Example 2-8)
[0503] The method for producing the expanded beads of Example 2-8 was substantially the same as the method for producing the expanded beads of Example 2-1, except that the foaming conditions were changed as shown in Table 11.
[0504] (Comparative Examples 2-1 to 2-2)
[0505] As shown in Table 12, the foamed beads of Comparative Examples 2-1 and 2-2 do not contain resin B, but are composed of resin composition A2-1. The manufacturing method of the foamed beads of these comparative examples is substantially the same as the manufacturing method of the foamed beads of Example 2-1, except that resin B is not used but only resin composition A2-1 is used, and the foaming conditions are changed as shown in Table 12.
[0506] (Comparative Example 2-3)
[0507] The method for producing the foamed beads of Comparative Example 2-3 was substantially the same as the method for producing the foamed beads of Example 2-3, except that the type of resin B and the foaming conditions were changed as shown in Table 12.
[0508] (Reference Example 2-1)
[0509] The method for producing foamed beads of Reference Example 2-1 is substantially the same as the method for producing foamed beads of Example 2-3, except that a polypropylene resin B2-6 not containing ethylene-propylene rubber is used instead of resin composition A2-1 and the foaming conditions are changed as shown in Table 12.
[0510] The resin particles, foamed particles, and molded articles formed by in-mold molding of the foamed particles thus obtained were used to evaluate the evaluation items shown in Tables 10 to 12. The evaluation methods for the items that were not evaluated in Embodiment 1 among these evaluation items are shown below. In addition, among the evaluation items evaluated in the embodiments after this embodiment, the evaluation methods for the same evaluation items as those evaluated in the previous embodiments are the same as those in the previous embodiments.
[0511] 〔Ash content of resin particles and foamed particles〕
[0512] The method for measuring the ash content of the resin particles and the ash content of the foamed particles is the same as the method for measuring the ash content of the resin composition A described above, except that the resin particles or the foamed particles are used instead of the resin composition A).
[0513] [Apparent density of foamed particles]
[0514] The foamed particle group was left to stand for 1 day in an environment with a relative humidity of 50%, a temperature of 23°C, and an air pressure of 1 atm to adjust the state of the foamed particles. After measuring the mass (unit: g) of the foamed particle group, a metal mesh was used to sink it into a measuring cylinder filled with water at 23°C, and the volume (unit: L) of the foamed particle group was calculated based on the amount of water surface rise. After that, the value obtained by dividing the mass of the foamed particle group by the volume of the foamed particle group was converted into units, thereby calculating the apparent density of the foamed particles (unit: kg / m 3 ).
[0515] [Temperature, peak height and full width at half maximum of the endothermic peak]
[0516] By the above method, the top temperature Ta, peak height ha, and half-maximum full width wa of the first endothermic peak Pa and the top temperature Tb, peak height hb, and half-maximum full width wb of the second endothermic peak Pb were measured. In addition, Tables 10 to 12 show the value of the ratio hb / ha of the peak height hb of the second endothermic peak Pb to the peak height ha of the first endothermic peak Pa calculated based on the height of each endothermic peak, the difference in top temperature Tb-Ta calculated based on the top temperature of each endothermic peak, and the half-maximum full width of each endothermic peak.
[0517] 〔Heat of fusion of endothermic peak〕
[0518] First, differential scanning calorimetry is performed under the same conditions as those for measuring the peak temperature of each endothermic peak, thereby obtaining a DSC curve. Figure 1 As shown, a straight line L1 is drawn, which connects a point α corresponding to 80° C. and a point β corresponding to the melting end temperature T of the foamed beads on the DSC curve.
[0519] After the straight line L1 is drawn, a straight line L2 is drawn, which passes through the maximum point γ existing between the first endothermic peak Pa and the second endothermic peak Pb and is parallel to the vertical axis of the graph, and the first endothermic peak Pa and the second endothermic peak Pb are divided by the straight line L2. Then, based on the area of the portion constituting each endothermic peak in the DSC curve, the portion surrounded by the straight line L1 and the straight line L2, the heat of fusion of each endothermic peak is calculated. In addition, in Tables 10 to 12, the heat of fusion of each endothermic peak and the ratio of the heat of fusion Qa / Qb calculated based on these values and the sum of the heat of fusion Qa+Qb are described.
[0520] [Melting point of foamed particles, melting end temperature, and half-maximum width of the melting peak]
[0521] Using a heat flux differential scanning calorimeter (manufactured by SII Nano Technology Co., Ltd., model: DSC7020), the foamed particles are heated from 23°C to 200°C at a heating rate of 10°C / min. Thereafter, the foamed particles are cooled from 200°C to 23°C at a cooling rate of 10°C / min. After the cooling is completed, the foamed particles are heated again from 23°C to 200°C at a heating rate of 10°C / min (i.e., the second heating), and a DSC curve is obtained. Then, the top temperature of the melting peak that appears in the DSC curve in the second heating is taken as the melting point of the foamed particles, and the end point on the high temperature side of the melting peak, i.e., the temperature of the intersection of the melting peak in the second DSC curve and the baseline on the higher temperature side than the melting peak, is taken as the melting end temperature. In addition, the melting point of the foamed particles measured in this way is equal to the melting point Tm of the foamed particles measured by the measurement method of embodiment 1.
[0522] Furthermore, the full width at half maximum of the melting peak in the second DSC curve is calculated by the same method as the method for measuring the full width at half maximum wa of the first endothermic peak Pa.
[0523] [Moldable range, minimum molding pressure]
[0524] In the evaluation of the formable range and the minimum forming pressure, the forming pressure during formal heating is changed by 0.01 MPa at a time between 0.26 and 0.46 MPa (G) to perform in-mold forming, thereby making a foamed bead molded body, and the minimum forming pressure and the formable range are determined based on the surface properties, weldability and recovery of the obtained molded body. In addition, the specific manufacturing method of the foamed bead molded body is the same as that of embodiment 1.
[0525] The surface property, weldability and recovery of the foamed particle molded body after state adjustment are evaluated, and the range of the molding pressure (i.e., the molding pressure during the formal heating that can obtain a qualified product) that is qualified in any of the evaluation criteria described later is set as the moldable range, and the lowest molding pressure in the moldable range is set as the lowest molding pressure. In addition, the evaluation method of the surface property, weldability and recovery of the foamed particle molded body is the same as that of embodiment 1.
[0526] In addition, for Comparative Examples 2-1 to 2-3 shown in Table 12, since qualified products could not be obtained within the above-mentioned range of forming pressure, "None" is recorded in the "Formable Range" column of these tables, and a symbol "-" is recorded in the "Minimum Forming Pressure" column. In addition, for these comparative examples, no other evaluation of the formed bodies was performed. Therefore, the symbol "-" is recorded in the evaluation items of the formed bodies in Comparative Examples 2-1 to 2-3.
[0527] [Balance between molding pressure and rigidity]
[0528] The balance between molding pressure and rigidity is evaluated based on the value obtained by dividing the 50% compression strength by the density. There is a tendency that the higher the density of the molded body, the higher the rigidity of the polypropylene resin foamed particle molded body. In addition, there is a tendency that the higher the molding pressure, the higher the rigidity of the polypropylene resin foamed particle molded body. Therefore, considering the influence of the density of the molded body, the value of 50% compression strength / density is used as an indicator of the balance. When the value of 50% compression strength / density is higher than the value expected based on the molding pressure, it can be judged that the balance between molding pressure and rigidity is good.
[0529] In this example, the value calculated based on the following formula (7) (unit: kPa·m 3 / kg) is set as the value expected according to the molding pressure, and the balance between the molding pressure and the rigidity is evaluated based on the comparison result between this value and the value of 50% compressive strength / density. In addition, in this example, the molding pressure (unit: kPa) of the following formula (7) is the molding pressure when the molded body whose value of 50% compressive strength / density is measured is molded, that is, the minimum molding pressure. The minimum molding pressure in the following formula (7) is an absolute pressure, and the unit of the minimum molding pressure is "kPa".
[0530] 0.025×(molding pressure)-2.75…(7)
[0531] The meanings of the symbols described in the column "Balance between molding pressure and rigidity" in Tables 10 to 12 are as follows.
[0532] Excellent: The value of 50% compressive strength / density is the value of formula (7) + 1.0 or more
[0533] Good: The value of 50% compressive strength / density is greater than or equal to the value of formula (7) and less than the value of formula (7) + 1.0
[0534] Difference: The value of 50% compressive strength / density is less than the value of formula (7)
[0535] In the evaluation of the balance between molding pressure and rigidity, when the value of 50% compression strength / density is greater than the value of formula (7) (symbol "excellent") or "good"), rigidity commensurate with the molding pressure is obtained and the product is judged to be qualified. When the value of 50% compression strength / density is less than the value of formula (7) (symbol "poor"), the rigidity is insufficient relative to the molding pressure and the product is judged to be unqualified.
[0536] Table 10
[0537] (Table 10)
[0538]
[0539] Table 11
[0540] (Table 11)
[0541]
[0542] Table 12
[0543] (Table 12)
[0544]
[0545] As shown in Tables 10 and 11, the polypropylene resin composition constituting the foamed layer in the foamed beads of Examples 2-1 to 2-8 includes a polypropylene resin and a rubber-like body including an ethylene-propylene rubber, and the rubber-like body is dispersed in the polypropylene resin. In addition, the melting point of the foamed beads is within the specific range. Therefore, the foamed beads of Examples 2-1 to 2-8 have good in-mold formability.
[0546] Among the foamed particles in the examples, the independent cell rate of the foamed particles of Examples 2-1 to 2-5 is 85% or more. In addition, the temperature Tb of the top of the second endothermic peak Pb in these foamed particles is 158°C or more, the difference Tb-Ta between the temperature Tb of the top of the second endothermic peak Pb and the temperature Ta of the top of the first endothermic peak Pa is 15°C or more and 30°C or less, and the ratio of the peak height hb of the second endothermic peak Pb to the peak height ha of the first endothermic peak Pa, hb / ha, is 1.2 or more and 2.8 or less. Therefore, these foamed particles have good in-mold formability and excellent balance of rigidity relative to molding pressure. In addition, it can be understood from the results of Examples 2-1 to 2-5 that these special effects can be exhibited even in the case where the foaming layer contains a high melting point polypropylene resin composition containing ethylene propylene rubber from post-consumer materials.
[0547] In particular, the foamed beads of Examples 2-1 and 2-2 have a better balance between the molding pressure and the rigidity of the molded body than the foamed beads of Examples 2-3 to 2-5. Furthermore, the foamed beads of Examples 2-1 and 2-2 have better in-mold moldability and a wider moldable range than the foamed beads of Examples 2-3 to 2-5.
[0548] On the other hand, as shown in Table 12, the foamed beads of Comparative Examples 2-1 and 2-2 did not contain a rubber-like body composed of ethylene-propylene rubber. Therefore, the foamed beads of these Comparative Examples could not provide a good molded body.
[0549] In addition, the melting point of the expanded beads of Comparative Example 2-3 deviates from the specific range. Therefore, the expanded beads of Comparative Example 2-3 cannot form a good molded body.
[0550] Reference Example 2-1 is a foamed particle composed of a polypropylene resin composition containing homopolypropylene as the main component and not containing ethylene propylene rubber. The peak height ratio hb / ha of the foamed particles of Reference Example 2-1 is higher than that of Examples 2-1 to 2-5, but the balance of rigidity with respect to the molding pressure is good. It can be understood that the improvement effect of the balance of rigidity with respect to the molding pressure brought about by setting the peak height ratio hb / ha to the specific range is an effect unique to the foamed particles containing ethylene propylene rubber.
[0551] <Implementation Method 3>
[0552] (Polypropylene resin composition A)
[0553] Table 13 shows the properties of the polypropylene resin composition A used in the manufacture of the foamed particles of this embodiment. The polypropylene resin composition A3-1 shown in Table 13 is a recycled polypropylene with the polypropylene resin composition a1 recovered from ASR as the main component (more specifically, the resin composition A3-1 is "PLC-A02" manufactured by Planic Co., Ltd.). The shape of the resin composition A3-1 is a cylindrical pellet, the average length in the height direction of the pellet (the average length in the extrusion direction when manufacturing the pellet) is 3 mm, the diameter of the pellet is 3 mm, and the average mass of the pellet is 16 mg. In addition, the polypropylene resin composition A3-1 contains an inorganic substance with talc as the main component. The morphology of the polypropylene resin composition A3-1 used in this example was observed by the method described later, and the results showed that the polypropylene resin composition A3-1 has a morphology with a polypropylene resin as the matrix and a rubber-like body containing the ethylene propylene rubber as the micro-region.
[0554] Table 13
[0555] (Table 13) Polypropylene resin composition A
[0556] unit A3-1 A3-2 A3-3 density <![CDATA[kg / m 3 ]]> 930 930 1050 Ethylene content quality% 26 26 26 Carbon black content quality% 0.4 0.4 0.4 Ash content quality% 4.8 4.8 20 <![CDATA[Melting point Tmm A > ℃ 164 164 164 <![CDATA[Melt mass flow rate MFR A > g / 10 minutes 26 15 26 <![CDATA[Flexural modulus M A > MPa 950 1000 1000 <![CDATA[M A / Tm A ]]> MPa / ℃ 5.8 6.1 6.1
[0557] The methods for measuring the physical property values of the polypropylene resin composition A shown in Table 13 are the same as the methods for measuring the physical property values of the polypropylene resin composition A in the first embodiment.
[0558] (Polypropylene resin B)
[0559] Table 14 shows the properties and the like of the polypropylene resin B used for producing the foamed beads of the present embodiment.
[0560] Table 14
[0561] (Table 14) Polypropylene resin B
[0562] unit B3-1 B3-2 B3-3 B3-4 B3-5 Types of polypropylene resins R R R R h density <![CDATA[kg / m 3 ]]> 900 900 900 900 900 Ethylene content quality% 2.8 1.1 34 0.6 0 Butene content quality% - - - 9.7 - Ash content quality% 0 0 0 0 0 Melting point TmB ℃ 143 151 139 141 162 <![CDATA[Melt mass flow rate MFR B > g / 10 minutes 8 7 7 7 10 Flexural modulus MB MPa 950 1200 850 910 1650
[0563] The methods for measuring the physical property values of the polypropylene resin B shown in Table 14 are the same as the methods for measuring the physical property values of the polypropylene resin B in the first embodiment.
[0564] Next, the structure and production method of the foamed beads of this embodiment will be described.
[0565] (Example 3-1)
[0566] Resin composition A3-1, resin B3-1 and bubble regulator were put into an extruder in the mass ratio shown in Table 15, and a mixture containing a molten state of resin composition A3-1 and resin B3-1 was formed in the extruder. In addition, zinc borate was used as a bubble regulator. The addition amount of zinc borate was 500 mass ppm relative to the total of resin composition A3-1 and resin B3-1.
[0567] Then, the molten mixture is extruded into a strand from a small hole of a die head provided on the downstream side of the extruder. The strand-shaped extrudate is pulled out and cooled, and then cut into appropriate lengths using a pelletizer to obtain resin pellets.
[0568] The resin particles thus obtained were foamed by a direct foaming method. Specifically, first, 1 kg of the resin particles were put into a container with an internal volume of 5 L together with 3 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.02 parts by mass of sodium alkylbenzene sulfonate as a dispersing aid, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the resin particles, and the resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0569] After that, carbon dioxide as a foaming agent is supplied into the sealed container while stirring the container, so that the temperature in the container rises to 155.5°C. The pressure in the container at this time is 2.1MPa(G). After that, the temperature in the container is adjusted to 156°C and the temperature is maintained for 15 minutes, thereby impregnating the foaming agent into the resin particles. After that, the container is opened and the contents are released under atmospheric pressure, thereby foaming the resin particles. The foamed particles are dried in an atmosphere of a temperature of 23°C and a relative humidity of 50% for 24 hours. Through the above, the foamed particles of Example 3-1 are obtained.
[0570] (Example 3-2)
[0571] The method for producing the foamed beads of Example 3-2 is substantially the same as the method for producing the foamed beads of Example 3-1, except that the mass ratio of the resin composition A3-1 to the resin B3-1 is changed as shown in Table 15, and the temperature in the container during foaming is changed to 152.5°C.
[0572] (Example 3-3)
[0573] The method for producing the foamed beads of Example 3-3 is substantially the same as the method for producing the foamed beads of Example 3-1, except that the mass ratio of the resin composition A3-1 and the resin B3-1 is changed as shown in Table 15, and the temperature in the container during foaming is changed to 161°C.
[0574] (Example 3-4)
[0575] The method for producing foamed beads of Example 3-4 is substantially the same as the method for producing foamed beads of Example 3-1, except that the mass ratio of resin composition A3-1 to resin B3-1 is changed as shown in Table 15, and the temperature in the container during foaming is changed to 158.5°C.
[0576] (Example 3-5)
[0577] The method for manufacturing the foamed beads of Example 3-5 is substantially the same as the method for manufacturing the foamed beads of Example 3-1, except that the type of resin B is changed as shown in Table 15, the mass ratio of resin composition A to resin B is changed as shown in Table 15, and the temperature in the container during foaming is changed to 158.5°C.
[0578] (Example 3-6)
[0579] The method for manufacturing the foamed particles of Example 3-6 is substantially the same as the method for manufacturing the foamed particles of Example 3-1, except that the type of resin B is changed as shown in Table 15, the mass ratio of the resin composition A to the resin B is changed as shown in Table 15, and the temperature in the container during foaming is changed to 158.5°C.
[0580] (Example 3-7)
[0581] The method for manufacturing the foamed particles of Example 3-7 is substantially the same as the method for manufacturing the foamed particles of Example 3-1, except that the type of resin B is changed as shown in Table 16, the mass ratio of the resin composition A to the resin B is changed as shown in Table 16, and the temperature in the container during foaming is changed to 158.5°C.
[0582] (Example 3-8)
[0583] The method for manufacturing the foamed beads of Example 3-8 is substantially the same as the method for manufacturing the foamed beads of Example 3-1, except that the type of resin composition A is changed as shown in Table 16, the mass ratio of resin composition A to resin B is changed as shown in Table 16, and the temperature in the container during foaming is changed to 158.5°C.
[0584] (Example 3-9)
[0585] The method for manufacturing the foamed beads of Example 3-9 is substantially the same as the method for manufacturing the foamed beads of Example 3-1, except that the type of resin composition A is changed as shown in Table 16, the mass ratio of resin composition A to resin B is changed as shown in Table 16, and the temperature in the container during foaming is changed to 158.5°C.
[0586] (Example 3-10)
[0587] The method for producing foamed beads of Example 3-10 is substantially the same as the method for producing foamed beads of Example 3-1, except that the temperature in the container during foaming was changed to 155.5° C. and the pressure in the container was changed to 2.8 MPa (G).
[0588] (Comparative Example 3-1)
[0589] The foamed beads of Comparative Example 3-1 do not contain resin B, but are composed of resin composition A3-1. The method for producing the foamed beads of Comparative Example 3-1 is substantially the same as the method for producing the foamed beads of Example 3-1, except that resin composition A3-1 is used instead of resin B, and the temperature in the container during foaming is changed to 164°C.
[0590] (Comparative Example 3-2)
[0591] The method for manufacturing the foamed beads of Comparative Example 3-2 is substantially the same as the method for manufacturing the foamed beads of Example 3-1, except that the type of resin B is changed as shown in Table 16, the mass ratio of resin composition A to resin B is changed as shown in Table 16, and the temperature in the container during foaming is changed to 164°C.
[0592] (Reference Example 3-1)
[0593] The foamed beads of Reference Example 3-1 do not contain resin composition A, but are composed of resin B3-1. The method for producing the foamed beads of Reference Example 3-1 is substantially the same as the method for producing the foamed beads of Example 3-1, except that resin composition A is not used but only resin B3-1 is used, and the temperature in the container during foaming is changed to 149.5°C.
[0594] The resin particles, foamed particles, and molded articles obtained by in-mold molding the foamed particles thus obtained were used to evaluate the evaluation items shown in Tables 15 and 16. The evaluation methods for the items not evaluated in the embodiments described above are shown below.
[0595] 〔Melting point T of foamed particles r 〕
[0596] Using a heat flux differential scanning calorimeter (manufactured by SII Nano Technology Co., Ltd., model: DSC7020), the foamed particles were heated from 30°C to 230°C at a heating rate of 10°C / min. Thereafter, the foamed particles were cooled from 230°C to 23°C at a cooling rate of 10°C / min. After the cooling was completed, the foamed particles were heated again from 23°C to 230°C at a heating rate of 10°C / min (i.e., the second heating), and a DSC curve was obtained. Then, the top temperature of the melting peak that appeared in the DSC curve in the second heating was taken as the melting point T of the foamed particles. r In addition, the melting point T of the foamed particles thus determined is r This is equal to the melting point Tm of the foamed beads measured by the measuring method of the first embodiment.
[0597] 〔Foamable range〕
[0598] In the above-mentioned method for producing foamed beads, the resin particles were foamed by stepwise changing the temperature during foaming by 0.5° C. within the range of 150° C. to 165° C. At this time, the equilibrium vapor pressure in the container was 2.1 MPa(G).
[0599] Afterwards, the bulk density and state of the foamed particles obtained by foaming at each foaming temperature were evaluated. 3 The foaming temperature at which the foamed particles have no clear wrinkles and the shrinkage of the foamed particles is hardly confirmed is determined as the foamable temperature, and the lowest temperature among the foamable temperatures is determined as the lower limit of the foamable range, and the highest temperature is determined as the upper limit of the foamable range. The wider the width from the lower limit to the upper limit of the foaming temperature range for obtaining a good product, the better the foamability of the resin particles when foaming, which is preferred.
[0600] 〔Formable range〕
[0601] In the evaluation of the formable range, the forming pressure during formal heating is changed by 0.01 MPa each time from 0.26 MPa (G) to 0.38 MPa (G) to perform in-mold forming, thereby making a foamed particle molded body, and the formable range is determined based on the surface property, weldability and recovery of the obtained molded body. In addition, the specific manufacturing method of the foamed particle molded body is the same as that of embodiment 1.
[0602] The surface property, weldability and recovery of the foamed particle molded body after state adjustment are evaluated, and the range of the molding pressure (that is, the molding pressure during the formal heating that can obtain a qualified product) that is qualified in any of the evaluation criteria described later is set as the moldable range. In addition, the evaluation method of the surface property, weldability and recovery of the foamed particle molded body is the same as that of embodiment 1.
[0603]
[0604]
[0605] As shown in Tables 15 and 16, the polypropylene resin composition constituting the foamed layer in the foamed beads of Examples 3-1 to 3-10 includes a polypropylene resin and a rubber-like body including an ethylene-propylene rubber, and the rubber-like body is dispersed in the polypropylene resin. r Therefore, the expanded beads of Examples 3-1 to 3-10 have good in-mold formability.
[0606] The molded articles obtained from the expanded beads obtained by expanding the resin particles of Examples 3-1 to 3-10 showed good compressible properties. Furthermore, the obtained molded articles had a spot pattern consisting of relatively light black (gray) and white, and thus had excellent design properties.
[0607] Among them, in particular, the foamed particles of Examples 3-1 and 3-2, although containing the polypropylene resin composition a1 from ASR, have good in-mold formability to the same extent as that of Reference Example 3-1 shown in Table 16, i.e., polypropylene resin foamed particles composed of non-recycled polypropylene resin.
[0608] On the other hand, as shown in Table 16, the foamed beads of Comparative Example 3-1 do not contain a rubber-like body containing ethylene-propylene rubber, and the melting point T r Deviating from the above-mentioned specific range, therefore, the expanded beads of Comparative Example 3-1 could not obtain a good molded body.
[0609] In addition, the melting point T of the expanded beads of Comparative Example 3-2 is r Deviating from the specific range, the expanded beads of Comparative Example 3-2 could not form a good molded body.
[0610] <Implementation Method 4>
[0611] (Polypropylene resin composition A)
[0612] Table 17 shows the properties of the polypropylene resin composition A used in the manufacture of the foamed particles of this embodiment. Resin composition A4-1 shown in Table 17 is "PLC-A02" manufactured by Planic Co., Ltd., and resin composition A4-2 is "ELVBP-10" manufactured by the same company. Resin composition A4-1 and resin composition A4-2 are both recycled polypropylenes derived from post-consumer materials and containing ethylene propylene rubber. More specifically, the main component of resin composition A4-1 is polypropylene resin composition a1 recovered from ASR, and resin composition A4-2 is polypropylene resin composition a recovered from used automobile parts (more specifically, bumpers).
[0613] Resin composition A4-1 and resin composition A4-2 are cylindrical pellets, and the average length in the height direction of the pellets (the average length in the extrusion direction when manufacturing the pellets) is 3mm, the diameter of the pellets is 3mm, and the average mass of the pellets is 16mg. In addition, the inorganic substance with talc as the main component is contained in resin composition A4-1 and resin composition A4-2. By the method described later, the form of the resin composition A4-1 and resin composition A4-2 used in this example is observed, and the result shows that the resin composition A4-1 and resin composition A4-2 are all based on polypropylene resin as the matrix and the rubber-like body containing ethylene propylene rubber as the form of micro-region.
[0614] Table 17
[0615] (Table 17) Polypropylene resin composition A
[0616] unit A4-1 A4-2 density <![CDATA[kg / m 3 ]]> 930 990 Carbon black content quality% 0.4 0.7 Ash content quality% 4.8 12.7 23℃ decane soluble components quality% 12 11 <![CDATA[D sol -A inso1 ]]> g 0.12 0.11 <![CDATA[Melting point Tm A > ℃ 164 164 <![CDATA[Heat of fusion H A > J / g 81 65 <![CDATA[Melt mass flow rate MFR A > 10 minutes 26 29 <![CDATA[Flexural modulus M A > MPa 950 1090 <![CDATA[M A / Tm A ]]> MPa / ℃ 5.8 6.6
[0617] The physical property values of the polypropylene resin composition A shown in Table 17 were measured in the same manner as those of the polypropylene resin composition A in Embodiment 1. In addition, the column "23°C n-decane soluble components" in Table 17 describes the amount of D contained in the resin composition A per 1 g of the resin composition A. sol -A insol The amount of is converted into a value obtained by percentage relative to the mass of the resin composition A (unit: mass %).
[0618] (Polypropylene resin B)
[0619] Table 18 shows the properties and the like of the polypropylene resin B used for producing the foamed beads of the present embodiment.
[0620] Table 18
[0621] (Table 18) Polypropylene resin B
[0622] unit B4-1 B4-2 B4-3 B4-4 Types of polypropylene resins - R R R h density <![CDATA[kg / m 3 ]]> 900 900 900 900 Ethylene content quality% 1.1 2.0 3.4 0.0 Ash content quality% 0 0 0 0 <![CDATA[Melting point Tm B > ℃ 151 147 139 162 <![CDATA[Heat of fusion H B > J / g 91 77 63 101 <![CDATA[Melt mass flow rate MFR B > g / 10 minutes 7 7 7 10 <![CDATA[Flexural modulus M B > MPa 1200 1070 850 1650
[0623] The methods for measuring the physical property values of the polypropylene resin B shown in Table 18 are the same as the methods for measuring the physical property values of the polypropylene resin B in the first embodiment.
[0624] Next, the structure and production method of the foamed beads of this embodiment will be described.
[0625] (Example 4-1)
[0626] Resin composition A4-1, resin B4-1 and bubble regulator were put into an extruder in the mass ratio shown in Table 19, and a mixture containing a molten state of resin composition A4-1 and resin B4-1 was formed in the extruder. In addition, zinc borate was used as a bubble regulator. The addition amount of zinc borate was 500 mass ppm relative to the total of resin composition A4-1 and resin B4-1.
[0627] Then, the molten mixture is extruded into a strand from a small hole of a die head provided on the downstream side of the extruder. The strand-shaped extrudate is pulled out and cooled, and then cut into appropriate lengths using a pelletizer to obtain resin pellets.
[0628] The resin particles thus obtained were foamed by a direct foaming method. Specifically, first, 1 kg of the resin particles were put into a container with an internal volume of 5 L together with 3 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.02 parts by mass of sodium alkylbenzene sulfonate as a dispersing aid, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the resin particles, and the resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0629] After that, carbon dioxide as a blowing agent is supplied into the sealed container while stirring the container, so that the temperature in the container rises to 155.5°C. The pressure in the container at this time is 2.1 MPa (G). After that, the temperature in the container is adjusted to 156°C and the temperature is maintained for 15 minutes, thereby impregnating the blowing agent into the resin particles. After that, the container is opened and the contents are released under atmospheric pressure, thereby foaming the resin particles to obtain primary foamed particles. The primary foamed particles are dried in an atmosphere of temperature 23°C and relative humidity 50% for 24 hours.
[0630] Next, the pressure-resistant container is filled with primary foaming particles, and air is injected into the pressure-resistant container, and the pressure in the pressure-resistant container is raised from atmospheric pressure to 0.6 MPa (G) over 24 hours. The pressure is maintained for 24 hours to allow air to be immersed in the bubbles. After that, the primary foaming particles taken out of the pressure-resistant container are filled into the secondary foamer, and steam with a pressure of 0.15 MPa (G) is supplied, thereby further foaming the primary foaming particles. Through the above, the foaming particles of Example 4-1 are obtained.
[0631] (Example 4-2)
[0632] The method for producing the foamed beads of Example 4-2 was substantially the same as the method for producing the foamed beads of Example 4-1, except that the mass ratio of the resin composition A4-1 to the resin B4-1 was changed as shown in Table 19.
[0633] (Example 4-3)
[0634] The method for producing the foamed beads of Example 4-3 is substantially the same as the method for producing the foamed beads of Example 4-1, except that the polypropylene resin B4-2 is used as the resin B instead of the polypropylene resin B4-1 as shown in Table 19.
[0635] (Example 4-4)
[0636] The method for producing the foamed beads of Example 4-4 was substantially the same as the method for producing the foamed beads of Example 4-1, except that resin composition A4-2 was used as resin composition A in place of resin composition A4-1 as shown in Table 19.
[0637] (Example 4-5)
[0638] The foamed beads of Example 4-5 are primary foamed beads obtained in substantially the same manner as the foamed beads of Example 4-1. The bulk density of the foamed beads of Example 4-5 is 45 kg / m 3 .
[0639] (Comparative Example 4-1)
[0640] The expanded beads of Comparative Example 4-1 do not contain the resin B but are composed of the resin composition A4-1. The method for producing the expanded beads of Comparative Example 4-1 is substantially the same as the method for producing the expanded beads of Example 4-1 except that the resin composition A4-1 is used instead of the resin B.
[0641] (Reference Example 4-1)
[0642] The expanded beads of Reference Example 4-1 do not contain the resin composition A but are composed of the resin B4-1. The method for producing the expanded beads of Reference Example 4-1 is substantially the same as the method for producing the expanded beads of Example 4-1 except that the resin composition A is not used but only the resin B4-1 is used.
[0643] The resin particles, foamed particles, and molded articles obtained by in-mold molding of the foamed particles obtained in this manner were used to evaluate the evaluation items shown in Table 19. The following describes the evaluation methods for the items that were not evaluated in the embodiments described above.
[0644] [Melting point Tm of the polypropylene resin composition R constituting the foamed layer R , flexural modulus M R , melt mass flow rate MFR R and the heat of fusion H R 〕
[0645] The melting point Tm of the polypropylene resin composition R constituting the foamed layer R , flexural modulus M R , melt mass flow rate MFR R and heat of fusion H R The method for measuring the melting point Tm of the resin composition A is as follows: A , flexural modulus M A , melt mass flow rate MFR A and the heat of fusion H A That is, the melting point Tm of the polypropylene resin composition R described in Table 19 is R , flexural modulus M R And melt mass flow rate MFR R These are physical property values corresponding to the melting point Tm of the foamed beads in Embodiment 1, and the flexural elastic modulus and melt mass flow rate of the polypropylene resin composition constituting the foamed beads.
[0646] In addition, the flexural modulus M of the polypropylene resin composition R R In the measurement, the foamed beads were hot-pressed at 180°C to prepare a sheet with a thickness of 4 mm, and a test piece with a length of 80 mm×width of 10 mm×thickness of 4 mm was cut out from the sheet to measure the bending elastic modulus M. R Determination of.
[0647] In addition, the melt mass flow rate MFR of the polypropylene resin composition R RIn the measurement of the MFR, first, the foamed particles were hot-pressed at 180°C for 3 minutes to degas the foamed particles, thereby preparing a resin sheet composed of a mixed resin constituting the foamed particles. The pellet-shaped sample obtained by cutting the resin sheet was used to measure the melt mass flow rate MFR. R Determination of.
[0648] 〔Formable range〕
[0649] In the evaluation of the formable range, the forming pressure during formal heating is changed by 0.01 MPa each time from 0.32 MPa (G) to 0.44 MPa (G) to perform in-mold forming, thereby making a foamed particle molded body, and the formable range is determined based on the surface property, weldability and recovery of the obtained molded body. In addition, the specific manufacturing method of the foamed particle molded body is the same as that of embodiment 1.
[0650] The surface property, weldability and recovery of the foamed particle molded body after state adjustment are evaluated, and the range of the molding pressure (that is, the molding pressure during the formal heating that can obtain a qualified product) that is qualified in any of the evaluation criteria described later is set as the moldable range. In addition, the evaluation method of the surface property, weldability and recovery of the foamed particle molded body is the same as that of embodiment 1.
[0651]
[0652] As shown in Table 19, the polypropylene resin composition constituting the foamed layer in the foamed beads of Examples 4-1 to 4-5 contains a polypropylene resin and a rubber-like body containing an ethylene-propylene rubber, and the rubber-like body is dispersed in the polypropylene resin. In addition, the melting point Tm of the polypropylene resin composition R constituting the foamed layer is R Within the specific range, the expanded beads of Examples 4-1 to 4-5 have good in-mold formability.
[0653] In addition, the resin composition A used in these examples is a polypropylene-based resin composition derived from post-consumer materials. The melting point Tm of the resin composition A is A Above 160°C, the bending modulus M A The melting point Tm of resin B is 800 MPa or more and 1200 MPa or less. B Less than 160℃, bending modulus M B 900 MPa or more and 1400 MPa or less, and the bending modulus M B Relative to the bending modulus M A Ratio M B / M Ais 1 or more. Moreover, the resin particles in Examples 4-1 to 4-5 are composed of a melt-kneaded product obtained by mixing such resin composition A and resin B at a mass ratio in the range of resin composition A:resin B=10:90 to 70:30. Therefore, the foamed particles obtained by foaming the resin particles show good compressible properties.
[0654] On the other hand, the foamed beads of Comparative Example 4-1 did not contain a rubber-like body composed of ethylene-propylene rubber, and the melting point Tm of the polypropylene resin composition R was R The foamed beads of Comparative Example 4-1 were out of the above-mentioned specific range.
[0655] <Implementation method 5>
[0656] (Polypropylene resin composition I, polypropylene resin B)
[0657] In this embodiment, foamed beads are produced using an impact polypropylene as the polypropylene resin composition I and a propylene random copolymer as the polypropylene resin B. The impact polypropylene and the propylene random copolymer used in this embodiment are as follows.
[0658] Impact-resistant polypropylene
[0659] (1) Abbreviation “ICP1”: Polypropylene “PLC-A02” manufactured by Planic, with a weight average molecular weight (Mw) of 220,000, a number average molecular weight (Mn) of 24,000, and an ethylene content of 26% by mass.
[0660] (2) Abbreviation “ICP2”: End-capped polypropylene “MK112” manufactured by Idemitsu Kosan Co., Ltd.
[0661] (3) “ICP3” for short: Block polypropylene “J762HP” manufactured by Prime Polymers
[0662] (4) Abbreviation “ICP4”: decomposition raw material of ICP2 (0.2 parts by mass of PERHEXA25B manufactured by NOF Corporation was added to ICP2, and the mixture was melt-kneaded once in an extruder to form pellets).
[0663] (5) Abbreviation “ICP5”: Block polypropylene “CPP050RP” manufactured by REEF Technology Co., Ltd., with a weight average molecular weight (Mw) of 265,000 and a number average molecular weight (Mn) of 46,000.
[0664] ·Propylene random copolymer
[0665] (1) Abbreviation “r-PP1”: Random polypropylene (ethylene content 2.5 mass%) manufactured by Primen Polymers
[0666] (2) Abbreviation: “r-PP2”: manufactured by Sinopec Shanghai Petrochemical Co., Ltd., ethylene-propylene-butene random copolymer resin (ethylene content: 0.9% by mass, butene content: 9.6% by mass)
[0667] Table 20 shows the properties of the impact polypropylene and propylene random copolymer used for producing the foamed beads of the present embodiment.
[0668]
[0669] The physical property values shown in Table 20 are measured in the same manner as the physical property values of the polypropylene resin composition A in Embodiment 1. In addition, in Tables 20 and 21, carbon black is abbreviated as "CB". In Table 21, the melting point of the impact polypropylene is abbreviated as Tm I The melting point of the propylene random copolymer is abbreviated as Tm B , the melt mass flow rate of impact polypropylene is abbreviated as MFR I The melt mass flow rate of the propylene random copolymer is abbreviated as MFR B To record.
[0670] Next, the structure and production method of the foamed beads of this embodiment will be described.
[0671] (Examples 5-1 to 5-5, Comparative Examples 5-1 to 5-3, Reference Example 5-1, Reference Example 5-2)
[0672] The impact-resistant polypropylene and propylene random copolymer shown in Table 21 are supplied to the extruder in the mixing ratio shown in Table 21. Furthermore, a bubble regulator is supplied to the extruder to form a molten mixture containing the impact-resistant polypropylene and the propylene random copolymer in the extruder. In addition, zinc borate is used as a bubble regulator. The amount of zinc borate added is 1000 mass ppm relative to the total of the impact-resistant polypropylene and the propylene random copolymer. In addition, in Example 5-4, Comparative Example 5-1, Comparative Example 5-2, Reference Example 5-1 and Reference Example 5-2, a carbon black masterbatch and a talc masterbatch based on r-PP1 are added to the extruder in such a manner as to obtain the CB amount and ash amount recorded in Table 21.
[0673] After that, the molten mixture is extruded into a strand from a small hole of a die head provided on the downstream side of the extruder. The strand-shaped extrudate is pulled out and cooled, and then cut into appropriate lengths using a pelletizer to obtain resin pellets. The mass of the resin pellets is about 1.0 mg.
[0674] The resin particles thus obtained were foamed by a direct foaming method. Specifically, first, 1 kg of the resin particles were put into an autoclave with an internal volume of 5 L together with 3 L of water as an aqueous medium. Then, 3 g of kaolin as a dispersant and 0.04 g of sodium alkylbenzene sulfonate and 0.1 g of aluminum sulfate as a dispersant were added to the autoclave to disperse the resin particles in the aqueous medium.
[0675] Thereafter, while stirring the contents of the autoclave, carbon dioxide as a foaming agent was supplied into the autoclave to raise the temperature in the container to the foaming temperature shown in Table 21. The foaming temperature is a temperature at which the apparent density is minimized while maintaining good in-mold formability while the foaming pressure (back pressure in the autoclave) is fixed to 2.1 MPa during dispersion medium release foaming.
[0676] After that, the temperature in the autoclave was maintained for 15 minutes, thereby allowing the foaming agent to be impregnated into the resin particles and adjusting the melting heat of the high temperature peak. After that, the autoclave was pressurized with carbon dioxide, and the foaming pressure shown in Table 21 was maintained, while the contents of the autoclave were released under an atmospheric pressure atmosphere, thereby foaming the resin particles. Through the above, foamed particles of Examples 5-1 to 5-5, Comparative Examples 5-1 to 5-3, and Reference Examples 5-1 to 5-2 were obtained.
[0677] The resin particles, foamed particles, and molded articles obtained by in-mold molding of the foamed particles thus obtained were used to evaluate the evaluation items shown in Table 21. The following shows the evaluation methods for the items that were not evaluated in Embodiment 1 among these evaluation items. In addition, the evaluation methods for the items that were the same as the items evaluated in Embodiment 1 among the evaluation items shown in Table 21 were the same as the evaluation methods in Embodiment 1.
[0678] [Ash content and carbon black content of the polypropylene resin composition constituting the core layer]
[0679] The ash content of the polypropylene resin composition constituting the core layer was measured by the following method using a thermogravimetric measuring apparatus ("TG / DTA7200" manufactured by Hitachi High-Technologies Corporation) and a platinum sample pan (K-Y50-035 PTΦ5×5PAN).
[0680] First, 14 to 16 mg of resin particles or mini pellets are prepared as samples. Platinum sample pans without samples are placed on the reference balance and the measuring balance, respectively, and zero point adjustment is performed. Next, the accurately weighed sample is placed in the platinum sample pan on the measuring balance. Afterwards, while the weight is continuously recorded on the balance, the sample is heated in a nitrogen atmosphere and the temperature is maintained at 40°C for 5 minutes. Thereafter, the organic components contained in the sample are thermally decomposed by heating from 40°C to 500°C at a heating rate of 10°C / min to obtain a residue composed of inorganic components including carbon black. The weight of the residue (hereinafter referred to as "residue weight 1") is measured.
[0681] Next, the residue is heated from 500°C to 900°C in an air atmosphere to oxidize and remove the carbon black in the residue. Then, the weight of the residue after the carbon black is removed (hereinafter referred to as "residue weight 2") is measured. Using the weight of the sample obtained above, the residue weight 1 (unit: mg) and the residue weight 2 (unit: mg), the CB amount (unit: wt%) is calculated based on the following formula (8), and the ash amount (unit: wt%) is calculated using formula (9). In addition, the ratio of the CB amount to the ash amount is recorded in the "CB amount / ash amount" column in Table 21.
[0682] CB amount = (residue weight 1 - residue weight 2) ÷ sample weight × 100 (8)
[0683] Ash content = residue weight 2 ÷ sample weight × 100…(9)
[0684] 〔Apparent density / foaming pressure〕
[0685] The column "Apparent density / foaming pressure" in Table 21 records the value obtained by dividing the apparent density of the foamed particles by the foaming pressure. In this method, the foaming property of the foamed particles is evaluated based on the value of apparent density / foaming pressure. Regarding the foaming property of the foamed particles, the foaming pressure (the back pressure in the closed container during foaming) is fixed to a certain pressure (specifically, 2.1 MPa) to produce the foamed particles, and whether the apparent density of 80 kg / m can be stably produced is evaluated. 3 The evaluation is made based on the fact that the closed cell ratio of the expanded beads is 80% or more. More specifically, the smaller the ratio of the apparent density / foaming pressure of the expanded beads is, the more excellent the expandability is judged to be.
[0686] 〔Lower limit welding pressure, lower limit forming pressure, forming range〕
[0687] In the evaluation of the lower limit welding pressure, the lower limit forming pressure and the formable range, the forming pressure during formal heating is changed by 0.01 MPa at a time from 0.20 MPa (G) to 0.44 MPa (G) to perform in-mold forming, thereby producing a molded body, and the formable range is determined based on the surface properties, welding properties and recovery properties of the obtained molded body.
[0688] The manufacturing method of the molded body is as follows. First, the foamed particles are filled into the forming mold by the crack filling method. In this example, a forming mold with a rectangular forming cavity is used, and the forming cavity has an inner dimension of 300mm in the longitudinal direction, 250mm in the transverse direction, and 50mm in the thickness direction. When the mold is opened 5mm in the thickness direction from a completely closed state (i.e., a crack gap of 5mm), the foamed particles are filled in the forming cavity. After the filling is completed, the mold is completely closed (i.e., 10% of the crack amount). After that, steam of any molding pressure within the above range is supplied to the forming cavity, the foamed particles are heated, the foamed particles are secondary foamed, and the foamed particles are welded, thereby obtaining a foamed particle molded body. The mold is water-cooled until the surface pressure of the foamed particle molded body in the mold becomes 0.04MPa (G), the mold is opened, and the foamed particle molded body is taken out from the mold. The obtained foamed particle molded body is cured for 12 hours in an atmosphere of atmospheric pressure and a temperature of 80°C.
[0689] The surface appearance, weldability and recovery of the molded body after curing are evaluated, and the range of the molding pressure that is qualified in any item of the evaluation criteria described later (that is, the molding pressure that can obtain qualified products) is used as the moldable range. The larger the moldable range is, the better the in-mold moldability can be judged to be. In addition, the highest molding pressure in the moldable range is used as the upper limit molding pressure, and the lowest molding pressure is used as the lower limit molding pressure. Furthermore, the lowest molding pressure among the molding pressures with qualified weldability in the evaluation criteria described later is set as the lower limit welding pressure. In addition, in the absence of a moldable range, it is judged that it cannot be molded, and the symbol "-" is recorded in the "Moldable Range" column of Table 21.
[0690] Weldability
[0691] Bend the foamed bead molded body to break it, and find the total number of foamed beads present on the fracture surface (C1) and the number of foamed beads broken inside the foamed beads on the fracture surface (C2). Then, calculate the value of the ratio of the number of foamed beads C2 broken inside the foamed beads to the total number of foamed beads C1 expressed as a percentage (i.e., C2 / C1×100) as the material destruction rate (unit: %). Perform the operation more than five times and calculate the arithmetic mean of the material destruction rates of the five times. Then, the case where the arithmetic mean of the material destruction rate is 90% or more is judged to be qualified.
[0692] Surface appearance
[0693] A 100 mm × 100 mm square is drawn in the center of one side of the surface in the thickness direction of the foamed bead molded body, and a diagonal line is drawn from any corner of the square. Then, the number of voids on the diagonal line, that is, the number of voids larger than 1 mm × 1 mm formed in the gaps between the foamed beads, is counted. Moreover, the number of voids is less than 5 and the surface is not uneven.
[0694] Restoration
[0695] When the formed body is viewed from above in the thickness direction, the thickness of the formed body at four positions (hereinafter referred to as "corners") 10 mm inward from each vertex of the surface surrounded by the side of 300 mm in length and the side of 250 mm in width and the thickness of the formed body at the center of the surface are measured. Next, the ratio of the thickness of the center portion to the thickness of the thickest corner among the four corners is calculated (unit: %). The thickness ratio thus obtained is considered acceptable when it is 99% or more.
[0696] [Surface state at upper limit forming pressure reduction]
[0697] In-mold forming is performed at the upper limit forming pressure in the above-mentioned formable range to obtain a molded body. The surface state of the molded body is visually observed. In the evaluation of the surface state under the upper limit forming pressure, the state in which the surface appearance of the molded body is good and there are no wrinkles on the surface is judged to be good. In addition, the state in which there are more than five local wrinkles (groove-shaped sunken parts) in the foamed particle part constituting the surface of the molded body is judged to be the presence of wrinkles. In addition, as described later, in Comparative Example 5-3, since there is no molding pressure that can obtain a good molded body, the evaluation of the surface state under the upper limit molding pressure is not performed. Therefore, the symbol "-" is recorded in the column "Surface state under upper limit molding pressure" in Comparative Example 5-3.
[0698] 〔Shrinkage rate〕
[0699] The mold is formed at the lower limit forming pressure in the above-mentioned forming range to obtain a molded body. After the molded body is cured in an atmosphere of 80°C for 12 hours, it is slowly cooled and further cured in an atmosphere of 23°C for 6 hours to prepare a test body. Then, the length of the long side, that is, the longest side of the test body is measured. Using the length L (unit: mm) of the long side of the test body obtained above and the length Lm (unit: mm) of the long side of the forming cavity in the forming mold, the shrinkage rate (unit: %) of the test body is calculated based on the following formula (12).
[0700] Shrinkage rate = (Lm-L) / Lm×100…(12)
[0701] The above operation was performed on three test bodies, and the arithmetic mean of the shrinkage rates in the three test bodies was taken as the shrinkage rate of the molded body (unit: %). In addition, in Comparative Example 5-3, since there was no molding pressure that could obtain a good molded body, the shrinkage rate of the molded body was calculated using the molded body obtained by in-mold molding at a molding pressure of 0.44 MPa (G).
[0702] 〔Molding body density〕
[0703] The foamed bead molded body is obtained by in-mold molding at the lowest molding pressure in the above-mentioned moldable range. The density of the molded body (unit: kg / m 3 ). In Comparative Example 5-3, since there was no molding pressure that could obtain a good molded body, the shrinkage of the molded body was calculated using the molded body obtained by in-mold molding at a molding pressure of 0.44 MPa (G).
[0704] [Closed cell ratio of molded body]
[0705] In-mold molding is performed at a molding pressure at the lower limit of the above-mentioned moldable range to obtain a molded body. The obtained molded body is placed in a constant temperature chamber under atmospheric pressure, relative humidity of 50%, and 23°C for 10 days for curing. Next, a 25×25×30mm sample is cut out from the molded body, and the independent cell rate of the molded body is measured using the same method as the independent cell rate of the above-mentioned foamed particles using the sample. In addition, in Comparative Example 5-3, since there is no molding pressure that can obtain a good molded body, the independent cell rate is not measured. Therefore, the symbol "-" is recorded in the "Independent Cell Rate" column of the molded body in Comparative Example 5-3.
[0706]
[0707] As shown in Table 21, in the methods for producing the foamed beads of Examples 5-1 to 5-5, the core layer is made of an ethylene-propylene rubber having a melting point Tm I Impact polypropylene with a melting point of more than 160°C BIt is composed of a molten mixture of propylene random copolymers at a temperature of 125°C or more and less than 160°C. In addition, the mass ratio of the impact polypropylene and the propylene random copolymer in the core layer is impact polypropylene: propylene random copolymer = 2:98~70:30. Therefore, the foamed particles of these embodiments have excellent in-mold formability. In addition, compared with Comparative Example 5-1 that does not contain impact polypropylene, Examples 5-1 to 5-5 can produce foamed particles at a high foaming temperature. Furthermore, the apparent density of the foamed particles of Examples 5-1 to 5-5, and thus the apparent density of the molded body, is lower than that of Comparative Example 5-1, and the foamability is improved.
[0708] In Comparative Example 5-2, the resin particles were foamed at a higher foaming temperature than that of Comparative Example 5-1, while the same propylene random copolymer was used. As a result, foamed particles with improved foamability and low apparent density were obtained, but the in-mold formability of the foamed particles was reduced, the shrinkage of the obtained foamed particle molded body was increased, and wrinkles were generated on the surface.
[0709] The resin particles of Comparative Example 5-3 do not contain a propylene random copolymer and have a core layer composed of impact polypropylene. In Comparative Example 5-3, although the foaming temperature can be increased, the moldability of the obtained foamed particles is reduced, and even if the molding pressure is changed, a good molded body cannot be obtained.
[0710] The resin particles of Reference Example 5-1 contain impact polypropylene having a relatively low melting point. The resin particles of Reference Example 5-1 have inferior foamability compared to the resin particles of Examples 5-1 to 5-5. In addition, the foamed particles of Reference Example 5-1 have inferior moldability compared to the foamed particles of Examples 5-1 to 5-5.
[0711] The resin particles of Reference Example 5-2 contain impact-resistant polypropylene having a relatively low melting point. The expanded particles of Reference Example 5-2 have inferior moldability in moldability compared to the expanded particles of Examples 5-1 to 5-5.
[0712] The specific aspects of the foamed beads and the method for producing the same according to the present invention are described above based on the embodiments. However, the specific aspects of the foamed beads and the method for producing the same according to the present invention are not limited to the embodiments, and the structure can be appropriately changed within the scope of the present invention.
[0713] For example, from another viewpoint, the expanded beads and the molded article according to the first embodiment can be understood as the following inventions of expanded beads according to [1-1] to [1-4] and the invention of a molded article according to [1-5].
[0714] [1-1] A polypropylene resin foamed particle having a foamed layer composed of a polypropylene resin composition, wherein:
[0715] The polypropylene resin composition constituting the foamed layer comprises a polypropylene resin and a rubber-like body comprising an ethylene-propylene rubber.
[0716] The rubber-like body is dispersed in the polypropylene resin.
[0717] The amount of the acetone-insoluble component contained in the n-decane extract of the foamed beads is 0.02 g or more and 0.10 g or less per 1 g of the foamed beads,
[0718] The melting point Tm of the foamed particles is 140° C. or higher and 162° C. or lower.
[0719] A difference Tm-Tc between a melting point Tm of the foamed particles and a crystallization temperature Tc of the foamed particles is 38° C. or less.
[0720] [1-2] The polypropylene resin foamed particles according to [1-1], wherein the average diameter of the rubber-like body is 0.1 μm or more and 2 μm or less.
[0721] [1-3] The polypropylene resin foamed particles according to [1-1] or [1-2], wherein the polypropylene resin composition constituting the foamed layer comprises a polypropylene resin derived from recycled polypropylene and an ethylene propylene rubber.
[0722] [1-4] The polypropylene resin foamed beads according to any one of [1-1] to [1-3], wherein the flexural modulus of the polypropylene resin composition constituting the foamed layer is 800 MPa to 1300 MPa.
[0723] [1-5] A polypropylene resin foamed bead molded article, wherein the polypropylene resin foamed bead molded article is formed by in-mold molding the polypropylene resin foamed beads described in any one of [1-1] to [1-4].
[0724] According to the methods shown in [1-1] to [1-5], it is possible to provide a polypropylene resin foamed particle and a polypropylene resin foamed particle molded body formed by in-mold molding of the foamed particles, wherein the polypropylene resin foamed particles can be molded into a foamed particle molded body having good in-mold moldability and a low rate of increase in compressive stress associated with an increase in compressive strain. In addition, when the polypropylene resin foamed particle molded body is used for applications such as vehicle components, the molded body preferably has good impact absorption performance. According to the methods shown in [1-1] to [1-5], when compressive strain is applied, a molded body having a low rate of increase in compressive stress associated with an increase in strain can be obtained, thereby providing a molded body having good impact absorption performance.
[0725] From another viewpoint, the expanded beads according to the second embodiment can be understood as the inventions of the expanded beads according to the following [2-1] to [2-10].
[0726] [2-1] A polypropylene resin foamed particle having a foamed layer composed of a polypropylene resin composition, wherein:
[0727] The polypropylene resin composition comprises ethylene propylene rubber,
[0728] The foamed beads have a crystal structure in which, in a DSC curve obtained when the foamed beads are heated from 23° C. to 200° C. at a heating rate of 10° C. / min, a first endothermic peak Pa having the largest peak area and a second endothermic peak Pb adjacent to the first endothermic peak Pa on the high temperature side of the first endothermic peak Pa appear;
[0729] The independent bubble rate of the foamed particles is more than 85%,
[0730] The temperature Tb of the top of the second endothermic peak Pb is 158° C. or higher,
[0731] The difference Tb-Ta between the temperature Tb of the top of the second endothermic peak Pb and the temperature Ta of the top of the first endothermic peak Pa is 15° C. or more and 30° C. or less,
[0732] A ratio hb / ha of a peak height hb of the second endothermic peak Pb to a peak height ha of the first endothermic peak Pa is 1.2 or more and 2.8 or less.
[0733] [2-2] The polypropylene resin foamed particles according to [2-1], wherein the polypropylene resin composition is a molten mixture of a polypropylene resin composition I containing an ethylene-propylene rubber and a polypropylene resin B.
[0734] [2-3] The polypropylene resin foamed particles according to [2-2], wherein the polypropylene resin composition I has a morphology with a polypropylene resin as a matrix and a rubber-like body containing the ethylene-propylene rubber as microregions, and the polypropylene resin B is a copolymer of propylene and ethylene and / or butene.
[0735] [2-4] The polypropylene resin foamed particles according to [2-2] or [2-3], wherein the mass ratio of the polypropylene resin composition I to the polypropylene resin B is resin composition I:resin B=3:97 to 40:60.
[0736] [2-5] The polypropylene resin foamed particles according to any one of [2-2] to [2-4], wherein the polypropylene resin composition I is derived from post-consumer materials.
[0737] [2-6] The polypropylene resin foamed particles according to any one of [2-2] to [2-5], wherein the flexural modulus of the polypropylene resin B is 900 MPa to 1500 MPa.
[0738] [2-7] The polypropylene resin foamed particles according to any one of [2-1] to [2-6], wherein the foamed particles are heated from 23°C to 200°C at a heating rate of 10°C / min, then cooled to 23°C at a cooling rate of 10°C / min, and then heated again from 23°C to 200°C at a heating rate of 10°C / min, and the melting end temperature in the second DSC curve obtained is 160°C or above.
[0739] [2-8] The polypropylene resin foamed particles according to any one of [2-1] to [2-7], wherein the full width at half maximum of the first endothermic peak Pa is 15°C or more and less than 25°C.
[0740] [2-9] The polypropylene resin foamed beads according to any one of [2-1] to [2-8], wherein the average cell diameter of the foamed beads is 40 μm or more and 100 μm or less.
[0741] [2-10] The polypropylene resin foamed particles according to any one of [2-1] to [2-9], wherein the apparent density of the foamed particles is 10 kg / m 3 Above and 80kg / m 3 .
[0742] According to the methods shown in [2-1] to [2-10], it is possible to provide a polypropylene resin foamed particle which has good in-mold formability and a good balance between rigidity and in-mold forming pressure even when the foamed particle is composed of a polypropylene resin composition containing ethylene-propylene rubber.
[0743] In addition, from another point of view, the method for producing foamed particles involved in embodiment 3 and the resin composition A used as the raw material for foamed particles can be grasped as the invention of the method for producing foamed particles involved in the following [3-1] to [3-5] and the invention of the resin raw material for foamed particles involved in [3-6] to [3-9].
[0744] [3-1] A method for producing foamed particles, comprising: releasing resin particles composed of a polypropylene resin composition impregnated with a foaming agent dispersed in an aqueous medium in a container together with the aqueous medium from the container in an atmosphere having a pressure lower than the pressure in the container, and foaming the resin particles to obtain foamed particles, wherein:
[0745] The resin pellets are composed of a molten mixture of a polypropylene resin composition A and a polypropylene resin B, wherein the polypropylene resin composition A includes a polypropylene resin composition a derived from an automobile component and has a melting point of 160° C. or higher, and the polypropylene resin B has a melting point of 130° C. or higher and less than 160° C.,
[0746] The mass ratio of the polypropylene resin composition A to the polypropylene resin B in the resin particles is polypropylene resin composition A:polypropylene resin B=3:97 to 60:40.
[0747] [3-2] The method for producing foamed beads according to [3-1], wherein the melting point Tm of the polypropylene resin composition A is A The melting point Tm of the polypropylene resin B B Difference Tm A -Tm B It is 10°C or higher and 30°C or lower.
[0748] [3-3] The method for producing foamed beads according to [3-1] or [3-2], wherein the melt flow rate of the polypropylene resin composition A measured at a temperature of 230° C. and a load of 2.16 kg is 10 g / 10 min or more and 40 g / 10 min or less.
[0749] [3-4] The method for producing expanded beads according to any one of [3-1] to [3-3], wherein the ash content of the polypropylene resin composition A is 1% by mass or more and 25% by mass or less.
[0750] [3-5] A method for producing foamed particles according to any one of [3-1] to [3-4], wherein the polypropylene resin composition A shows a morphology in which a polypropylene resin is used as a matrix and a rubber-like body containing ethylene-propylene rubber is used as a micro-region, and a bending elastic modulus is greater than or equal to 800 MPa and less than or equal to 1200 MPa.
[0751] [3-6] A resin raw material for foamed particles, which is used for the production of foamed particles, wherein:
[0752] The resin raw material is a polypropylene resin composition including a polypropylene resin composition a derived from an automobile member,
[0753] The melting point of the polypropylene resin composition is 160° C. or higher.
[0754] [3-7] The resin raw material for foamed beads according to [3-6], wherein the resin raw material has a melt flow rate of 10 g / 10 min or more and 40 g / 10 min or less when measured at a temperature of 230° C. and a load of 2.16 kg.
[0755] [3-8] The resin raw material for foamed beads according to [3-6] or [3-7], wherein the ash content of the resin raw material is 1% by mass or more and 25% by mass or less.
[0756] [3-9] A resin raw material for foamed particles according to any one of [3-6] to [3-8], wherein the resin raw material shows a morphology in which a polypropylene resin is used as a matrix and a rubber-like body containing ethylene-propylene rubber is used as a microregion, and the bending modulus of the resin raw material is greater than or equal to 800 MPa and less than or equal to 1200 MPa.
[0757] According to the methods shown in [3-1] to [3-9], it is possible to provide a method for producing foamed particles that can effectively and flexibly utilize resin components from automotive components and can produce foamed particles with good in-mold formability, as well as a resin raw material for foamed particles used in the method for producing foamed particles.
[0758] From another viewpoint, the expanded beads and the method for producing the same according to the fourth embodiment can be understood as the inventions of the method for producing expanded beads according to the following [4-1] to [4-7] and the inventions of expanded beads according to [4-8] to [4-10].
[0759] [4-1] A method for producing expanded beads, the method comprising foaming polypropylene resin particles to obtain expanded beads, wherein:
[0760] The resin pellets are composed of a molten mixture of a polypropylene resin composition A and a polypropylene resin B, wherein the polypropylene resin composition A comprises a polypropylene resin composition derived from post-consumer materials, and the melting point Tm A Above 160°C, the bending modulus M A is 800 MPa or more and 1200 MPa or less, and the melting point Tm of the polypropylene resin B is B Less than 160℃, bending modulus M B 900 MPa or more and 1400 MPa or less,
[0761] The bending elastic modulus M B With respect to the bending elastic modulus M A Ratio M B / M A is 1 or more,
[0762] The mass ratio of the polypropylene resin composition A to the polypropylene resin B in the resin particles is polypropylene resin composition A:polypropylene resin B=10:90 to 70:30.
[0763] [4-2] The method for producing foamed particles according to [4-1], wherein the resin particles are composed of a polypropylene resin composition r, and the melting point Tm of the polypropylene resin composition r is r 150°C or higher and 162°C or lower, the bending modulus M r It is 900 MPa or more and 1300 MPa or less.
[0764] [4-3] The method for producing foamed beads according to [4-1] or [4-2], wherein the melting point Tm of the polypropylene resin composition A is A The melting point Tm of the polypropylene resin B B Difference Tm A -Tm B It is 5°C or higher and 20°C or lower.
[0765] [4-4] The method for producing foamed beads according to any one of [4-1] to [4-3], wherein the melt mass flow rate of the polypropylene resin composition A measured at a temperature of 230° C. and a load of 2.16 kg is 10 g / 10 min or more and 40 g / 10 min or less.
[0766] [4-5] The method for producing foamed beads according to any one of [4-1] to [4-4], wherein the polypropylene resin composition A has a morphology in which a polypropylene resin is a matrix and a rubber-like body containing ethylene propylene rubber is a microdomain.
[0767] [4-6] The method for producing expanded beads according to any one of [4-1] to [4-5], wherein the bulk density of the expanded beads is 10 kg / m 3 Above and 200kg / m 3 the following.
[0768] [4-7] The method for producing expanded beads according to any one of [4-1] to [4-6], wherein the expanded beads have a closed cell ratio of 90% or more.
[0769] [4-8] A foamed particle, which is composed of a polypropylene resin composition R, wherein the polypropylene resin composition R comprises a polypropylene resin composition derived from post-consumer materials, and has a melting point Tm R 150°C or higher and 162°C or lower, the bending modulus M RIt is 900 MPa or more and 1300 MPa or less.
[0770] [4-9] The foamed particles according to [4-8], wherein the bulk density of the foamed particles is 10 kg / m 3 Above and 200kg / m 3 the following.
[0771] [4-10] The expanded beads according to [4-8] or [4-9], wherein the expanded beads have a closed cell ratio of 90% or more.
[0772] According to the methods shown in [4-1] to [4-10], it is possible to provide a foamed bead and a method for producing the same which can effectively utilize a resin component derived from post-consumer materials, have good in-mold moldability, and can produce a foamed bead molded body having excellent compressive strength.
[0773] From another viewpoint, the method for producing expanded beads according to the fifth embodiment can be understood as the invention of the method for producing expanded beads according to the following [5-1] to [5-4].
[0774] [5-1] A method for producing polypropylene resin foamed particles, comprising releasing polypropylene resin particles containing a foaming agent dispersed in a dispersion medium in a closed container together with the dispersion medium from a low-pressure region in the closed container that is lower than the pressure in the container, to foam the polypropylene resin particles, wherein:
[0775] The polypropylene resin composition constituting the polypropylene resin particles is a melt mixture obtained by kneading at least one propylene random copolymer selected from the group consisting of ethylene-propylene random copolymers and ethylene-propylene-butene random copolymers and an impact polypropylene having a morphology of a polypropylene resin as a matrix and a rubber-like body containing ethylene-propylene rubber as micro-domains.
[0776] The mass ratio of the blending amount of the propylene random copolymer to the blending amount of the impact polypropylene satisfies the following: propylene random copolymer: impact polypropylene = 55:45 to 98:2,
[0777] The melting point of the propylene random copolymer: d (unit: ° C) and the melting point of the impact polypropylene: c (unit: ° C) satisfy the following formulas (I) and (II),
[0778] 150(℃) <c<170(℃)…(I)
[0779] 5(℃)≤cd≤35(℃)…(II)
[0780] Furthermore, the melt mass flow rate f (unit: g / 10 min) of the polypropylene random copolymer measured at a temperature of 230° C. and a load of 2.16 kg and the melt mass flow rate e (unit: g / 10 min) of the impact polypropylene measured at a temperature of 230° C. and a load of 2.16 kg satisfy the following formulas (III), (IV) and (V).
[0781] 3(g / 10min)≤e …(III)
[0782] 0.3≤e / f≤8 …(IV)
[0783] 3(g / 10min)≤f≤10(g / 10min) …(V)
[0784] [5-2] A method for producing polypropylene resin foamed particles according to [5-1], wherein the melt mass flow rate of the polypropylene resin composition constituting the foamed particles measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is greater than or equal to 5 g / 10 min and less than or equal to 20 g / 10 min.
[0785] [5-3] The method for producing polypropylene resin foamed particles according to [5-1] or [5-2], wherein the flexural modulus of the impact polypropylene is 800 MPa or more and 1200 MPa or less.
[0786] [5-4] The method for producing polypropylene resin foamed particles according to any one of [5-1] to [5-3], wherein the flexural modulus M of the impact polypropylene is I With respect to the bending elastic modulus M of the propylene random copolymer B Ratio M I / M B is greater than 1 and less than 2.
[0787] According to the aspects shown in [5-1] to [5-4], it is possible to provide a method for producing foamed beads which has excellent foamability when producing foamed beads from resin particles and also has excellent moldability when in-mold molding using the obtained foamed beads.
Claims
1. A polypropylene resin foamed particle having a foamed layer composed of a polypropylene resin composition, wherein: The polypropylene resin composition comprises a polypropylene resin and a rubber-like body comprising an ethylene-propylene rubber. The rubber-like body is dispersed in the polypropylene resin, The melting point Tm of the foamed particles is 130° C. or higher and 162° C. or lower.
2. The polypropylene resin foamed particles according to claim 1, wherein The amount of the acetone-insoluble component contained in the n-decane extract of the foamed beads is 0.02 g or more and 0.10 g or less per 1 g of the foamed beads, The melting point Tm of the foamed particles is 140° C. or higher and 162° C. or lower. A difference Tm-Tc between a melting point Tm of the foamed particles and a crystallization temperature Tc of the foamed particles is 38° C. or less.
3. The polypropylene resin foamed particles according to claim 1 or 2, wherein The rubber-like body has an average diameter of 0.1 μm or more and 2 μm or less.
4. The polypropylene resin foamed particles according to any one of claims 1 to 3, wherein The polypropylene-based resin composition constituting the foamed layer includes a polypropylene-based resin derived from recycled polypropylene and an ethylene-propylene-based rubber.
5. The polypropylene resin foamed particles according to any one of claims 1 to 4, wherein The polypropylene resin composition constituting the foam layer has a flexural modulus of 800 MPa or more and 1300 MPa or less.
6. The polypropylene resin foamed particles according to any one of claims 1 to 5, wherein The foamed beads have a crystal structure in which, in a DSC curve obtained when the foamed beads are heated from 23° C. to 200° C. at a heating rate of 10° C. / min, a first endothermic peak Pa having the largest peak area and a second endothermic peak Pb adjacent to the first endothermic peak Pa on the high temperature side of the first endothermic peak Pa appear; The independent bubble rate of the foamed particles is more than 85%, The temperature Tb of the top of the second endothermic peak Pb is 158° C. or higher, The difference Tb-Ta between the temperature Tb of the top of the second endothermic peak Pb and the temperature Ta of the top of the first endothermic peak Pa is 15° C. or more and 30° C. or less, A ratio hb / ha of a peak height hb of the second endothermic peak Pb to a peak height ha of the first endothermic peak Pa is 1.2 or more and 2.8 or less.
7. A method for producing polypropylene resin foamed particles, which comprises foaming polypropylene resin particles having a core layer to obtain polypropylene resin foamed particles having a foamed layer, wherein: The core layer is composed of a molten mixture of a polypropylene resin composition containing ethylene-propylene rubber and having a melting point of 160° C. or higher, and a polypropylene resin having a melting point of 125° C. or higher and less than 160° C. The mass ratio of the polypropylene resin composition to the polypropylene resin in the core layer is polypropylene resin composition:polypropylene resin=2:98 to 70:
30.
8. The method for producing polypropylene resin foamed particles according to claim 7, wherein: The melting point of the polypropylene resin is 130°C or higher and lower than 160°C.
9. The method for producing polypropylene resin foamed particles according to claim 7 or 8, wherein: The polypropylene resin composition is impact-resistant polypropylene.
10. The method for producing foamed polypropylene resin particles according to any one of claims 7 to 9, wherein The melting point Tm of the polypropylene resin composition I The melting point Tm of the polypropylene resin B Difference Tm I -Tm B It is 5°C or higher and 35°C or lower.
11. The method for producing foamed polypropylene resin particles according to any one of claims 7 to 10, wherein: The melt mass flow rate MFR of the polypropylene resin composition measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is I It is 3 g / 10 minutes or more and 40 g / 10 minutes or less.
12. The method for producing foamed polypropylene resin particles according to any one of claims 7 to 11, wherein The polypropylene resin composition has a flexural modulus of 800 MPa or more and 1200 MPa or less.
13. The method for producing foamed polypropylene resin particles according to any one of claims 7 to 12, wherein: The polypropylene-based resin composition includes a polypropylene-based resin derived from recycled polypropylene and an ethylene-propylene-based rubber.
14. The method for producing foamed polypropylene resin particles according to any one of claims 7 to 13, wherein The resin particles impregnated with a blowing agent dispersed in an aqueous medium in a container are released from the container together with the aqueous medium in an atmosphere having a pressure lower than the pressure in the container, thereby foaming the resin particles to obtain foamed particles.
15. The method for producing foamed polypropylene resin particles according to any one of claims 7 to 14, wherein: The melting point Tm of the polypropylene resin composition I The melting point Tm of the polypropylene resin B Difference Tm I -Tm B 5℃ or above and 35℃ or below, The melt mass flow rate MFR of the polypropylene resin composition measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is I More than 3g / 10 minutes, The melt mass flow rate MFR of the polypropylene resin measured under the conditions of a temperature of 230° C. and a load of 2.16 kg is B 3g / 10min or more and 10g / 10min, The melt mass flow rate MFR of the polypropylene resin composition I Relative to the melt mass flow rate MFR of the polypropylene resin B MFR I / MFR B It is 0.3 or more and 8 or less.
Citation Information
Patent Citations
Method of recovering valuable resource from dust of abandoned automobile shredder
JP2004058032A
Method of and apparatus for sorting crushed industrial waste
JP2008178846A
Method for treating resin waste, and system for treating resin waste
JP2018122299A